Metabolomics-based analysis of dynamic metabolic trajectories and regulatory networks in two-stage fermentation of kiwifruit wine - Wangsheng Sun; Pengfei Bi; Wanju Yan; Rou Cai; Zhendong Zhang; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Jing Guo (Food Microbiology, 2027)

State-dependent alterations of network characteristics between seizure and non-seizure onset zones in drug-resistant epilepsy - Kunlin Guo; Kunying Meng; Renping Yu; Lipeng Zhang; Yuxia Hu; Rui Zhang; Dezhong Yao; Mingming Chen (Cognitive Neurodynamics, 2026)

Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Study on the O2 migration pathway and critical product formation mechanism in the water immersion coal oxidation - Guo-yu Shi; Xin-xiao Lu; Guan Wang; Zhao Yang; Long He; Rui-nan Zhang (Fuel, 2026)

Balancing fermentation control and aroma complexity in semi-spontaneous kiwifruit fermentation through Saccharomyces cerevisiae inoculum level - Wanju Yan; Yuanjing Li; Zitong Zhang; Rou Cai; Sinuo Feng; Jia Han; Wangsheng Sun; Rui Cai; Zhouli Wang; Jing Guo (Food Research International, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

Addressing the protein challenge in aquaculture: Nutritional attributes, application bottlenecks and refinement strategies for single-cell protein - Jiayv Zhang; Shanfei Fu; Rui Li; Mengxue Li; Zhenni Cheng; Xiaolei Fan; Rongbo Guo; Haiqing Wang (Animal Feed Science and Technology, 2026)

Investigation of electrode-free, room temperature, flexible NH3 sensors with high stability and sensitivity using MXene@PANI-MWCNTs ink - Jiahui Zheng; Bochao Ma; Xiaoqing Cui; Rui Wang; Li An; Bin Guo; Hongyan Zhang (Analytica Chimica Acta, 2026)

Biochar strengthens rainfall regime resistance of soil inorganic C by enhancing pH–bicarbonate and carbonic anhydrase regulation in dryland region - Yuhao Wang; Yanbo Ji; Shutong Guo; Lin Sun; Enke Liu; Zhikuan Jia; Kadambot H.M. Siddique; Rui Qian; Ting Wei; Peng Zhang (Agriculture, Ecosystems & Environment, 2026)

Effect of double-cropping pattern on biological yield and quality of silage corn across different cropping systems in the Hebei region - Liang Song; Min Jia; Quanguo Zhang; Jianghao Wang; Liwei Wang; Rui Guo; Yuanyuan Yan; Jianfeng Wei; Xinghua Li; Wei Song (Next Research, 2026)

A review of molybdenum disulfide-based materials (MoS2) for piezocatalytic degradation of organic pollutants - Sa Li; Jiarui Zhang; Xuefei Lei; Biao Wang; Wei Cai; Xuanwen Liu; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

Transient geomorphic processes revealed by luminescence sensitivity of Yellow River terrace sediments - Ya Liu; Zheng-Hao Gu; Jia-Fu Zhang; Xue Rui; Yu-Jie Guo; Song-Xi Du; Yu-He Shen; Qing-Hao Ma (Geomorphology, 2026)

Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Ultrasound/electrostatic field combined with ε-polylysine for improving the quality of ready-to-eat pork jelly and freshness classification based on convolutional neural network - Qing Guo; Min Zhang; Bhesh Bhandari; Qi Yu; Luming Rui (Food Chemistry, 2026)

From charge dependence to host-guest recognition: A reliable CZE method for simultaneous separation and determination of flavonoid glycosides with similar structures - Rui Zhang; Biying Guo; Xin Zhou; Fuyu Yang; Yong Xu (Food Chemistry, 2026)

Simultaneous extraction of keratin and gelatin from eggshell membrane via a one-step alkali method: Structural features and functional characterization - Yanli Guo; Xinyi Ju; Rui Chuang; Huajiang Zhang; Lina Xu; Lei Jin; Ning Xia; Tong Zhang; He Zhang (Food Chemistry, 2026)

Dual signal-enhanced immunochromatographic test strip based on Au@PtNPs: From sensitive detection of thiamethoxam to multiplex pesticide screening in vegetables - Zhengtao Li; Lingjun Geng; Jiashuai Sun; Jingcheng Huang; Rui Xu; Zhen Guo; Shouyi Dou; Liying Zhang; Fangling Du; Yemin Guo; Xia Sun; Nortoji A. Khujamshukurov (Food Chemistry, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Prenatal exposure to outdoor artificial light at night and neonatal thyroid function: Identifying critical windows of susceptibility - Wanting Miao; Yanling Shu; Qing Fang; Gaojie Fan; Jing Peng; Li Zhang; Binghai Liu; Wenwen Guo; Lianyan Yan; Jiaoyan Li; Rui Chen; Xiaoning Lei; et al. (Environmental Pollution, 2026)

Ultrasonic torsional wave excitation using a double-layer flexible magnetostrictive transducer for HDPE pipe monitoring - Kai Wang; Yizhou Guo; Yini Song; Yiru Xiao; Rui Zhang (Engineering Structures, 2026)

A biomimetic mineralized injectable hydrogel enables spatiotemporal dual-drug delivery for colorectal cancer therapy - Jing-Yu Feng; Rui Zhang; Jing-Ling Yang; Rui Lu; Kiran Thakur; Fei Hu; Yi-Long Ma; Jian-Guo Zhang; Zhao-Jun Wei (Chemical Engineering Journal, 2026)

Temperature-responsive topology regulation for fire-safe, high-strength polyamide 66 via a low-barrier phosphonate spacer - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Ya-Dong Wang; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2026)

Interfacial electronic coupling in Bi2O3/COF heterostructures for high-performance supercapacitors - Rui Zhang; Hong-xia Gao; Yu-ting Zhao; Li Li; Yan Lv; Xue-yan Wu; Jixi Guo; Rui Xue (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

Solvent-triggered dissolution-gelation for multiscale structural densification of lignocellulosic biocomposites - Yifan Guo; He Zhang; Tongxin Bian; Xiufang Ma; Xiu Dong; Rui Fan; Wei Wei; Yun Wan; Bin Yang; Zuowan Zhou (Chemical Engineering Journal, 2026)

Mechanobiological antagonism of integrin β1/β3 gates YAP-driven reactionary dentinogenesis through fluid shear stress sensing - Peiqi Liu; Hui Zhang; Haoyu Wang; Jingning Gou; Lingxiang Lian; Bilun Jin; Yi Guo; Wei Gong; Chenxu Wang; Yijie Wang; Rui Zou; Bo Cheng; et al. (Chemical Engineering Journal, 2026)

Soil deposition reduces bacterial network complexity and stability by shifts in life-history strategies on the Loess Plateau of China - Yanqing Guo; Hailun Zhang; Shunxiang Yao; Bin Zhu; Rui Ma; Xiuling Li; Qianjin Liu; Qiqi Sun; Shengli Guo; Yaxian Hu; Lanlan Du (Applied Soil Ecology, 2026)

Regulatory mechanisms underlying dynamic variation of DHA, EPA, and odd-chain fatty acids content in Auran tiochytrium sp. SZ13 - Rui Luo; Buwen Sun; Jiaxing Li; Nannan Zhang; Meihan Chen; Ziyu Du; Shuo Li; Jialin Guo; Bin Liu; Dongzhe Sun (Algal Research, 2026)

Corrigendum to “Evaluation of street-scale air pollution using multi-source data fusion” [Sustainable Cities and Society 148 (2026) 107644] - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Evaluation of street-scale air pollution using multi-source data fusion - Zhihao Guo; Xun Zhang; Zongning Wu; Rui Zhou; Xiansheng Liu; Jin Zou (Sustainable Cities and Society, 2026)

Buckling mode shifting of subsea pipelines under linear temperature field - Dongyang Liu; Qian Zhang; Zhenkui Wang; Shengjie Rui; Lizhong Wang; Zhen Guo (Ocean Engineering, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

Ecological risk assessment of caffeine in global aquatic ecosystems: From land to sea - Bo Fan; Xiaolong Guo; Baoyi Zhao; Xinyue Zhang; Yanting Mao; Baokun Lei; Rui Xu; Yuhan Yang; Yunrui Li; Junlang Deng; Yishu Deng (Journal of Hazardous Materials, 2026)

A Porous Zn-Salen-Based Organic Ionic Polymer as a Robust Bifunctional Catalyst for CO2 Fixation via Epoxide Cycloaddition - Guo-Ling Li; Rui-Yao Qin; Meng-Meng Wang; Qing Li; Shijian Lu; Jin-Shui Su; Qi Zhang; Yun Zhao; Ran Zhang; Zhong-Hai Ni (Journal of Environmental Chemical Engineering, 2026)

Highly efficient and selective recovery of rare earths from NdFeB waste via water-regulated deep eutectic solvent - Jianru Li; Cunying Xu; Rui Luo; Qibo Zhang; Yixin Hua; Mingyuan Gao; Rongrong Deng; Mengwei Guo; Yan Li (Journal of Cleaner Production, 2026)

Fluoride induced chondrocyte extracellular matrix degradation by inhibition of glycolysis by the PHD2/HIF1α signaling pathway - Yu Gui; Rui Ma; Lan Ma; Tingling Zou; Kaiqiang Zhang; Xiaoying Guo (Environmental Toxicology and Pharmacology, 2026)

Two-phase flow in clayey silt hydrate reservoirs drives migration and clogging of fine clay particles - Jiang Lei; Wei Guo; Yuan Wang; Wen Zhang; Huie Chen; Pengyu Zhang; Rui Jia (Engineering Geology, 2026)

Relative-effect metrics do not reflect societal burden under population ageing: Evidence from cold spell–related dementia mortality in China - Rui Zhang; Songwang Wang; Yujie Meng; Huan Zheng; Zixiong Zhao; Qing Guo; Shuo Zhan; Qiang Chen; Chaonan Wang; Jia Zhao; Ainan Jia; Xuejie Du; et al. (Environmental Impact Assessment Review, 2026)

Overcoming mass-transfer bottlenecks in thick electrodes via in-situ growth of high-entropy sulfides on 3D freeze-printed nickel frameworks - Long-Zhe Wei; Yi-Ting Zhang; Hui Sun; Rui-Fen Guo; Ping Shen (Chemical Engineering Journal, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Metal covalent organic frameworks with donor-acceptor-catalytic site (D-A-C) for boosting CO2 photoreduction - Shi-Wen Zhang; Wen-Yi Zheng; Shu-Zhi Hu; Qian-Rui Mao; Mi Tian; Wang-Kang Han; Zhi-Guo Gu (Chemical Engineering Journal, 2026)

A narrow-bandgap organic photothermal material enabling efficient solar driven sustainable electricity-water cogeneration - Xiaoqing Liu; Bingpeng Guo; Rui Wei; Huijun Kong; Jiahui Yu; Baolei Wang; Weiyan Li; Jingyue Zhang; Chuanying Wang; Zhongqian Song; Changxiang Shao (Chemical Engineering Journal, 2026)

Polymer-based hydrogen barrier coatings: Material design, mechanisms, and theoretical simulation - Zhuofan Li; Zhibin Chen; Lingwei Ma; Jinke Wang; Xin Guo; Rui Tian; Bowei Zhang; Huaiyuan Wang; Dawei Zhang (Chemical Engineering Journal, 2026)

Mesoporous carbon nanospheres-confined ZnMn2O4/Mn3O4 heterostructures for sustainable zinc-ion storage - Ling-Xin Kong; Songtao Zhang; Yaxun Hu; Peng Liu; Wanchang Feng; Zefan Sang; Xiaotian Guo; Hao Gong; Rui Wang; Dae Joon Kang; Huan Pang (Chemical Engineering Journal, 2026)

Tick-type Schottky contact engineering via Ni-CoOx interlayer for enhanced electron transfer in PEM water electrolyzers - Weiding Wang; Kaini Zhang; Hao Wang; Rui Zhao; Chuanjie Lin; Luning Li; Xinzhe Li; Jinzhan Su; Liejin Guo (Chemical Engineering Journal, 2026)

Identifying ventilation corridors in a coastal mountainous city under multiple circulation scenarios: CFD-based mountain resistance parameterization and directional-consistency screening - Qijin Guo; Yaoyu Lin; Xiaojun Zhang; Yilin Li; Rui Si (Building and Environment, 2026)

Roles of Fe3O4 nanoparticles in enhancing anaerobic digestion of synthetic wastewater with high chemical oxygen demand - Xinying Huang; Yi Gao; Rui He; Xiaobo Guo; Yanyu Zhang; Luyi Chang; Ke Pan; Yunhui Lei (Biomass and Bioenergy, 2026)

Fracture development characteristics in carbonate reservoirs: insights from stress field simulation with a heterogeneous rock mechanics model and adaptive boundaries - Yao Wang; Wenlong Ding; Zhongliang Guo; Chenggang Li; Bochao Tang; Ziyou Zhang; Dong Fu; Rui Xia (Carbonates and Evaporites, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Microbe-mediated coupling of soil disease suppression and rhizobial symbiosis in legume diversified cropping systems - Xiang-Yu Zhang; Rui Yuan; Xue Guo; Wen-Xue Zhang; Hao-Ran Li; Cao-Yue Wu; Jun-Yu Zhao; Ting-Ting Zhang; Hong-Wei Wang; Ricardo A. R. Machado; Stefan Scheu; Yong Jia; et al. (Plant and Soil, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Dimefluthrin-induced multigenerational endocrine toxicity in zebrafish (Danio rerio) offspring via parental exposure - Wei-Guo Wang; Rui-Rui Li; Ming-Jun Yang; Jing-Ying Hu; Wen-Ping Xu; Li-Ming Tao; Yang Zhang (Pesticide Biochemistry and Physiology, 2026)

Sleeper-induced pipeline buckling under non-uniform transient temperature field - Dongyang Liu; Zhenkui Wang; Haoyan Sun; Qian Zhang; Shengjie Rui; Lizhong Wang; Zhen Guo (Ocean Engineering, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

Compartment-specific host association and mobility shape ARG risk in aquaculture systems - Zhong-Quan Jiang; Rui-Kai Xing; Di Peng; Yuan-Hao Ren; Tian-Yi Wei; Wen-Bo Guo; Zhe-Min Shen; Chao-Nan Wang; Feng-Li Zhang; Tao Yuan (Journal of Hazardous Materials, 2026)

Long-term variations and formation drivers of PM2.5 nitrate in a megacity of Guanzhong Plain, China: Implications for air quality management - Liang Wen; Yan Yang; Yujie Zhang; Jiaying Feng; Rui Gao; Wei Guo; Shengnan Guo; Hao Wang; Fahe Chai; Hartmut Herrmann; Andreas Tilgner; Thomas Schaefer; et al. (Journal of Environmental Sciences, 2026)

Micritization mechanism in penecontemporaneous carbonate rocks: coupled C − Ca cycles and constraints from diagenetic environments - Yunfeng Zhang; Menghao Zhu; Wen Yan; Haizhou Qu; Kexin Guo; Weihai Xu; Xiyang Zhang; Fei Tan; Yu Tang; Rui Wang; Guanghui Wu; Shuai Huang (Geochimica et Cosmochimica Acta, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Quinoa bran polyphenol extract ameliorates NAFLD through modulating Allobaculum and regulating pantothenate and CoA biosynthesis alongside retinol metabolism - Minjun Sun; Sarina Ma; Rui Wang; Ying Miao; Rui Huo; Qixin Gu; Wenhui Guo; Dongyan Li; Meili Zhang (Food Bioscience, 2026)

Geometry-programmed microcapsules for rice-leaf interface pinning and targeted fungicide delivery - Xiquan Ding; Lei Wang; Meng Yu; Hongwei Li; Yinmin Wang; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Phase-change-gated nanocapsules synchronize fungicide release and plant transport for wheat crown-rot control - Xiquan Ding; Yu Fang; Zheng Zhang; Dongyin Yi; Ze Lv; Yang Gao; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Anti-chlorine corrosion strategies and selective oxygen evolution in seawater electrolysis: A review - Chao Guo; Yijie Zhang; Yuan Gao; Rui Yao; Jinping Li; Guang Liu (Chemical Engineering Journal, 2026)

Genetic dissection of a key dynamic growth period QTL for source–sink-related traits and its breeding application potential in wheat - Meng Yuan; Hongke Ding; Yunkai Yue; Chuanliang Zhang; Yuze Wang; Dandan Zhang; Shipeng Li; Ruiqi Nie; Jia Liu; Yanchuan Huang; Jinyu Han; Sufu Deng; et al. (Theoretical and Applied Genetics, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Autophagy dysfunction in pancreatic acinar cells in acute pancreatitis: from molecular mechinery and trypsinogen activation to heterogeneity and therapeutic implications - Yuping Feng; Wen Guo; Rui Wu; Tingting Tan; Chen Tang; Li Zhang (Journal of Molecular Histology, 2026)

Higher nutrient availability fosters intricate bacterial networks in rhizosphere of invasive plants - Mengxin Zhao; Han Zhang; Qiao Li; Die Zhang; Jianying Guo; Rui Wang; Fengjuan Zhang; Fanghao Wan; Wanxue Liu (Applied Soil Ecology, 2026)

Single-cell transcriptomic analysis identifies a MIF-driven keratinocyte-macrophage-Th2 axis as a key inflammatory circuit in atopic dermatitis - Yan Wei; Rui-Min Bai; Hao-Ran Guo; Jin Shan; Li-Juan Wang; Yan Zhou; Kuan-Hou Mou; Yan Zheng; Ya-Guang Zhang (Inflammation Research, 2026)

Infiltration behavior of shield slurry in highly permeable sandy strata: non-newtonian rheological effects and pressure transmission mechanisms - Shaoxuan Guo; Qingsong Zhang; Rui Li; Changzhi Shao; Xianghui Li; Zhanchao Yin (Transportation Geotechnics, 2026)

The phase and energy-level evolutions in seven distinct sequential states and their hierarchical memory effect of isomeric MOFs - Rui-Fang Ma; Jia-Xin Wu; Ming-Zhu Chen; Tao Liu; Jian Li; Yi-Bo Zhang; Lei Shi; Sheng Liao; Fei Gao; Yi-Hang Guo; Yingbo Zhao; Zheng Yin; et al. (Science Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Regulation of photosynthesis and ROS homeostasis by Fd1 and FNR1 confers thermotolerant yield stability in rice - Qiaoyan Wang; Qingmei Su; Man Li; Dongdong Chen; Yuchun Rao; Pengfei Dong; Bingxin Ye; Tingyi Wang; Zhiqi Hao; Rui Pang; Ruiying Li; Guangheng Zhang; et al. (Science Bulletin, 2026)

Corrigendum to “Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems” [Food Res. Int. 235 (2026) 119173] - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Integrative metabolomic and genomic characterization of the high antimicrobial activity of Lacticaseibacillus paracasei and its potential for juice preservation - Fu Wei; Yanmei Sun; Yaping Mi; Chen Liang; Meichi Yue; Kehui Zhang; Rui Dong; Ziyi Zhang; Qiannan Yang; Songtao Guo; Shiwei Wang (Food Research International, 2026)

Preparation of multifunctional hydrogel composed of polyvinyl alcohol/ chitosan/cellulose nanofiber/anthocyanin and its application in intelligent food packaging systems - Zhen-Zhen Lu; Jie Chen; Jing Jin; Xiao-Rui Ge; Xiao-Hui Yao; Wei-Guo Zhao; Dong-Yang Zhang (Food Research International, 2026)

Integrative multi-omics combined with molecular docking and molecular dynamics simulations elucidates the mechanism driving the transition from green notes to fruity aroma during musang king durian ripening - Zhongyan Li; Tianci Yan; Bin Xu; Xulu Luo; Yumei Ding; Wei Fan; Qin Qiao; Shaojie Yuan; Hui Guo; Meng Zhang; Yan Zhao; Rui Wang; et al. (Food Research International, 2026)

Numerical manifold method for compression molding of granular materials - Xuezhen Zhai; Yuchen Guo; Yongjia Zhang; Rui Yue; Liuchen Shu; Youjun Ning; Pengwan Chen; Ge Kang (Computers and Geotechnics, 2026)

Visible-light-driven N-CDs/Cu photocatalysis for CO2 valorization to selenylated vinyl oxazolidinones - Jun-Bo Wang; Jia-Tong Guo; Shu-Rui Wang; Bei Ruan; Zhan-Hui Zhang (Chemical Engineering Journal, 2026)

Band engineering via doping modification in Bi2O2Se for enhanced photoelectric conversion efficiency - Xinyu Guo; Chen Li; Rui Zhang; Peijie Ma; Xiaoyu Ma; Kun Zheng (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Microalgae–bacteria photobioreactor (MBPR) based bioremediation of coking wastewater under carbon neutralization background: performance and toxicity evaluation, response metabolism and life cycle assessment (LCA) - Xuejiao An; Lele Gao; Wanjun Hu; Rui Pei; Jiehao Wen; Liuhua Guo; Qinghua Zhang (Bioresource Technology, 2026)

P2Y12-AMPKα2 signaling contributes to cardiomyocyte senescence in doxorubicin-induced heart failure - Qianqian Niu; Huidan Wang; Mengyao Zhao; Hongdou Zhang; Rui Hao; Peiyao Liu; Lijuan Guo; Bulei Chen; Yuting Xi; Peng Li; Yaling Yin (Molecular and Cellular Biochemistry, 2026)

Adaptive Fixed-Time Control Framework for Deterministic Response of Fully Constrained Vessels with Unknown Dynamics - Qiang Guo; Shuangpeng Duan; Jia Zhou; Shengguo Wang; Rui Li; Xianku Zhang (Journal of Marine Science and Engineering, 2026)
To achieve precise trajectory tracking for surface vessels subject to unknown dynamics, strict physical limitations, and external disturbances, this paper proposes an Adaptive Fixed-Time Control Framework that ensures a deterministic response under full constraints. First, navigation safety is guaranteed by employing a Barrier Lyapunov Function (BLF) to strictly confine vessel position states, enabling constrained position tracking without requiring prior knowledge of the desired trajectory. Second, addressing the input constraint aspect of the “full constraints” problem, a fixed-time auxiliary system is introduced to compensate for nonlinearities induced by actuator saturation, thereby maintaining control feasibility. Central to this framework is the realization of a deterministic response; by incorporating fixed-time convergence theory, the controller guarantees that velocity tracking errors converge within a predefined time bound independent of initial conditions. Furthermore, an RBF neural network combined with adaptive techniques is utilized to estimate unknown dynamics and external disturbance bounds online, enhancing robustness and safety in realistic marine environments.

Pharmacological effect of rhCC16 on COPD: anti-senescence via the PI3K-AKT-mTOR pathway - Rui Gao; Shuo Wu; Chu-lin Zhang; Chao-feng Liu; Ting Li; Min Guo; Zhao-yang Chen; Hai-long Wang; Min Pang (Molecular and Cellular Biochemistry, 2026)

Low-dose nitrogen-doped carbon quantum dots boost medium-chain fatty acids production via enhanced proton-electron transfer - Shan-Shan Ye; Rui-Dong Xie; Yong-Yao Zhang; Qing-Lian Wu; Wei-Tong Ren; Hua-Zhe Wang; Juan-Shan Du; Wan-Qian Guo (Water Research, 2026)

Luminescent hydrogel-enabled electrochemiluminescent aptasensor and portable analyzer for on-site quantification of acetamiprid in vegetables - Jiashuai Sun; Lingjun Geng; Jingcheng Huang; Zhen Guo; Rui Xu; Zhiping Yu; Zhengtao Li; Peisen Li; Pengwei Zhang; Shengkun Ren; Elena Zavyalova; Yemin Guo; et al. (Journal of Hazardous Materials, 2026)

Carbon-supported nZVI mediates Fe oxides-DOM interactions to regulate Cd and As bioavailability in co-contaminated soils - Jianhua Guo; Yan Wu; Heng Zhang; Rui Wang; Yue Zhao; Xin Fan; Shuaitao Feng; Zuben Xu (Journal of Environmental Chemical Engineering, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Erosion control performance of geomats on silty soil slopes under simulated rainfall - Rui Zhang; Xiwei Zhang; Kang Chen; Yipeng Guo; Yanhua Yu; Huanhua Cai (Geotextiles and Geomembranes, 2026)

Investigating stress evolution in rock burst prone regions in an underground mine with seismic tomographic imaging - Xu Ma; Rui Ma; Erik Westman; Baisheng Nie; Miao Zhang; Kai Guo (Geomechanics for Energy and the Environment, 2026)

Mechanistic insights into off-flavor masking of textured soy protein using a Maillard reaction system with D-xylose and sulfur-containing amino acids - Jian Ma; Rui Cao; Xuejie Li; Wentao Zhang; Zengwang Guo; Jian Li (Food Research International, 2026)

Secondhand and thirdhand smoke exposure and the risk of liver cancer: a prospective cohort study of 315,833 Chinese never smokers - Zhi Li; Ling-Xiang Xu; Chun-Rui Wang; Zhang-You Guo; Chen-Wei Tang; Xin Dai; Guo-Chao Zhong (Environmental Pollution, 2026)

Developmental light colour influences adult phototaxis and locomotion in Drosophila melanogaster - Rui Han; Jun Zhang; Zi-Yu Guo; Xu-Hui Guo; Sheng-Yu Hou; Ke-Jing Feng; Yu-Xin He; Han-Ning Wu; Xin-Hui Chen (Behavioural Processes, 2026)

Efficacy and Safety of Intravenous Thrombolysis with Tenecteplase in Patients with Wake-Up Branch Atheromatous Disease - Lili Zhu; Ying Zhang; Jiarong Li; Liang Song; Haoran Li; Yang Yang; Lijuan Liu; Shaolei Zhang; Xiaofei Gao; Weifeng Chen; Guo Rui; Haiqiang Qin; et al. (Translational Stroke Research, 2026)
Branch atheromatous disease (BAD), a subtype of acute ischemic stroke (AIS), is associated with a high risk of early neurological deterioration (END) and poor prognosis. Wake-up stroke (WUS), comprising 20%–30% of AIS cases, is typically excluded from thrombolysis because of unknown onset time. Using diffusion-weighted imaging/fluid-attenuated inversion recovery (DWI/FLAIR) mismatch, we evaluated the efficacy and safety of Tenecteplase (TNK) thrombolysis in patients with BAD-related WUS. We retrospectively recruited 1,062 patients from seven Zhengzhou hospitals between January 2021 and June 2025. The patients received either TNK (n = 338) or dual antiplatelet therapy (n = 724). Propensity score matching (PSM; 1:1, caliper 0.02) yielded 292 matched pairs. Early neurological changes were evaluated using the National Institutes of Health Stroke Scale (NIHSS), and 90-day outcomes were evaluated using the modified Rankin Scale (mRS). After PSM, TNK significantly reduced the risk of END (odds ratio [OR] = 0.425, 95% confidence interval [CI]: 0.262–0.689; P < 0.001). Patients treated with TNK were more likely to achieve good functional outcomes (modified Rankin Scale [mRS] 0–1 and 0–2) with fewer poor outcomes (mRS ≥ 4). There were no significant differences in symptomatic intracranial hemorrhage, other bleeding events, or mortality among the groups. DWI/FLAIR mismatch-guided TNK thrombolysis appears to overcome the limitations of an unknown onset time in WUS and may counteract the progressive pathophysiology of BAD. TNK intravenous thrombolysis may be a safe and effective treatment for patients with wake-up BAD and DWI/FLAIR mismatches.

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Research on the Mechanisms Regulating Soil Microbial Community Structure and Functional Metabolism during Coloured Potato Cultivation with “Seed Rotation” - Yulong Wang; Anle He; Huachun Guo; Fang Yang; Youhan Li; Lei Bai; Jun Li; Rui Zhang (Potato Research, 2026)
To address the continuous cropping obstacles associated with coloured potatoes ( Solanum tuberosum L.) in the red soil region of Yunnan, in this study, two “seed rotation” cultivation regulation modes, namely cultivar rotation (red potato–purple potato) and crop rotation (red/purple potato–soybean), were innovatively proposed. Through pot experiments, the regulatory effects of different cultivation modes on soil nutrients, enzyme activities, microbial community structure, and functional metabolic networks were systematically analysed. Compared with the monocropping of a single potato cultivar, the cultivar switching treatment significantly improved the soil nutrient status, with the contents of soil available nitrogen, phosphorus, and potassium significantly increasing by 56.40–58.04%, 14.96–27.44%, and 58.59–62.21%, respectively, while the cultivar rotation treatment had a secondary effect. In addition, the interspecific rotation treatment enriched beneficial bacteria such as Bradyrhizobium ; upregulated the abundance of secondary metabolites, including flavonoids; and activated biosynthetic pathways such as those involving phenylpropanoids, flavonoids, and various amino acids. Compared with the continuous cultivation of a single potato cultivar, the cultivar rotation treatment alleviated the homogenization trend of the soil microbial community, increased the abundance of organic acids and glycosides, and activated pathways such as the shikimate pathway and the biosynthetic pathways of aromatic amino acids (phenylalanine and tyrosine). In summary, both modes, especially the interspecific rotation mode, can improve the soil environment and have significant agronomic application value and ecological environmental benefits. Owing to the similar biological characteristics between the same family, the cultivar rotation mode results in relatively limited changes in the soil microbial community and metabolite composition, but it can delay the occurrence of continuous cropping obstacles. This study provides practical value for the sustainable soil management of potato cultivation in red soil regions.

A comprehensive review on the main alkamides in Piper nigrum and anti-inflammatory properties of piperine - Rui Guo; Yiming Fang; Junyao Li; Haoyang Gao; Zhiqiang Niu; Yadong Lv; Long You; Ji Zhang; Xu Wang; Guiping Wu; Taoyun Wang; Weicheng Hu; et al. (Phytochemistry Reviews, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Investigation of the Spatiotemporal Variation Characteristics and Potential Source Regions of PM2.5, PM10, and O3 in Shiyan, China - Ying Zhang; Shici Zhang; Rui Zhang; Hua Guo; Jinjin Peng; Yuqing Zhao; Zhiyan Zhang; Shuo Zhang; Shan Liu (Aerosol Science and Engineering, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

Multifaceted roles of CcGpi7, a phosphoethanolamine transferase, in physiology and virulence of Corynespora cassiicola - Chao Xu; Mengyuan Hou; Qingzhou Ma; Yue-hua Geng; Rui Zang; Taibo Liang; Yashuang Guo; Mengmeng Yang; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

Construction of a plasmid-based reverse genetics system for the rescue of shrimp infectious covert mortality nodavirus (CMNV) and use in deciphering the role of its B2 protein in regulating its cross-species infectivity - Zhenxin Zhao; Ting Xue; Jinwu Wang; Rui Xiao; Yue Zhang; Meiling Sun; Qingli Zhang; Huarong Guo (Aquaculture, 2026)

Triphasic volatile emission dynamics and gene expression in postharvest PGF-lost non-melting peach (Prunus persica) var. RedY - Ping Zhou; Xiaodan Zhang; Xin Feng; Rui Guo; Shaobin Yan; Xiuqing Wei; Liang Li; Yajun Tang; Zhizheng Fang; Yan Lei (Postharvest Biology and Technology, 2026)

Integrative analysis of physiology, transcriptomics, and metabolomics unveils mechanisms in soybean (Glycine max (Linn.) Merr) response to alkaline stress - Qian Li; Bo Chen; Ziyu Yang; ChenJing Li; Qing Jing; Qinghong Lu; Rui Ni; Pengzhi Mao; Li Zhang; Xinyong Guo (Plant Science, 2026)

Keying process of a novel folding-plate anchor: investigation of installation depth loss - Yue Zhao; Shengjie Rui; Haojie Zhang; Zhen Guo (Ocean Engineering, 2026)

A win-win recycling strategy for spent lithium-ion batteries: Prioritized selective lithium extraction afterwards triggers intrinsic catalysis - Yifan Sui; Zeqiu Chen; Yue Chang; Yaoguang Guo; Jie Guan; Xuning Zhuang; Fei He; Zhenming Zhang; Weihua Gu; Qianqian Chen; Li Fan; Qin Xu; et al. (Journal of Hazardous Materials, 2026)

Structural features and antioxidant efficacy of a novel low-molecular-weight pectic polysaccharide from Fuzhuan brick tea - Xianbao Sun; Jun'ai Zhang; Rui Guo; Xuan Ma; Lihua Song; Yan Wu (Food Bioscience, 2026)

U-shaped multi-scale feature fusion network for three-dimensional geological modelling and uncertainty assessment - Yu Zhang; Rui Wang; Jian Chu; Mingchun Guo (Engineering Geology, 2026)

Dual-sided Pd functionalization of groove-textured CeO2 hollow microcages boosts room temperature NO2 sensing - Yan Tong; Pengkai Xing; Wenbo Ruan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Muhammad Ikram; Xue Bai; Qin Guo; Keying Shi (Chemical Engineering Journal, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Tailoring pore architecture in hard carbons: Clarifying the distinct sodium storage roles of closed pores and ultra-micropores - Wei-wei Kang; Hai-tao Zeng; Guang-xu Huang; Jian-bo Jia; Qiang Li; Han Hu; Bing Xu; Wei-jie Guo; Rui Hao; Bao-lin Xing; Chuan-xiang Zhang (Chemical Engineering Journal, 2026)

Chemically modified bacterial cellulose–mediated fiber salting-out method for preparing tough hydrogels - Bei Zhang; Xin-Xin Chen; Xiao-Rui Ge; Xin-Ping Wang; Xiao-Hui Yao; Wei-Guo Zhao; Tao Chen; Dong-Yang Zhang (Carbohydrate Polymers, 2026)

The association of long-term exposure to PM1 with dyslipidemia in Chinese older adults and the modifying role of vitamin D - Pengjing Yao; Rui Zhang; Xuqiu Cheng; Xinyu Kou; Ziwei Tian; Jinmin Zheng; Yan Zhang; Xianwei Guo; Bing Hu; Changliu Liang; Yufeng Wen; Fangbiao Tao; et al. (Atmospheric Pollution Research, 2026)

Dominant drivers of soil multifunctionality change: interactions among soil, plants, and the atmosphere - Tiantian Luo; Weiyi Zhou; Yun Shi; Fenghong Zhang; Guo Rui; Hongyuan He; Tao Wu; Hongxia Li; Yiting Ma (Plant and Soil, 2026)

Sustainable land use and agricultural management enhance arbuscular mycorrhizal fungal communities and soil health - Huaisong Wang; Juntong Zhu; Mingming Wang; Lei Zhang; Ying Gao; Lianxuan Shi; Jixun Guo; Rui Guo; Tao Zhang (Applied Soil Ecology, 2026)

BsSYT1 is required for growth, conidiogenesis, stress response and virulence of Bipolaris sorokiniana - Yuehua Geng; Feiyu Yan; Yu Zhang; Mengyao Yang; Changshui Li; Ruilin Shi; Chao Xu; Rui Zang; Qin Guo; Yashuang Guo; Qingzhou Ma; Meng Zhang (World Journal of Microbiology and Biotechnology, 2026)

Corrigendum to “Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling” [Tissue and Cell, 97 (2025) 103089] - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2026)

Study on mechanical response and meso-scale behaviour of pile-soil interface under traffic loading - Qingyao Zhang; Jukun Guo; Rui Guo; Wan Zhang; Shengxiang Tang; Yajuan Huang; Jiahao Zhang (Soil Dynamics and Earthquake Engineering, 2026)

The evaluation to combined toxic effects of polypropylene microplastics and benzo[a]pyrene on macrophage cells - Ye-xuan Zhang; Rui Hou; Si-si Chen; Xue-wen Guo; Hong-juan Chen; Li Mao; Wei-juan Zheng; Hong-zhen Lian (Science of The Total Environment, 2026)

The hidden risk of thiocyanate biodegradation: bloom of antibiotic resistance in mixed bacterial consortia - Jiehao Wen; Jingliang Shi; Xuejiao An; Rui Zhao; Liuhua Guo; Qinghua Zhang (Journal of Water Process Engineering, 2026)

Phosphogypsum coupled enzyme-induced calcium carbonate precipitation for soil stabilization: Mechanical performance and sustainable application - Lun Zhang; Yun Dai; Zhenyao Xia; Jun Wu; Zhien Zhu; Yunkang Rao; Hongqiang Shi; Chao Kang; Rui Xiang; Hongwei Guo; Hai Xiao (Journal of Environmental Management, 2026)

Self-assembled 8-shogaol/curcumin nanoparticles via hydrogen bonding: enhanced stability and sustained release in vitro - Rui Zhang; Jing-Yu Feng; Kiran Thakur; Fei Hu; Jian-Guo Zhang; Yi-Long Ma; Zhao-Jun Wei (Food Chemistry, 2026)

Mechanistic insights into polystyrene micro/nanoplastics-facilitated cadmium trophic transfer and aggravated toxicity along a lettuce-snail terrestrial food chain - Fuyu Guo; Bo Xu; Rui Zhang; Yan Chang; Tingting Chu; Meng Zhu; Fengxiang X. Han; Ruyi Yang (Environmental Pollution, 2026)

Enhanced performance of direct contact membrane distillation for aquaculture wastewater treatment via far-ultraviolet/sulfite-based pretreatment - Bing Zhang; Rui Guo; Heli Tang; Bing Zhang; Haiqing Chang; Wenxin Shi (Chemical Engineering Journal, 2026)

Curcumin-derived smart anti-corrosion coating for early damage warning and active protection in diverse lighting and corrosive environments - Jinke Wang; Xin Guo; Congshu Huang; Danni Shang; Zhibin Chen; Rui Tian; Lingwei Ma; Dawei Zhang (Chemical Engineering Journal, 2026)

Improved corrosion resistance of amorphous-containing dual-structured micro-arc oxidation coatings on (Zr0.5Ti0.35Nb0.15)90Al10 high-entropy alloy - Luqi Chai; Xuehui Yan; Yubo Ma; Lijiao Wang; Xin Li; Chungang Guo; Chi Xu; Jiancheng Du; Xiaoyue Jin; Wenbin Xue; Menglu Zhang; Rui Zuo (Chemical Engineering Journal, 2026)

Defect-rich 3D flower-like SnS2-xSex nanostructures for ultrasensitive NO2 gas sensing at room temperature - Shanshan Cong; Pengkai Xing; Wenbo Ruan; Jiahui Fan; Xiaopeng Wang; Rui Zhang; Weixin Lv; Qin Guo; Xue Bai; Keying Shi (Chemical Engineering Journal, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

The climate threshold for locally absent rings in Siberian larch exhibits significant variation with altitude - Xiao-xia Gou; Tong-wen Zhang; Hua-ming Shang; Shu-long Yu; Dong Guo; Rui-bo Zhang; Li Qin; Sheng-xia Jiang; Yu-ting Fan; Ke-xiang Liu; He-li Zhang; Kai-long Guo; et al. (Agricultural and Forest Meteorology, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Rubber-based agroforestry systems enhancing soil carbon sequestration through improved soil aggregate stability - Wenxian Xu; Wenjie Liu; Bo Song; Yingying Zhang; Ashar Tahir; Yumiao Cao; Changgeng Kuang; Xinwei Guo; Rui Sun; Xian Zhang; Qiu Yang; Zhixiang Wu (Soil and Tillage Research, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Integrated metabolomics and transcriptomics analyses reveal the molecular mechanism of anthocyanin accumulation in veins and leaves of Broussonetia papyrifera under cold stress - Xiangxue Yu; Rui Ni; Dingguo Zhang; Bo Chen; Qian Li; Ziyu Yang; Chenjing Li; Fuyuan Liu; Yongtao Xia; Guoqing Hou; Guoping Wang; Pengzhi Mao; et al. (Plant Science, 2026)

Evaluating the environmental impact of hydrothermal cracking solid organic fertilizer: Carbon and nitrogen retention and toxic metals analysis - Rui Xia; Xiao-xiao Yang; Jue Wang; Kai-le Li; Zhi-peng Sun; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Journal of Environmental Sciences, 2026)

Prenatal air pollution exposure and postpartum glucose intolerance in women with gestational diabetes mellitus: Identifying susceptible windows - Gaojie Fan; Qing Liu; Li Zhang; Jing Peng; Li Wu; Qing Fang; Wenwen Guo; Binghai Liu; Lianyan Yan; Jiaoyan Li; Wanting Miao; Rui Chen; et al. (Environmental Research, 2026)

Rewiring (p)ppGpp metabolism for high-yield anaerobic methanol and CO2 conversion in Butyribacterium methylotrophicum - Yuanke Guo; Feiyi Zhuang; Rui Zhang; Ruirui Qin; Jiao Feng; Kequan Chen; Xin Wang (Chemical Engineering Journal, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

The enhanced role of glycine in methanesulfonic acid-methylamine-driven nucleation in urban aerosols and coastal industrial regions - Shuqin Wei; Kaiyu Xue; Xiaokai Guo; Wenyuan He; Tianlei Zhang; Rui Wang (Atmospheric Environment, 2026)

Integrating Machine Learning and Petrophysical Data for 3D Ore Body Modeling: A Case Study of the Bayan Obo Deposit - Shupeng Lu; Ya Xu; Rui Guo; Song Huang; Qianwen Zhang; Yonggang Zhao; Yun Liu; Jian Wang; Liang Zhao (Pure and Applied Geophysics, 2026)

Wave-absorbing grouting for mitigating rockbursts triggered by multi dynamic disturbances in deep tunnels - Heng-Yuan Zhang; Ben-Guo He; Xiang-Rui Meng; Jia-Hua Guan; Hua-Wei Xu (Tunnelling and Underground Space Technology, 2026)

Facile synthesis of dual-group functionalized magnetic starch-based adsorbent for moxifloxacin removal: Performance and mechanisms - Hongwei Yang; Yiyang Chen; Jie Zhang; Rui Zhao; Weikai Guo; Erming Ouyang (Journal of Water Process Engineering, 2026)

Biodegradable microplastics induce more soil nitrous oxide emission than conventional in semi-arid Loess Plateau - Xiaogang Li; Rui Wang; Xinran Zhang; Shengli Guo; Lei Yu; Xiaotang Ju (Journal of Hazardous Materials, 2026)

A one-step strategy for rapid detection of sub-50 nm polystyrene nanoplastics using nanobody-based homogeneous immunoassay - Yang Deng; Yang Guo; Fei Li; Ming Zhang; Yuansheng Yang; Rui Nian; Wenshuai Liu (Journal of Hazardous Materials, 2026)

Enhanced degradation of microplastics by laccase under ambient conditions: Analysis of underlying molecular mechanisms - Rui Ding; Linhan Xu; Xiaoling Shan; Xinran Qiu; Ling Ding; Bin Zhang; Xujun Liang; Lingyan Zhu; Xuetao Guo (Journal of Hazardous Materials, 2026)

Aggregation kinetics and stability of Ce(IV)-borate colloid: Effect of pH, electrolytes, gibbsite colloid, and humic acid colloid - Kang Chen; Rui Zhang; Chunsheng Shi; Shanrong Yuan; Zishuo Li; Daming Zhang; Qiang Jin; Zhijun Guo; Zongyuan Chen (Journal of Contaminant Hydrology, 2026)

Investigation of water and oxygen influence on the coal thermal decomposition entire process kinetic mechanism and gas product source tracing - Xin-xiao Lu; Guo-yu Shi; Rui-nan Zhang; Shuo Wang; Long He; Guan Wang (Fuel, 2026)

Characterization and formation mechanism of key volatile compounds in roasted and enzymatic fragrant sunflower seed oil by GC-O-MS and model reaction - Kangyu Zhao; Rui Chen; Jinting Guo; Mengfei Xie; Liwei Zhang (Food Chemistry, 2026)

Strain-dependent immunomodulatory activities of lipoteichoic acids from probiotics: From interspecies to intraspecies variation - Yini Liu; Rui Xiao; Min Guo; Jingyu Lu; Jianxin Zhao; Ruojie Zhang; Hao Zhang; Gang Wang; Zipei Zhang (Food Bioscience, 2026)

NCOA4-mediated ferritinophagy regulates AgNP-induced ferroptosis in lung cells - Rui Zhang; Haitao Yang; Menghao Guo; Shuyan Niu; Yu Ma; Xin Shen; Liqing Wu; Chenyu Liu; Mengjing Cui; Tianshu Wu; Yuying Xue (Food and Chemical Toxicology, 2026)

Biocarrier with layer-specific structure enhanced the microalgae-partial nitrification-anammox system performance: Insights into microbial aggregation behavior by FT-ICR-MS and XDLVO analysis - Xue Chen; Rui Hu; Jiabang Li; Yuchen Guo; Youfei Zhou; Meilan Zhang; Guihua Zhuo; Xueqin Lu; Guangyin Zhen (Chemical Engineering Journal, 2026)

Understanding the migration and transformation characteristics of Cr3+ in the hydrothermal cracking of biomass model components - Rui Xia; Kai-le Li; Peng Zhao; Xiao-xiao Yang; Jue Wang; Ke-wen An; Qing-hai Li; Hui Zhou; Yan-guo Zhang (Biomass and Bioenergy, 2026)

Advances in three-dimensional fish cell models for aquatic toxicology - Ping-Ping Zhang; Chong-Rui Yao; Wen-Jun Shi; Ting Xu; Guang-Guo Ying (Aquatic Toxicology, 2026)

Hidden potential of rare root endophytes in native plants for phytoremediation in antimony mine tailings - Hanbing Gao; Zhaohui Guo; Shikai Li; Chi Zhang; Min Shen; Xiao He; Rui Xu (Plant and Soil, 2026)

A process-level methodology for accounting carbon emissions in the entire steel production process: a case study of an iron and steel enterprise in China - Fenghui Guo; Tao Xie; Qianxuan Zhang; Rui Li; Jiajia Gao; Yali Tong; Guoliang Li; Tao Yue (Clean Technologies and Environmental Policy, 2026)

Pseudomonas eutrophicaquae sp. nov., a novel xenobiotic-degrading non-motile bacterium, containing Q-8 ubiquinone, isolated from an aquatic ecosystem in Jimo District, China - Kaiyue Wang; Jinhua Hu; Ke Ma; Haoran Liu; Doudou Kang; Mengyang Li; Jianjun Song; Bai Guo; Shuzhen Wei; Aijv Liu; Rui Zhang; Fengtang Yang; et al. (Antonie van Leeuwenhoek, 2026)

Influences of topography changes on the evolution of salinity intrusion in the North Branch of the Yangtze River Estuary over the past 70 years - Rui Ma; Zhilin Zhang; Yidi Yang; Zhigang Guo; Jianrong Zhu; Yihe Wang (Frontiers in Marine Science, 2026)
Estuarine topography influences hydrodynamics and salinity intrusion. The most significant feature of salinity intrusion in the Yangtze River Estuary is the salt-spilling-over (SSO) into the South Branch from the North Branch (NB), which affects the utilization of freshwater resources in the South Branch where three reservoirs were built. The topography in different decades from the 1950s to the 2020s was collected, and a numerical model was adopted to simulate the topography changes on salinity intrusion and SSO. From the 1950s to the 2020s, the topography of the Yangtze River Estuary changed greatly, especially in the NB. The channel area of the NB decreased by 55.56%, and its channel volume decreased by 57.57%. The numerical simulation results showed that the evolution of salinity intrusion in the NB and SSO experienced weakening–enhancing–weakening processes. The NB was covered by high-salinity water and experienced the SSO in the 1950s. The SSO distinctly weakened in the 1970s and 1980s, greatly enhanced in the 1990s, reached its most severe level in the 2000s, and significantly weakened in the 2010s and 2020s. From the 1950s to the 2020s, the tidal prism of the NB constantly decreased, with a reduction of 62.32% during spring–neap tide. The variations in the net water flux, net salt flux, and water diversion ratio in the upper section of the NB were consistent with the evolution processes of SSO. The evolution mechanisms of the salinity intrusion and SSO were elucidated in view of changes in the estuarine topography and dynamic factors.

Fabrication of Rare Earth-Doped Fe3O4/HAP Nanoparticles with Fluorescence and their Application in Food and Beverage Testing - Yulin Wang; Rui Wu; Yankun Zhang; Guanghui Tian; Jiawei Guo; Yapeng Li (Journal of Fluorescence, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

A broad-spectrum vibriophage with potential for phage therapy against Vibrio alginolyticus in shrimp aquaculture - Keming Shi; Huiyu Ding; Wanxuan Zhong; Wenqing Li; Min Hsiao; Bu Xu; Haipeng Guo; Jing Zhao; Jie Xu; Demin Zhang; Yunlan Yang; Rui Zhang (Aquaculture, 2026)

Effect of environmental factors on the control of milky disease in Chinese mitten crab (Eriocheir sinensis) - Rui Zhang; Zhigang Zhao; Kun Guo; Xu Zhao; Xiangyi Deng; Shihui Wang; Liang Luo (Aquaculture, 2026)

Non-degenerate and degenerate soliton solutions to the semi-discrete vector nonlinear Schrödinger system - Yang-Yang Du; Yan-Nan Zhao; Hui-Qin Hao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2026)

Spatial and seasonal variation in bioturbation potential of Macrobenthic communities in Bohai Bay - Yifeng Shi; Wenzhe Xu; Rui Gu; Wenxin Zhou; Guicheng Zhang; Yu Guo; Yiyan Guo; Jun Sun (Progress in Oceanography, 2026)

Numerical study of three-dimensional pull-out capacity and structural optimization for dynamically installed anchors - Haojie Zhang; Lizhong Wang; Shengjie Rui; Hongyu Wang; Zhen Guo (Ocean Engineering, 2026)

Cadmium immobilization and selenium mobilization by Citrobacter freundii in soil-rice system: a trade-off between remediation efficacy and soil microbial community integrity - Fuyu GUO; Tianao YU; Rui ZHANG; Tingting CHU; Meng ZHU; Shuting ZAN; Fengxiang X. HAN; Ruyi YANG (Pedosphere, 2026)

High-performance composite adsorbent for the identification and enrichment of fenthion and its main metabolites - Lingjun Geng; Pengwei Zhang; Qingxia Han; Haifang Wang; Jingcheng Huang; Rui Xu; Jicheng Zhao; Yemin Guo; Xia Sun; Fangling Du (Journal of Hazardous Materials, 2026)

Multi-load Undersea single-wire inductive power transfer system for sustainable ocean observation - Shui Pang; Jiayi Xu; Yehao Liu; Rui Guo; Chenguang Zhang; Jianyu Lu; Xingfei Li; Hongyu Li (Journal of Cleaner Production, 2026)

UV-aged nanoplastics induced stronger biotoxicity to earthworms: Differential effects and the underlying mechanisms of pristine and aged polystyrene nanoplastics - Yue Teng; Rui Xu; Jingyan Guo; Longteng Zhi; Ying Zhang; Hongyan Yu (Environmental Pollution, 2026)

Ultrafast synthesis of Cu/Cu2O/Cu2S@coal-based carbon heterostructure with multiple redox pairs for enhancing specific capacitance in asymmetric supercapacitors - Hongxia Gao; Xueyan Wu; Yan Lv; Rui Xue; Fanze Meng; Peiqi Jing; Jixi Guo; Xiaogang Zhang (Chemical Engineering Journal, 2026)

A Janus-interface origami fog collector with spike arrays for efficient droplet transport - Ji QI; Congji ZHANG; Rui SONG; Muneerah Alomar; Tianze ZHANG; Yuxiang CHEN; Jiachang CUI; Shangzhen XIE; Zhiguang GUO (Chemical Engineering Journal, 2026)

Engineering zincophilic-hydrophobic anode-anolyte interface via electrolyte additive for sustainable zinc‑manganese flow batteries - Lei Guo; Rui Sun; Yan Tan; Qing Zhang; Viswanathan S. Saji; Senlin Leng; Haiming Lv (Chemical Engineering Journal, 2026)

Influence of coal dust on flame propagation characteristics and spectral features of gas explosion - Qiuhong Wang; Zezhou Song; Jun Deng; Zhenmin Luo; Wei Gao; Yating Zhang; Guoqiang Dong; Rui Guo; Di Wu (Chemical Engineering Journal, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Depth-dependent effects of vegetation restoration on soil quality in ion-adsorbed rare earth leach residues: Insights from soil functions - Heng Zhang; Xianzhen Luo; Rui Zhang; Li Zhou; Rufeng Guo; Yuanwen Kuang; Dazhi Wen; Biao Qiu; Lingling Zhang (CATENA, 2026)

Field measurements of the typhoon near-surface wind characteristics under different precipitation intensities - Yun Guo; Shengming Tang; Huan Li; Jie Tang; Shuai Zhang; Rui Peng; Xuhui He (Atmospheric Research, 2026)

Keystone microbes mediate root traits and phosphorus uptake to enhance maize crop productivity in intercropping systems - Yi-Wen Zhao; Ran An; Jiu-Dong Zhang; Rui-Peng Yu; Yi Xing; Xing-Guo Bao; Jing-Jing Peng; Long Li (Plant and Soil, 2026)

The association of co-exposure to polycyclic aromatic hydrocarbons and phthalates with surrogate indicators of insulin resistance: a panel study - Sha You; Lin Liu; Min Xiang; Lei Zhao; Wenting Guo; Xiaomin Zhang; Rui Zhu; Liangle Yang (Environmental Geochemistry and Health, 2026)

A dual-mode colorimetric and electrochemical strategy for sensitive detection of PRRSV using imidazole-copper nanozymes - Jing Li; Xiang Lai; Chong Zhang; Yu-Fan Huang; Guo-Bao Ning; Si-Ying Ma; Ao-Xiang Chen; Ming-Rui Li; Guo-Hao Li; Qin Zhao; Can-Peng Li; Hui Zhao (Analytica Chimica Acta, 2026)

Variations in C:N:P Stoichiometry, Non-Structural Carbohydrate, Chlorophyll, and Hormones of Abelmoschus manihot Flower at Different Phenological Growth Stages - Wen-zhang Qian; Hong-rui Wang; Shao-jun Fan; Yi-xiao Xiao; Yun-yi Hu; Guo-xing Cao; Shun Gao (Journal of Plant Growth Regulation, 2025)

Improved PSO-VMD seismic signal denoising method combined with modified wavelet transform - Hui Sun; Hong-yong Ren; Rui Chen; Xing-guo Huang; Wei Zhang; Yan-song Li; Jian Zhang; Yu-bo Yue (Applied Geophysics, 2025)

Targeting YBX1: A novel therapeutic strategy for gastric cancer through regulation of cellular senescence and mTOR signaling - Wenze Zhang; Yanjuan Jia; Anqi Wang; Rui Guo; Zhuomin Fu; Wanxia Wang (Tissue and Cell, 2025)

Corylifol A ameliorates pancreatic cancer-associated cachexia by targeting TAOK3 in pancreatic cancer cells and targeting TAOK1 in skeletal muscle cells - Ke Yu; Rui-Qin Zhang; Nan Li; Qiong-Sen Wang; Jia Gu; Sai-Yue He; Ying-Qian Wang; Guo-Guo Wang; Xiong-Wen Zhang; Xiao-Dong Guo; Xuan Liu (Toxicology and Applied Pharmacology, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Strategic sampling for training a semantic segmentation model in operational mapping: Case studies on cropland parcel extraction - Rui Lu; Ronghua Liao; Ran Meng; Yingchu Hu; Yi Zhao; Yan Guo; Yingfan Zhang; Zhou Shi; Su Ye (Remote Sensing of Environment, 2025)

A new risk for the recovered Tibetan antelope (Pantholops hodgsonii): Co-exposure of microplastics with organophosphates in their habitats - Rui Guo; Caian He; Jian Sun; Shaohua Li; Chuntao Zhao; Zhiyong Ling; Liang Chen; Wenrui Zhang; Jingmeng Li; Bing Wang; Jufang Hu; Dongmei Yu; et al. (Journal of Hazardous Materials, 2025)

Tailored SO2 capture in multivariate UiO-66(Zr) MOFs: Experimental insights and theoretical mechanisms - Zai-Dong Shao; Peng Wu; Fang Liu; Qi-Jun Zhang; Chao-Yang Guo; Rui-Sang Liu; Jiang Lu; Xiao-Meng Ren; Yu-Ming Zheng (Journal of Environmental Chemical Engineering, 2025)

Grazing disturbance reduces soil organic carbon sequestration and stability in desert steppe - Naijing Lu; Tianqi Zhao; Jianying Guo; Mengli Zhao; Guodong Han; Zhongwu Wang; Jiangfeng He; Rui Zhao; Yong Wang; Jian Guan; Bin Zhang; Guang Yang (Journal of Environmental Management, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Single-atom Pt-engineered TiO₂ photoanode enabling low-charge voltage and high-efficiency neutral Zn-air batteries via photoelectrochemical enhancement - Wenliang Wang; JiangYuan Qiu; Tao Yu; Shuming Zhang; Xingwang Niu; Rui Guo; Jinsheng Li; Xuanwen Liu (Journal of Environmental Chemical Engineering, 2025)

Development of a 3D-printed food based on arrowhead (Sagittaria sagittifolia L.) byproducts: Effects of hydrocolloids on printability and post-processing performance - Qing Guo; Min Zhang; Chung Lim Law; Antonio Derossi; Luming Rui (Food Research International, 2025)

Esculetin improves lipid metabolism disorders induced by a high-fat diet by regulating the P13K-AKT signaling pathway and taurocholic acid metabolism - Liyang Guo; Yongjie Zhang; Kun Wang; Shun Wang; Yecheng Yao; Weiqi Liu; Fuhua Gu; Yifan Li; Rui Li; Jichang Li; Chunli Chen (Food Research International, 2025)

Deciphering the core microbiomes and associated genes and metabolites during the Shanxi aged vinegar making process - Rui Ma; Mingxia Cheng; Qiong Zhou; Xiaojie Nan; Min Zhu; Shang Guo; Zhibin Zhang; Fang Gao; Jingang Gu (Food Bioscience, 2025)

Integrated untargeted metabolomics and physiological analysis reveal the response mechanisms of Procambarus clarkii larvae to carbonate alkalinity exposure - Kun Guo; Zhigang Zhao; Rui Zhang; Liang Luo; Shihui Wang; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Nano-thiophene-graphdiyne engineered buried interface toward homogeneous crystallization of perovskite films - Yutongyang Fu; Le Liu; Zhibin Yu; Rui Han; Yilin Chang; Yunxin Zhang; Wenfei Guo; Bin Huang; Jiajia Du; Wenfeng Yang; Tonggang Jiu (Chemical Engineering Journal, 2025)

Dual pH/glutathione-responsive polyphenol-based self-assembled nanoparticles loaded with lambda-cyhalothrin show enhanced UV stability and non-target organism safety - Lei Wang; Zheng Zhang; Yu Fang; Rui Zhao; Shouhe Pan; Meng Yu; Yinjie Ma; Yinmin Wang; Xiquan Ding; Xinyu Guo; Fengyu Li; Pengkun Yan; et al. (Chemical Engineering Journal, 2025)

Direct synthesis of highly efficient NIR-I emitting core-only InP quantum dots via multi-ligand synergy - Rui Jiang; Jie Zhao; Yifei Qiao; Bo Tan; Jialin Yin; Zhenyu Dai; Shiliang Mei; Wanlu Zhang; Ruiqian Guo (Chemical Engineering Journal, 2025)

Research Progress on the Coupling of Carbon Sequestration by Soil Biochar and the Treatment of Organically Polluted Soil - Yuliang Guo; Zihaohan Sang; Rui Zhang; Lulin Tan (Water, Air, & Soil Pollution, 2025)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

TROAP aggravates chemoresistance of colorectal cancer cells via lipogenesis by PI3K/Akt pathway and histone acetylation - Ling-Ling Wang; Rui Zhang; Ning Li; Zheng-Guo Cui; Hua-Chuan Zheng (Functional & Integrative Genomics, 2025)

Detection of Caco-2 cell absorption rate of Bombyx mori peptide chelated zinc and validation of anti-inflammatory activity based on network pharmacology - Mengqing Guo; Ning Dong; Chunxue Liu; Rui Ma; Shen Li; Yao Sun; Fengqing Zhang (BioMetals, 2025)

Implementation of inverse transform sampling method for photon transport in Monte Carlo code and nuclear data library preparation by NECP-Atlas - Rui Zhang; Tiejun Zu; Jiandi Guo; Qingming He; Hongchun Wu; Liangzhi Cao (Annals of Nuclear Energy, 2025)

Synergistic electromagnetic and chemical enhancements in Al/C3N4/Ag@C for Raman-based chlortetracycline sensing - Jingyi Sun; Lujie Li; Tingting Zhang; Na Jiang; Zishan Guo; Congying Li; Weihua Li; Xianhuai Huang; Yan Li; Rui Lu (Analytica Chimica Acta, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

P T symmetry preserving, symmetry breaking and propagation behaviors in degenerate and non-degenerate solitons beyond the nonlocal Manakov system - Yang-Yang Du; Yan-Nan Zhao; Rui Guo; Jian-Wen Zhang (Wave Motion, 2025)

Sediment amplifies organic matter cycling and nutrients feedback in eutrophic lake zones - Junfeng Xing; Yuping Zhou; Ding He; Fen Guo; Penghui Li; Yuan Zhang; Rui Lv; Runze Xue; Changqing Liu; Yihua Xiao (Water Research, 2025)

Formaldehyde emissions in tanker truck cabins: Observation, deep learning prediction and health risk assessment - Rui Zhang; Dongdong Guo; Ruixiu Jiang; Honglin Cao; Yunjia Wu; Lirong Kou; Meng Wang; Linwei Xi; Yang Liu; Haimei Wang; Jianyin Xiong (Science of The Total Environment, 2025)

Eugenol-based meroterpenoids with neural differentiation activity from Eugenia caryophyllata - Cong Yan; Sheng-Rui Yan; Yutong Zhu; Mengjiao Cai; Rui-Li Huang; Xinyu Wang; Shiqing Zhang; Lei Shi; Li-Jun Hu; Wen-Cai Ye; Xiao-Jun Huang; Ying Wang; et al. (Phytochemistry, 2025)

Enhanced effects of species richness on cadmium phytoextraction across eastern China: A meta-analysis - Rufeng Guo; Xianzhen Luo; Li Zhou; Rui Zhang; Lingling Zhang; Yuanwen Kuang; Biao Qiu; Dazhi Wen (Environmental Research, 2025)

Study on the distribution characteristics and toxic risks of trace elements in the eggs of green turtles (Chelonia mydas) nesting on the Xisha Islands - Xiang Li; Li Jian; Minyu Fu; Henyi Zhang; Yuxin Zhang; Rui Guo; Jichao Wang (Environmental Research, 2025)

Genetic sensitivity moderates the effects of joint exposure to air pollution on depression risk: a genome-wide by environment interaction analysis - Yaoyao Sun; Xue Lv; Wenjian Bi; Yuyanan Zhang; Zhe Lu; Jing Guo; Zhewei Kang; Xiaoyang Feng; Yundan Liao; Guorui Zhao; Junyuan Sun; Yang Yang; et al. (Environmental Pollution, 2025)

Dual-stage reverse-dialysis-engineered cartilage-biomimetic hydrogels: Highly resilient anti-swelling double-layer architectures - Zheng-Feng Zhang; Mei-Yan Ling; Xiao-Rui Ge; Jia-Ying Chen; Bei Zhang; Xiao-Hui Yao; Peng Song; Wei-Guo Zhao; Dong-Yang Zhang; Jun Wang (Chemical Engineering Journal, 2025)

Wireless gas sensor based on monolayer Ti3C2Tx-modified GaN/CuO heterostructures for ultrafast and trace detection of NO2 gas - Haineng Bai; Cheng Feng; Rui Guo; Yiru Chen; Wenfeng Yuan; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2025)

Phytosphingosine suppresses gastric cancer through SFRP4/β-catenin axis-mediated Wnt signaling pathway inhibition - Yanchen Liu; Rui Guo; Chi Xue; Xinwei Zhang; Fanghao Xiao; Xiangxuan Zhao; Zhi Zhu; Kai Li (Chemico-Biological Interactions, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

A risk assessment method for subsea tunnel collapse based on cloud Bayesian network - Shaoxuan Guo; Junlong Yan; Rui Li; Xianghui Li; Dongzhu Zheng; Qingsong Zhang; Yankai Liu (Marine Georesources & Geotechnology, 2025)

Monsoon and deep ocean control of organic carbon burial in the southeastern Bay of Bengal - Jingrui Li; Shengfa Liu; Hui Zhang; Xiaoming Miao; Fangliang Li; Kun Guo; Hongying Song; Rijun Hu; Rui Jiang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Opening of South China Sea in the Western Pacific forcing the climate cooling and lake level rise at Eocene–Oligocene transition - Jing Guo; Fujie Jiang; Guangrong Peng; Yuqi Wu; Weibing Shen; Rui Zhang; Yu An; Dapeng Jiang; Fusheng Yu; Yaqi Li; Zhifeng Yu; Jiabing Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Diagnostic early freeze onset in the Bering Sea - Weibo Wang; Jie Su; Junpeng Zhang; Rui Ding; Chunsheng Jing; Xiaogang Guo (Journal of Marine Systems, 2025)

Metagenomic insights into the synergistic properties and mechanisms of sludge microbial communities degrading polystyrene and polypropylene - Ying Zhou; Wei-hua Gu; Jian-feng Bai; Rui-xue Wang; Cheng-long Zhang; Yao-guang Guo; Cong Lu; Shan-ping Chen (Journal of Hazardous Materials, 2025)

Sustainable enzyme immobilization: Enhanced antibiotics removal via dopamine-mediated CLEAs anchoring on porous sponge carriers - Keshuai Liu; Shuxian Zhang; Lingling Yang; Xiaoxuan Fan; Xiaofei Wang; Wangyan Zhao; Rui Mai; Xiaoli Guo; Xueqin Ma; Guoning Chen (Journal of Environmental Chemical Engineering, 2025)

Nitrogen and phosphorus addition affected soil organic carbon storage and arbuscular mycorrhizal fungi contributions - Shengchao Ma; Rui Guo; Yue Wang; Yan Yan; Qianwen Chu; Nan Cui; Yifei Zhang; Lei Zhang; Li Jiang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; et al. (Journal of Environmental Management, 2025)

The relationship between anaerobic oxidation of methane and dark carbon fixation in methane seep sediments - Yinan Deng; Rui Xie; Qingjun Guo; Shengxiong Yang; Ganglan Zhang; Hongfei Lai; Qianyong Liang; Fang Chen; Jun Cao (Global and Planetary Change, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

A lytic vibriophage as a potential biocontrol agent against vibriosis in aquaculture - Yunlan Yang; Wanxuan Zhong; Huiyu Ding; Keming Shi; Haipeng Guo; Demin Zhang; Lanlan Cai; Min Hsiao; Jie Xu; Rui Zhang (Fish & Shellfish Immunology, 2025)

Synthesis of confined palladium nanocatalysts in crystalline hemoglobin framework: An ultrastable nanoreactor for Cr(VI) detoxification - Xiao-Qian Jin; Jia-Lei Li; Jun-Bin Xiong; Rui Zhang; Chen-Yuan Li; Xue-Ting Wang; Wei-Hong Guo; Da-Chuan Yin (Environmental Research, 2025)

Effects of re-enter water on antioxidant, immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after high temperature air exposure - Xiangyi Deng; Yuhong Yang; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Sunlight-activated photochromic-photothermal nanofibrous textiles for self-monitored thermal management - Shuai Liang; An-Yang Duan; Shi-Kun Yan; Yan-Rui Zhao; Jin Zhang; Guo-Wei Xiao; Chang-Hai Xu; Ji-Xiang Hu; Guo-Ming Wang (Chemical Engineering Journal, 2025)

ROS-responsive hydrogel loaded with berberine liposome protects against intervertebral disc degeneration by inhibiting mitochondrial fission and apoptosis - Cunliang Guo; Lilong Du; Xiaoxun Du; Rui Gao; Xinyi Jiao; Zhenhua Li; Tongxing Zhang; Pingsheng Huang; Chuangnian Zhang; Zujian Feng; Weiwei Wang; Baoshan Xu (Chemical Engineering Journal, 2025)

Global response of soil phosphatase activity to land reclamation and vegetation restoration - Huaisong Wang; Mingming Wang; Jialing Xu; Yibo Tian; Jinyu Bai; Lei Zhang; Lianxuan Shi; Jixun Guo; Yingzhi Gao; Rui Guo; Tao Zhang (CATENA, 2025)

Differential responses in topsoil and subsoil: N2O, CO2, and CH4 dynamics under extreme rainfall - Mengdi Yang; Yufei Cui; Xiaomin Li; Ning Zhang; Shengli Guo; Rui Wang (CATENA, 2025)

Silkworm sand-based bio-organic fertilizers reshape rhizosphere microbiomes and modulate soil chemistry for sustainable management of Myrica rubra decline - Leidong Hong; Chunlai Hong; Weijing Zhu; Fengxiang Zhu; Weiping Wang; Tao Zhang; Rui Guo; Xingjiang Qi; Xiuqin Zou; Yanlai Yao (Plant and Soil, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

Hawthorn Polysaccharide Enhances Growth, Immunity, and Intestinal Health in Crucian Carp (Carassius auratus) Challenged with Aeromonas hydrophila - Liang Luo; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Cheng Zhao; Baoquan He; Wei Wang; Wenhua Wu (Fishes, 2025)
Bacterial disease infections pose a major challenge to the healthy growth of crucian carp. Hawthorn polysaccharide (HP) is a natural active ingredient in hawthorn and has a wide range of pharmacological effects. However, the mechanism of HP against Aeromonas hydrophila infection in crucian carp cultures is unknown. In this study, it was found that 0.4% HP could significantly reduce the mortality of crucian carp, significantly increase the activities of T-AOC, SOD, CAT, and GSH-PX of crucian carp infected with A. hydrophila (p

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

New point mutations in osmosensing two-component histidine kinase gene associated with iprodione resistance in Monilinia fructicola field isolates from China - Qian Long; Yiyi Guo; Miaomiao Yi; Changsheng Lu; Rui Zhong; Hao Zhang; Usama Amin; Dufang Ke; Zongwen Wang; Fengping Chen (Pesticide Biochemistry and Physiology, 2025)

Mechanistic insights into microbial-mediated transformation of Fe2+, Mn2+, and NH₄+ under co-existing conditions in groundwater: Evidence from two-dimensional tank experiment - Li Meng; Rui Zuo; Jingrui Wang; Xueru Guo; Jiawei Liu; Ziyi Wu; Jinsheng Wang; Yuanzheng Zhai; Zhigang Zhang; Xi Yang; Guanlan Wu (Journal of Water Process Engineering, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Exploiting the gut microbiota of aquatic animals as indicators of microplastic pollution using interpretable machine learning models - Zhaoji Shi; Rui Guo; Fucheng Yao; Ziqiang Liu; Jiaen Zhang (Journal of Hazardous Materials, 2025)

Effect of non-Saccharomyces yeast combinations and lactic acid bacteria inoculation timing on fermentation performance and aroma quality of kiwifruit wine - Wangsheng Sun; Wanju Yan; Rou Cai; Zhendong Zhang; Pengfei Bi; Jia Han; Sinuo Feng; Shiqi Li; Rui Cai; Zhouli Wang; Fangyu Long; Jing Guo (Food Bioscience, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Barn swallow (Hirundo rustica) transfers current-use pesticides from agricultural fields to houses - Jiahe Zeng; Ziqing Luo; Kaiying Guo; Li Tian; Rui Zhang; Xiaobo Zheng (Environmental Pollution, 2025)

Self-powered Ag2Se/SiO2/Si heterojunctions for ultrafast broadband high-sensitivity photodetection - Weipeng Shi; Rui Guo; Gailing Tian; Wenjing Zhang; Yi Chen; Wenyan Wang; Yonghua Wang; Danfeng Cui; Jinglong Wen; Dan Liu; Chenyang Xue (Chemical Engineering Journal, 2025)

BaTiO3 dressed in carbon multifunctional layer achieving high areal capacity zinc metal batteries - Rui Wang; Jing Xu; Shijun Luo; Yan Guo; Baohe Yuan; Lei Xu; Junming Li; Yongqi Zhang; Yusheng Wang; Wenpeng Yang; Jinbing Cheng; Yongsong Luo (Chemical Engineering Journal, 2025)

Enhancing flame retardancy and mechanical properties of epoxy/carbon fiber composites via a metal-phosphorus synergistic interface structure - Dou Hu; Guo-rui Zhang; Xiao-dong Qi; Jing-hui Yang; De-xiang Sun; Yong Wang (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Synergistic treatment of respiratory syncytial virus induced pneumonia by multifunctional Baicalin-Resveratrol self-assembled nanomedicine - Chenqi Chang; Yu Zheng; Chang Lu; Ying Ma; Liang Wu; Yunyu Zhang; Lili Lin; Liang Guo; XiuZhen Chen; Linwei Chen; Jianming Cheng; Rui Chen (Chemical Engineering Journal, 2025)

Knockdown of Atg1 Impairs Brain Regeneration and Downregulates ECM-Related Genes in the Planarian Dugesia japonica - Kexue Ma; Fangying Guo; Rui Li; Gege Song; Hecai Zhang; Qiong Lu; Keshi Ma; Shaoqing Gong (Molecular Neurobiology, 2025)

Phylogenetic and toxicogenomic profiling of CYPomes to elucidate convergent and divergent insecticide resistance profiles in three rice planthopper species - Kai Lin; Hongxin Wu; Zhongsheng Li; Zichun Zhong; Liuyan He; Yujing Guo; Jie Zhang; Xiaoxia Xu; Wenqing Zhang; Fengliang Jin; Rui Pang (Journal of Pest Science, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Vortex-Induced Vibration of Deep-Sea Mining Riser Under Different Currents and Tension Conditions Using Wake Oscillator Model - Liwen Deng; Haining Lu; Jianmin Yang; Rui Guo; Bei Zhang; Pengfei Sun (Journal of Marine Science and Engineering, 2025)
The vortex-induced vibration (VIV) dynamics of commercial-scale deep-sea mining risers with complex component arrangements (pumps, buffer stations, buoyancy modules) remain insufficiently explored, especially for 6000 m systems with nonlinear tension. This study investigates VIV control strategy by adjusting tension for a nonlinear riser system using the Iwan-Blevins wake oscillator model integrated with Morison equation-based analysis. An analytical model incorporating four typical current profiles was established to quantify the dynamic response under different flow velocities, internal flow density, and structural parameters. Increased buffer station mass effectively suppressed drift distance (over 35% reduction under specific conditions) by regulating axial tension. Dynamic comparisons demonstrated distinct VIV energy distribution patterns under different current conditions. Spectral analysis revealed that the vibration follows Strouhal vortex shedding lock-in principles. Spatial modal differentiation was observed due to nonlinear variations in velocity profiles, pipe diameters, and axial tension, accompanied by multi-frequency resonance, coexistence of standing and traveling waves, and broadband resonance with amplitude surges under critical velocities (1.75 m/s in Current-B). This study proposes to control the VIV amplitude by adjusting internal flow density and buffer mass, which is proved effective for reducing vibrations in upper (0–2000 m) risers. It validates vibration amplitude and frequency control through current velocity, buffer mass and slurry density regulation in a nonlinear riser system.

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Predicting estrogen receptor agonists from plastic additives across various aquatic-related species using machine learning and AlphaFold2 - Wen-Jun Shi; Zhou Cao; Xiao-Bing Long; Chong-Rui Yao; Jin-Ge Zhang; Chang-Er Chen; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

The feasibility and prospects of coal mine water as a cooling medium for data centers - Zaining Li; Chunhui Zhang; Peidong Su; Guifeng Zhao; ZePeng Wang; YiYun Li; YanXin Li; Mengna Wang; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

Deep Learning in Gravity Research: A Review - Qingkui Meng; Lianghui Guo; Shuai Zhang; Hanyu Lou; Rui Li (Journal of Earth Science, 2025)

Exploring Core Genes Involved in Ischemic Stroke and the Therapeutic Potential of Hyperbaric Oxygen: Insights from Transcriptomic Analysis - Yingcun Bao; Xudong Guo; Jinhai Wang; Jihe Kang; Rui Ma; Xiaorong Cheng; Yumei Ma; Yanxia Niu; Wei Zhang; Xiaoling Li (NeuroMolecular Medicine, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

An automatic landmarking algorithm for leaf morphology based on conformal mapping - Peige Zhong; Xiaojun Liu; Yulu Ye; Rui Zhang; Hu Zhou; Yan Guo; Baoguo Li; Jinyu Zhu; Yuntao Ma (Computers and Electronics in Agriculture, 2025)

An oral recombinant human type 5 adenovirus vector vaccine encoding the S protein of Type I feline coronavirus effectively protection against FCoV challenge in cats - Gu-nan Deng; Chang-zhan Xie; Ke-lei Zhou; Chun-sai He; Yuan-Zhen Ma; A.-jia Ake; Rui Guo; Kai Li; Chen Peng; Bin Zhang (Veterinary Microbiology, 2025)

Traffic-based resilience assessment on urban road tunnel affected by fire accident - Rui Zhu; Dong-Mei Zhang; Zhong-Kai Huang; Xiao-yang Guo; Bin-lin Gan; Wen-ding Zhou (Tunnelling and Underground Space Technology, 2025)

Structurally diverse abietane diterpenoids from the whole plants of Salvia przewalskii Maxim. With anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Tong Zhang; Shuang Xu; Xin Qiao; Guo-Shun Zhang; Qiong Zhang (Phytochemistry, 2025)

Bipartite trophic levels cannot resist the interference of microplastics: A case study of submerged macrophytes and snail - Jun Chen; Zhiqiang Zhang; Nan Shen; Hongwei Yu; Guo Yu; Jing Qi; Rui Liu; Chengzhi Hu; Jiuhui Qu (Journal of Hazardous Materials, 2025)

Addressing challenges and advancing solutions: Enhancing semi-coking wastewater treatment for a sustainable prospect - Tingting Cui; Chunhui Zhang; Bingxu Quan; Liwei Wang; Zhao Zhang; Peidong Su; Yuanhui Tang; Guifeng Zhao; Ping Qiao; Junqiang Guo; Rui Zhang (Journal of Environmental Management, 2025)

Effects of electric field-assisted freeze-thaw cycle on arrowhead (Sagittaria sagittifolia L.) quality and the structural and physicochemical properties of starch - Qing Guo; Min Zhang; Arun S. Mujumdar; Luming Rui (Innovative Food Science & Emerging Technologies, 2025)

Mechanistic applications of low-temperature plasma in starch-based biopolymer film: A review - Yanli Guo; Mengzhuo Liu; Rui Chuang; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

Time-Delayed Rockbursts Induced by Dynamic Disturbances: 793 Cases in Deep Tunnels - Ben-Guo He; Heng-Yuan Zhang; Xia-Ting Feng; Xiang-Rui Meng (Rock Mechanics and Rock Engineering, 2025)

Variations in lunar regolith mineralogy along the Chang’e-4, Yutu-2 traverse: Combined effects of ejecta sedimentation and subsequent modification - Zhenxing Zhao; Yazhou Yang; Dijun Guo; Yang Liu; Feng Zhang; Xing Wu; Rui Xu; Zhiping He; Yongliao Zou (Science China Earth Sciences, 2025)

Synergistic effect of canine FGF-21 combined with insulin in the treatment of canine diabetes - Wenying Sun; Yaoqun Wang; Ziran Liu; Qing Wu; Xiaochen Guo; Zhitong Li; Xinyu Li; Chunxu Shi; Rui Gao; Lin Bai; Jingming Wang; Yuhan Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Molecular characterization of a novel non-segmented double stranded RNA mycovirus infecting the phytopathogenic fungus Botryosphaeria dothidea - Shunpei Xie; Yanan Zhang; Guoqing Xing; Qinzhou Ma; Yashuang Guo; Rui Zang; Chao Xu; Haiyan Wu; Haiqiang Li; Meng Zhang (Archives of Virology, 2025)

Field test on the inclined installation performance of dynamically installed anchors - Haojie Zhang; Lizhong Wang; Hongyu Wang; Shengjie Rui; Zhen Guo (Ocean Engineering, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

In vitro experiments and computer simulation techniques on the identification, screening and inhibition mechanism of xanthine oxidase (XO) inhibitory peptides from Esox lucius bone - Rui Geng; Yabo Wei; Yi Wang; Xin Guo; Xiaorong Deng; Lianfu Zhang; Jian Zhang (Food Bioscience, 2025)

Construction of linear causal-regulated and autocatalysis-driven DNA circuits for highly sensitive and specific detection of Salmonella Typhimurium - Xinru Ren; Weiqing Sun; Bowen Li; Yijing Xiao; Xudong Yue; Meili Yang; Qing-ao Pang; Rui Zhu; Zhiqiang Guo; Haiping Zhang; Yu Wang; Su Liu; et al. (Food Control, 2025)

RouteView 2.0: A real-time operational planning system for vessels on the Arctic Northeast Passage - Adan Wu; Tao Che; Jinlei Chen; Xiaowen Zhu; Qingchao Xu; Tingfeng Dou; Rui Zhang; Shengpeng Chen; Jiping Wang; Yongfan Guo (Environmental Modelling & Software, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Single stem cell encapsulation by MnO2 doped hydrogel for robust bone regeneration - Yu Tian; Pengxia Zhang; Zhen Ma; Mengya Li; Yali Fan; Rui Guo; YanFeng Li; Yingying Zhang (Chemical Engineering Journal, 2025)

Solid-state fermentation of distillers grains with Aspergillus pachycristatus for echinocandin B biosynthesis - Jiaxin Tang; Weibing Zhang; Jing Xu; Luyan Sun; Yaqi Dang; Haoyang Li; Liyan Yu; Jing Su; Ting Xue; Rui Guo; Jun Xie; Lei Wang (Bioresource Technology, 2025)

Improving intestinal barrier function and intestinal microbiome of weaned piglets fed a low-protein diet through tryptophan and N-Acetylglutamic acid supplementation - Shichao Liu; Zhiyuan Tai; Muzhi Li; Rui Zhang; Guobin Shao; Jiatai Guo; Weixing Lu (Tropical Animal Health and Production, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

MVPCR: Multiplex Visual Detection Strategy Based on Ultrafast PCR for Point-of-Care Pathogens Detection Within 10 Min - Ziqin Zhang; Cui Wu; Linlin Bai; Kaiming Guo; Ting Wang; Dianwei Liu; Mingrui Zhu; Feng Qian; Fang Zhang; Rui Wang (Phenomics, 2025)

Long non-coding RNA HOXA11-AS inhibits apoptosis, induces proliferation, and promotes autophagy via the miR-214-3p/ATG12 axis in acute T lymphoblastic leukemia - Rui Zhang; YuanYuan Zhang; XiaoFei Li; ShaoHua Wang; Jiao Li; ShuoChun Shao; Bin Liu; WeiWei Guo; Min Shi (Journal of Molecular Histology, 2025)

Mesoscopic interpretation of fines clogging-induced permeability changes in completely decomposed granite - Rui Chen; Zhi-yuan Luo; Ai-guo Li; Hao Wang; Lei-lei Liu; Liang-liang Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Identification of antifungal metabolites from a soil-derived Streptomyces strain active against Fusarium graminearum using genome mining - Xingyu Liu; Lubna Rahman; Yang Zhang; Rui Guo; Min Zhang; Wei Zhou (Biotechnology Letters, 2025)

Effects of dietary Lycium barbarum polysaccharide on the growth, antioxidant, immunity response, and intestinal microbiota in Bulatmai barbel (Luciobarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Wei Xu; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2025)

Multi-layer landscape design of urban spontaneous plant community: A case study in Zhengzhou, China - Wangxin Su; Zeqi Zhai; Wenhui Zhang; Rui Li; Jiayi Li; Yang Liu; Wenqian Jiang; Hong Wei; Nan Guo; Yonghua Li (Urban Forestry & Urban Greening, 2025)

The Trp-574-Leu mutations together with enhanced metabolism contribute to cross-resistance to ALS inhibiting herbicides in Fimbristylis littoralis - Yueyue Shi; Zhiwen Wu; Rui Cheng; Lilei Zhang; Xiaoxiao Guo; Xuefeng Li; Yaling Bi (Pesticide Biochemistry and Physiology, 2025)

Extracellular polymeric substances enhanced photosynthesis over respiration in Microcystis aeruginosa - Kaikai Deng; Rui Yang; Shirong Zhang; Fang Fang; Yuanchen Huo; Peng Yan; Youpeng Chen; Jinsong Guo (Harmful Algae, 2025)

A novel soil reaction model for continuous impact pile driving - Shihong Zhang; Lizhong Wang; Mengtao Xu; Shengjie Rui; Zhen Guo (Computers and Geotechnics, 2025)

Defect-repair in carbon for fast and stable potassium and sodium storage - Rui Ma; Yaxin Chen; Binyuan Zhang; Lili Ai; Changyu Leng; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2025)

Self-oxygenated biomimetic nano-heterojunction combats bacterial biofilm infections via near-infrared triggered ROS storms - Zhengcai Guo; Rui Zhang; Yi Li; Zhiling Chen; Tao Wang; Mingyu Wang; Xiaohong Wang; Yang Cao; Jinchun Tu; Delun Chen; Yang Wang; Qiang Wu (Chemical Engineering Journal, 2025)

Biodiesel synthesis from Semen Abutili (Abutilon theophrasti Medic.) seed oil utilizing a novel immobilized complex lipase: Simultaneously ethanolysis and esterification - Rui Zhang; Jingjing Guo; Yaoyao Zhang; Shangde Sun (Biomass and Bioenergy, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Mechanisms of breast cancer metastasis: the role of extracellular matrix - Rui Chen; Ranqi Zhang; Famin Ke; Xiurong Guo; Fancai Zeng; Qiuyu Liu (Molecular and Cellular Biochemistry, 2025)

Metabolomics provide novel insights into the settlement and metamorphosis of the scyphozoan jellyfish Aurelia coerulea - Shuai Liu; Xiaoyu Tang; Xuerui Liu; Rui Zhang; Xiangrui Guo; Zhen Yu; Ye Zhao; Jiehui Yin; Hao Sun; Yanying Zhang (Journal of Oceanology and Limnology, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

ANAC050 confers aluminium resistance by cooperating with secretion of organic acids and accumulation of cell wall hemicelluloses in plants - Ye TAO; Su LI; Yusong LIU; Rui GUO; Changzhao CHEN; Jiu HUANG; Qiang ZHANG; Renfang SHEN; Xiaofang ZHU (Pedosphere, 2025)

Efficient degradation of norfloxacin by ZnCo2O4/halloysite composite activating peroxymonosulfate: Performance and mechanism insights - Long Zhang; Rui Li; Bohao Liu; Yubo Wang; Qingbin Guo; Junying Song; Xiongbo Dong; Li Wang; Xiaolong Hu; Dengzheng Gao (Journal of Water Process Engineering, 2025)

The integrating optional energy band alignment and oxygen vacancies over α/β-Fe2O3-3R homogenic boundary boosted self-fenton degradation of antibiotics - Jing Yan; Shi-Xian Guan; Ying Li; Jing Guo; Na Zhang; Jian-Yong Zhang; Chun-Wei Guo; Jie Ren; Qin-Fei Ke; Yong-Zheng Fang; Rui Zhang (Journal of Environmental Chemical Engineering, 2025)

Influence of geogrid reinforcement on the cracking characteristics of expansive soils: A laboratory study - Rui Zhang; Yu Zhou; Yipeng Guo; JianLong Zheng; Yufan Deng; Tian Lan (Geotextiles and Geomembranes, 2025)

Synthesis and performance evaluation of hydrate dissociation inhibitors suitable for cementing hydrate formations - Yuhuan Bu; Zilong Lu; Chang Lu; Huajie Liu; Shenglai Guo; Hexing Liu; Rui Ma; Zhen Zhang; Mengran Xu (Fuel, 2025)

Determination of five alternaria toxins in peppermint by dispersive solid-phase extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry based on MOF-808-TFA - Minhai Liu; Yan Zhang; Rui Cheng; Ting Tan; Lan Guo; Fan Liu; Yiqun Wan (Food Chemistry, 2025)

The research on the synergistic improvement of water retention capacity and eating quality of marinated pork meat by the combination of basic arginine and acidic aspartic acid - Kuo Xu; Ao-Jing Lv; Rui-Ling Dong; Yu-Cong Li; Li-Ting Zeng; Yang Wang; He-Shuai Li; Jun Qi; Hu-Hu Wang; Chun-Hui Zhang; Guo-Yuan Xiong; Qing-Yong Zhang (Food Chemistry, 2025)

Variability in maternal transfer efficiency of trace elements in green turtles (Chelonia mydas) - Li Jian; Xiang Li; Xiaobo Zheng; Henyi Zhang; Minyu Fu; Rui Guo; Jichao Wang (Environmental Pollution, 2025)

Highly efficient separation of anthracene and carbazole in crude anthracene by composite extractants with low viscosity - Yuanyuan Wang; Wenhai Zhang; Danting Wang; Rui Ma; Lili Ai; Mengjiao Xu; Dianzeng Jia; Nannan Guo; Luxiang Wang; Hong Meng (Chemical Engineering Journal, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Omics research in atherosclerosis - Kai-Jiang Tian; Yu Yang; Guo-Shuai Chen; Nian-hua Deng; Zhen Tian; Rui Bai; Fan Zhang; Zhi-Sheng Jiang (Molecular and Cellular Biochemistry, 2025)

Development of potential intron polymorphic (PIP) markers in melon (Cucumis melo L.) - Rui Sun; Yan-Ge Li; Ding-Ding Zuo; Meng-Ling Zheng; Jing Zhang; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Genetic Resources and Crop Evolution, 2025)

Association of Urinary Phthalate Metabolites with Lipid Profiles and the Mediating Role of Serum Globulin: A Repeated-Measures Study - Kun Huang; Linlin Liu; Lei Zhao; Miao Liu; Chongjian Wang; Wenting Guo; Huihua Yang; Rui Zhu; Xiaomin Zhang (Exposure and Health, 2025)

Intelligent identification and semantic segmentation of deep rock fracture based on deep ensemble learning and transfer learning - Rui Li; Qingsong Zhang; Shaoxuan Guo; Guangxuan Zhu; Hongzhao Li; Xin Chen; Junlong Yan (Tunnelling and Underground Space Technology, 2025)

End-to-end deep learning for pollutant prediction using street view images - Lijie Wu; Xiansheng Liu; Xun Zhang; Rui Wang; Zhihao Guo (Urban Climate, 2025)

Novel approaches for alleviating shallow soil compaction using microbial fertilizers and their beneficial impacts on plant growth and soil physicochemical properties - Xiang Yao; Hailin Guo; Dandan Li; Junqin Zong; Rui Zhang; Jingbo Chen; Dongli Hao; Xinyong Zhao; Jianxiu Liu; Haoran Wang; Chunjie Li (Soil and Tillage Research, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Co-exposure to polystyrene nanoplastics and F-53B induces vascular endothelial cell pyroptosis through the NF-κB/NLRP3 pathway - Junli Lv; Zhenzhen Tan; Ziwen An; Rui Xu; Huaxing Zhang; Mingmei Guo; Fang Xiao; Mengwei Zhao; Yi Guo; Yi Liu; Xuehui Liu; Jingtao Ma; et al. (Journal of Hazardous Materials, 2025)

A rapid and nondestructive quantitative detection method for total and organic selenium in selenium-enriched kefir grain based on hyperspectral imaging - Menghui Li; Jinyi Yang; Xing Guo; Rui Sun; Gechao Zhang; Wenhui Liu; Yuanye Liu; Zhouli Wang; Yahong Yuan; Tianli Yue (Food Control, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Implementation and optimisation of the cdugksFoam solver on the Sunway TaihuLight supercomputer - Jie Guo; Yunlan Wang; Rui Zhang; Feifei Zhang; Tianhai Zhao; Congshan Zhuo; Sha Liu; Chengwen Zhong (Computer Physics Communications, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Mapping of leaf lobe-related genes in melon (Cucumis melo L.) via bulked segregant analysis - Meng-Ling Zheng; Lu Yang; Ding-Ding Zuo; Rui Sun; Jing Zhang; Yan-Ge Li; Zhong-Hou Zhu; Xue-Jie Zhu; Da-Long Guo (Euphytica, 2025)

ANFIS-Based Course Controller Using MMG Maneuvering Model - Yu Guo; Rui Yang; Zhiheng Zhang; Bing Han (Journal of Marine Science and Engineering, 2025)
In the domain of course control, traditional methods such as proportional–integral–derivative (PID) control often exhibit limitations when addressing complex nonlinear systems and uncertain disturbances. To mitigate these challenges, the adaptive neuro-fuzzy inference system (ANFIS) has been integrated into course control strategies. The primary objective of this study is to investigate the course control characteristics of vessels governed by the ANFIS controller under both normal and severe sea conditions. A three-degree-of-freedom (3-DOF) maneuvering model set (MMG) was employed and validated through sea turning tests. The design of the ANFIS controller involved a combination of the backpropagation algorithm with the least square method. Training data for the ANFIS control system were derived from a linear control framework, followed by simulation tests conducted under normal and severe sea conditions to assess control performance. The simulation results indicate that in normal sea conditions, ANFIS has more stable heading control (smaller Aψ), but at the cost of more energy consumption (larger Iδ). Notably, response time is reduced by approximately 36.7% compared to that of the linear controller. Conversely, during severe sea conditions, ANFIS exhibits an increase in response time by about 33.3% relative to the linear controller while maintaining a smaller Iδ. In the whole course control stage, the stability is better than the linear controller, and it has better energy-saving characteristics. Under scenarios involving small and large course alterations, Aψ values for ANFIS are approximately 11.28% and 13.97% higher than those observed with the best-performing linear controller (λψ = 60), respectively. As the propeller speed increases, the Aψ value of the ANFIS controller decreases significantly, to about 62.71%, indicating that the energy efficiency is improved and the course stability is also enhanced. In conclusion, it can be asserted that the implementation of an ANFIS controller yields commendable performance in terms of controlling vessel courses effectively.

Monitoring nutrient and beneficial elements in the topsoil: the function of weathered background and later surficial process on their distribution - Bo Zhang; Kai-Ning Lv; Huan Li; Qin-Rui Zhang; Zhi-Qiang Yin; Wei-Zhi Zhou; Guo-Li Yuan (Environmental Monitoring and Assessment, 2025)

Assessment of the bioflocculant production and safety properties of Metabacillus hrfriensis sp. nov. based on phenotypic and whole-genome sequencing analysis - Rui Zhang; Zhigang Zhao; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Aquaculture, 2025)

Corrigendum to “Differentiation of sow and mouse ovarian granulosa cells exposed to zearalenone in vitro using RNA-seq gene expression” [Toxicology and Applied Pharmacology, 350 (2018) 78–90] - Guo-Liang Zhang; Jun-Lin Song; Yi Zhou; Rui-Qian Zhang; Shun-Feng Cheng; Xiao-Feng Sun; Guo-Qing Qin; Wei Shen; Lan Li (Toxicology and Applied Pharmacology, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Mechanical deformation destabilizing hydrate within thermodynamic equilibrium region - Peng Zhang; Xueping Chen; Rui Bao; Xu Ma; Yulu Wang; Yangli Che; Lianhai Zhang; Yingmei Wang; Jing Zhan; Guangjun Guo; Changyu Sun; Jianyang Wu; et al. (Fuel, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Recent advances in cold plasma technology for enhancing the safety and quality of meat and meat products: A comprehensive review - Changyan Zhang; Yulong Luo; Ziyao Deng; Rui Du; Mei Han; Junqin Wu; Wenxiu Zhao; Rong Guo; Yanru Hou; Songlei Wang (Food Research International, 2025)

Electrostatic field combined with edible chitosan-based pickering emulsion coating for extending the shelf-life of arrowhead (Sagittaria sagittifolia L.) vegetables - Qing Guo; Min Zhang; Arun S. Mujumdar; Luming Rui (Food Bioscience, 2025)

One new MOF with hierarchical pores achieving efficient one-step purifying C2H2, recycling CH4 and eliminating CO2 in C2H2 production - Lin Zhang; Ya-Li Bao; Rui-Cheng Gao; Wen-Juan Shi; Yi-Zhao Guo; Lei Hou; Yao-Yu Wang (Chemical Engineering Journal, 2025)

Strengthening H2 gas–liquid mass transfer using superaerophobic cathodes for enhanced methane production from CO2 in H2-mediated microbial electrosynthesis system - Jia-Yao Gao; Wen-Fang Cai; Ji-Rui Bai; Yu-Cheng Zhu; Yu-Xiao Zhang; Sheng Wang; Kun Guo; Qing-Yun Chen; Yun-Hai Wang (Bioresource Technology, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Clogging Patterns and Mechanisms in Landfill Leachate Drainage Layers - Yuliang Guo; Liwen Cao; Yan Mei; Rui Zhang (Geotechnical and Geological Engineering, 2025)

A multifunctional biosensor for selective identification, sensitive detection and efficient photothermal sterilization of Salmonella typhimurium and Staphylococcus aureus - Huasong Dai; Yingyue Zhang; Wenshi Zhao; Rui Guo; Sihan Qian; Yang Xu; Yuxuan Li; Yang Liu; Hongbo Liu (Analytica Chimica Acta, 2025)

Differential responses of soil CO2 dynamics along soil depth to rainfall patterns in the Chinese Loess Plateau - Xiao Yang; Rui Wang; Mengdi Yang; Quanfeng Liu; Wenju Zhang; Shengli Guo (Agriculture, Ecosystems & Environment, 2025)

A high-available segmentation algorithm for corn leaves and leaf spot disease based on feature fusion - Falin Guo; Caihua Yao; Rui Yang; Miaomiao Ma; Xiaojiang Wu; Zihan Xu; Ming Lu; Jie Zhang; Guoshu Gong (Crop Protection, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Heat-resistant boron Carbonitride with nitrogen-vacancies and oxygen-doping for efficient tetracycline removal: Adsorption characteristics, mechanism and regeneration - Xu-Dong Miao; Rui-Xiang Zhang; Wen-Tao Li; Qian Wang; Yu-Han Cai; Yong Guo; Ai-Min Li (Journal of Water Process Engineering, 2025)

Interval prediction of fuel cell degradation based on voltage signal frequency characteristics with TimesNet-GPR under dynamic conditions - Wenchao Zhu; Yongjia Li; Yafei Xu; Leiqi Zhang; Bingxin Guo; Rui Xiong; Changjun Xie (Journal of Cleaner Production, 2025)

Corporate innovation's impact on the cost of equity: Evidence from Chinese listed companies - Shixin Zheng; Xuefeng Wang; Yongji Zhang; Rui Guo; Hongshu Chen (Journal of Cleaner Production, 2025)

Solve the cause, not the symptom: Managerial myopia and environmental investment preferences - Rui Zhu; Yalan Zhang; Huixiang Zeng; Lian Guo (Journal of Environmental Management, 2025)

Extraction of phenolic acids and tetramethylpyrazine in Shanxi aged vinegar base on vortex-assisted liquid-liquid microextraction-hydrophobic deep eutectic solvent: COSMO-RS calculations and ANN-GA optimization - Baoqing Bai; Siyuan Meng; Yanli Guo; Ziqing Zhang; Rui Chen; Tao Bo; Jinhua Zhang; Sanhong Fan; Yukun Yang (Food Chemistry, 2025)

Multi-omics reveal inhibitory effects of Protopanaxadiol on metastasis through PI3K-Akt and MAPK pathway in human cervical cancer HeLa cells - Rui Lu; Juanjuan Liu; Kiran Thakur; Hui Cao; Juan Carlos Mejuto; Jesus Simal-Gandara; Jian-Guo Zhang (Food Bioscience, 2025)

Effect of the Hofmeister series anion salts on the ice recrystallization inhibition activity of tamarind seed polysaccharide - Xianbao Sun; Shihao Dai; Rui Guo; Taijie Zhan; Fan Xie; Yuxing Kou; Xuan Ma; Yinan Chen; Lihua Song; Hui Zhang; Lu Ren; Chunmei Yuan; et al. (Food Hydrocolloids, 2025)

Fabrication of the ferritin-mannoprotein shell-core heteroprotein complex for stabilization of bioactive molecules - Xinmei Sha; Runxuan Chen; Yichen Li; Tianyang Wang; Ku Li; Hui Guo; Yuyu Zhang; Rui Yang (Food Hydrocolloids, 2025)

Effects of water immersion on immune, intestinal flora and metabolome of Chinese mitten crab (Eriocheir sinensis) after air exposure - Xiangyi Deng; Zhiqiang Li; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Guo Qiao; Yuhong Yang; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Physicochemical properties, structural characterization, and antidiabetic activity of selenylated low molecular weight apple pectin in HFD/STZ-induced type 2 diabetic mice - Wen Tao; Diguo Liu; Ziqi Guo; Pengfei Han; Yan Ma; Muci Wu; Rui Zhang; Jingren He (Carbohydrate Polymers, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Evaluating pulmonary toxicity of PFOS and its alternative OBS using spheroids of A549 cells - Chong-Rui Yao; Yu-Xia Jiang; Si-Ying Li; Zhi-Jie Lu; Xiao-Bing Long; Na Xin; Jin-Ge Zhang; Dong-Dong Ma; Guang-Guo Ying; Wen-Jun Shi (Science of The Total Environment, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Flame propagation analyses of aluminium coated with various concentrations of stearic acid based upon elementary reaction simulation - Rui Guo; Yuxiong Huang; Xinyan Zhang; Yansong Zhang; Chang Xu; Yanjie Niu; Jiang Qin (Process Safety and Environmental Protection, 2024)

Holocene paleoenvironment of the Nihewan Basin, China, inferred from high-resolution luminescence dating and a multiproxy analysis of gully sediments - Qing-Hao Ma; Yu-Jie Guo; Hua-Rui Lei; Yu-He Shen; Jia-Jing Wang; Ya Liu; Zhen-Yu Zhou; Jia-Fu Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effective variance attention-enhanced diffusion model for crop field aerial image super resolution - Xiangyu Lu; Jianlin Zhang; Rui Yang; Qina Yang; Mengyuan Chen; Hongxing Xu; Pinjun Wan; Jiawen Guo; Fei Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Protopanaxadiol triggers G0/G1 cell cycle arrest and apoptosis in human cervical cancer HeLa cells through the PPER pathway - Rui Lu; Juanjuan Liu; Kiran Thakur; Hui Cao; Juan Carlos Mejuto; Jesus simal Gandara; Jian-Guo Zhang (Food Bioscience, 2024)

Composition of four polyphenol fractions extracted from partridge tea and their mechanisms on ameliorate insulin resistance in HepG2 cells - Ke-Xin Hao; Ying-Jing Zhang; Rui-Fang Zhong; Yi-Meng Li; Ling Wang; Xiao Chang; Da-Wei Wang; Jian-Guo Jiang; Wei Zhu (Food Bioscience, 2024)

The inoculation of Bacillus paralicheniformis and Streptomyces thermoviolaceus enhances the lignocellulose degradation and microbial communities during spent mushroom substrate composting - Jiao Zhang; Ya-Jie Zou; Shun-Li Wang; Wei-Wei Zhang; Qing-Jun Chen; Qiu-Ying Wang; Ti-Kun Guan; Jia-Yan Zhang; Min-Rui Zhao; Guo-Qing Zhang (Environmental Research, 2024)

Insights into carbon-neutral treatment of rural wastewater by constructed wetlands: A review of current development and future direction - Feifei Jiao; Xinzheng Zhang; Tao Zhang; Yong Hu; Rui Lu; Guangyi Ma; Tao Chen; Hongbo Guo; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Multiomics analysis reveal the impact of 17α-Ethinylestradiol on mortality in juvenile zebrafish - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying; Wen-Jun Shi (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Deciphering the nonlinear and synergistic role of building energy variables in shaping carbon emissions: A LightGBM- SHAP framework in office buildings - Congyue Zhou; Zhu Wang; Xuanli Wang; Rui Guo; Zhao Zhang; Xingwei Xiang; Yiqun Wu (Building and Environment, 2024)

SLC15A3 is transcriptionally regulated by HIF1α and p65 to worsen neuroinflammation in experimental ischemic stroke - Shan Yu; Jinghui Yang; Rui Zhang; Qian Guo; Lu Wang (Molecular Neurobiology, 2024)

Yam (Rhizoma Dioscoreae) polysaccharide affects growth performance, immunity, and intestinal microbial community in Bulatmai barbel (LucioBarbus capito) - Liang Luo; Xianwei Meng; Shihui Wang; Rui Zhang; Kun Guo; Gaochao Wang; Wei Wang; Zhigang Zhao (Animal Feed Science and Technology, 2024)

Rapid and accurate bacteria identification through deep-learning-based two-dimensional Raman spectroscopy - Yichen Liu; Yisheng Gao; Rui Niu; Zunyue Zhang; Guo-Wei Lu; Haofeng Hu; Tiegen Liu; Zhenzhou Cheng (Analytica Chimica Acta, 2024)

ZC3H13 promotes autophagy in bladder cancer through m6A methylation modification of PJA2 and ubiquitination of KSR1 - Beibei Liu; Mengjie Chen; Yujie Liang; Zhijie Mei; Wei Sun; Wuyue Gao; Tiantian Zhang; Rui Wang; Yuanyuan Guo (Human Cell, 2024)

The effect of green coffee extract supplementation on obesity indices: critical umbrella review of interventional meta-analyses - Zhao Yang; Zhuo Shao; Weiyi Ouyang; Lu Ying; Rui Guo; Mingxuan Hao; Youfeng Liang; Wenjing Zhang; Xiaoyang Chen; Ruolan Chen; Changyuan Yu; Kousalya Prabahar; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Ferritinophagy is involved in hexavalent chromium-induced ferroptosis in Sertoli cells - Ruijian Zhuge; Le Zhang; Qian Xue; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Chunyang Meng; Rifeng Lu; Fei Yin; Li Guo (Toxicology and Applied Pharmacology, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

Comprehensive compositional analysis of liquid organic product prepared by industrialized hydrothermal cracking of biomass waste and its potential application as fertilizer - Rui Xia; Jue Wang; Xiao-xiao Yang; Qing-hai Li; Hui Zhou; Hui Sun; Yan-guo Zhang (Science of The Total Environment, 2024)

Seasonal wet–dry transition and denitrifying communities contributed to nitrous oxide emissions in the water-level fluctuating zone of the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Zixu Guo; Junxiang Cheng; Zhongbo Yu; Ligang Xu; Qinglong L. Wu; Jin Zeng (Journal of Hydrology, 2024)

Manipulating surface reconstruction and lattice oxygen mechanism of nickel (oxy)hydroxide by defect engineering for industrial electrocatalytic water oxidation - Xiangling Wang; Zhimin Li; Yu Tang; Zhengfu Zhang; Chengping Li; Rui Bao; Guo Chen; Jinsong Wang (Chemical Engineering Journal, 2024)

A photosensitive modification of recombinant Salmonella carrying shRNA-PD-L1 promotes host immunity against poorly immunogenic tumors - Jiaying Yang; Mei Yang; Qi Wang; Qian Luo; Yingtong Wang; Jicheng Sun; Jixuan Liu; Jiasi Chen; Juanjuan Mao; Hailin Yin; Dhan V. Kalvakolanu; Baofeng Guo; et al. (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Disruption of a glycosyl transferase family 17 protein alters cadmium accumulation and resistance in rice (Oryza sativa) - Chun Yan Tu; Rui Guo; Chang Zhao Chen; Yong Qiang Gao; Lu Zheng; Qiang Zhang; Ren Fang Shen; Xiao Fang Zhu (Plant and Soil, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

Geographic variation in leaf traits and palatability of a native plant invader during domestic expansion - Yu‐Jie Zhao; Shengyu Wang; Zhi‐Yong Liao; Madalin Parepa; Lei Zhang; Peipei Cao; Jingwen Bi; Yaolin Guo; Oliver Bossdorf; Christina L. Richards; Jihua Wu; Bo Li; et al. (Ecology, 2024)
Like alien plant invasion, range expansion of native plants may threaten biodiversity and economies, rendering them native invaders. Variation in abiotic and biotic conditions across a large geographic scale greatly affects variation in traits and interactions with herbivores of native plant invaders, which is an interesting yet mostly unexplored issue. We used a common garden experiment to compare defensive/nutritional traits and palatability to generalist herbivores of 20 native (23.64° N–30.18° N) and introduced range (31.58° N–36.87° N) populations of Reynoutria japonica , which is a native invader following range expansion in China. We analyzed the relationships among herbivore pressure, climate, plant chloroplast haplotypes, leaf traits, and herbivore performance. Of the 16 variables tested, we observed range differences in 11 variables and latitudinal clines in nine variables. In general, herbivores performed better on the introduced plants than on the native plants, and better on the high‐latitude plants than on the low‐latitude plants within the introduced populations. Three key traits (leaf thickness, specific leaf area, and carbon‐to‐nitrogen [C:N] ratio) determined palatability to herbivores and were significantly associated with temperature and/or precipitation of plant provenance as well as with plant haplotypes but not with herbivore pressure. Our results revealed a causal sequence from plant‐range‐based environmental forces and genetic context to plant quality and palatability to herbivores in R. japonica . These findings suggest a post‐introduction evolution of R. japonica , which may partly explain the colonization success of this important native, but invasive plant.

Flow Field Analysis and Development of a Prediction Model Based on Deep Learning - Yingjie Yu; Xiufeng Zhang; Lucai Wang; Rui Tian; Xiaobin Qian; Dongdong Guo; Yanwei Liu (Journal of Marine Science and Engineering, 2024)
The velocity of ocean currents significantly affects the trajectory prediction of ocean drifters and the safe navigation of intelligent vessels. Currently, most ocean current predictions focus on time-based forecasts at specific fixed points. In this study, deep learning based on the flow field prediction model (CNNs–MHA–BiLSTMs) is proposed, which predicts the changes in ocean currents by learning from historical flow fields. Unlike conventional models that focus on single-point current velocity data, the CNNs–MHA–BiLSTMs model focuses on the ocean surface current information within a specific area. The CNNs–MHA–BiLSTMs model integrates multiple convolutional neural networks (CNNs) in parallel, multi-head attention (MHA), and bidirectional long short-term memory networks (BiLSTMs). The model demonstrated exceptional modelling capabilities in handling spatiotemporal features. The proposed model was validated by comparing its predictions with those predicted by the MIKE21 flow model of the ocean area within proximity to Dalian Port (which used a commercial numerical model), as well as those predicted by other deep learning algorithms. The results showed that the model offers significant advantages and efficiency in simulating and predicting ocean surface currents. Moreover, the accuracy of regional flow field prediction improved with an increase in the number of sampling points used for training. The proposed CNNs–MHA–BiLSTMs model can provide theoretical support for maritime search and rescue, the control or path planning of Unmanned Surface Vehicles (USVs), as well as protecting offshore structures in the future.

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

The OsNAC41-RoLe1-OsAGAP module promotes root development and drought resistance in upland rice - Shichen Han; Yulong Wang; Yingxiu Li; Rui Zhu; Yunsong Gu; Jin Li; Haifeng Guo; Wei Ye; Hafiz Ghualm Nabi; Tao Yang; Yanming Wang; Pengli Liu; et al. (Molecular Plant, 2024)

Metabolomics combined with intestinal microbiota analysis to reveal the effects of Inonotus hispidus on chronic kidney disease caused by high-protein diet - Xin Pang; Zitao Guo; Long Ao; Yong Huang; Bo Hu; Zhenghua Gu; Yu Xin; Zhongpeng Guo; Rui Zhu; Moying Li; Liang Zhang (Food Bioscience, 2024)

Association between heatwaves and risk and economic burden of injury related hospitalizations in China - Cheng Zhao; Yushu Huang; Yibin Cheng; Rui Zhang; Yu Wang; Shilu Tong; Jiang He; Jia Guo; Fan Xia; Yonghong Li; Xiaoyuan Yao (Environmental Research, 2024)

Advances in the Differentiation of hiPSCs into Cerebellar Neuronal Cells - Yingxin Wang; Wenzhu Liu; Yichang Jiao; Yitong Yang; Didi Shan; Xinbo Ji; Rui Zhang; Zexin Zhan; Yao Tang; Dandan Guo; Chuanzhu Yan; Fuchen Liu (Stem Cell Reviews and Reports, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Dexmedetomidine attenuates ferroptosis by Keap1-Nrf2/HO-1 pathway in LPS-induced acute kidney injury - Rui-Rui Luo; Jing Yang; Yan-Lin Sun; Bi-Ying Zhou; Si-Xuan Zhou; Guo-Xing Zhang; Ai-Xiang Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A study on the monitoring of landslide deformation disasters in Wenxian County, Longnan City based on different time-series InSAR techniques - Jinlong Zhang; Rui Yang; Yuan Qi; Hui Zhang; Juan Zhang; Qianhong Guo; Chao Ma; Hongwei Wang (Natural Hazards, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Long-term exposure to prometryn damages the visual system and changes color preference of female zebrafish (Danio rerio) - Shuhui Wei; Yixin Yang; Yao Zong; Yang Yang; Meiping Guo; Zhenzhong Zhang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Chemosphere, 2024)

Semi-liquid metal-based highly permeable and adhesive electronic skin inspired by spider web - Rui Guo; Xiaoqing Li; Yingtong Zhou; Yuqi Zhang; Chengjie Jiang; Yang Yu; Qingting Tan; Wenbo Ding; Hongzhang Wang (Science Bulletin, 2024)

Rare oxoisoaporphine alkaloids from Menispermum dauricum with potential anti-inflammatory activity - Rui Guo; Cun-Lin Wang; Xiao-Juan Cao; Xiao-Juan Yao; Xin Qiao; Ya-Tian Meng; Tong Zhang; Qiong Zhang (Phytochemistry, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Photochromic ionogel with a wide temperature range and fatigue resistance for high-resolution rewritable information record - Jingyue Zhang; Mengru Guo; Yuanteng Su; Wenxia Wu; Shicheng Wang; Rui Yang; Chao Xu; Hongzong Yin; Jiaheng Xu; Xiaolin Wang (Chemical Engineering Journal, 2024)

Genome-wide association study and selective sweep analysis uncover candidate genes controlling curd branch length in cauliflower - Yingxia Yang; Yutong Guo; Jing Wang; Wenjuan Cheng; Mingjie Lyu; Qian Wang; Jianjin Wu; Mingyan Hua; Weihua Zhang; Deling Sun; Xianhong Ge; Xingwei Yao; et al. (Theoretical and Applied Genetics, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Heterologous expression and characterization of two delta glutathione S-transferases genes involved in imidacloprid metabolism in Grapholita molesta - Qin-Wei Pang; Wen-Jie He; Ming-Gao Li; Ming Wang; Xue-Yao Zhang; Li-Jun Zhang; Ling-Ling Gao; Rui-Yan Ma; Yan-Qiong Guo; Qin Yu (Chemosphere, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Geogenic high arsenic elevates the groundwater antibiotic resistomes: A blind spot of resistance in Anthropocene - Rui Xu; Lingzhi Zhang; Fu-Yi Huang; Yong-Guan Zhu; Yi Zhao; Huaming Guo (Water Research, 2024)

Novel insights into the relationship between the functional groups and photoactivity of biochar-derived dissolved organic matter - Xin Zuo; Zhuozhi Ouyang; Jinmo Liao; Rui Ding; Weiwei Zhang; Chi Zhang; Xuetao Guo; Lingyan Zhu (Water Research, 2024)

Lithofacies, architecture and evolution of carbonate tidal delta system: Implications for reservoir heterogeneity (mid-cretaceous Mishrif Formation, Southeast Iraq) - Xiaowei Sun; Zhanfeng Qiao; Rui Guo; Guangya Zhu; Jianyong Zhang; Guanming Shao; Yu Zhang; Haiying Han; Zhehang Xu (Marine and Petroleum Geology, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Oxygen-driven closing pore formation in coal-based hard carbon for low-voltage rapid sodium storage - Rui Ma; Yaxin Chen; Qian Li; Binyuan Zhang; Feifei Chen; Changyu Leng; Dianzeng Jia; Nannan Guo; Luxiang Wang (Chemical Engineering Journal, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Strength and Deformation of Unsaturated Soil Contaminated with CH3COOH - Yuliang Guo; Liwen Cao; Zihaohan Sang; Rui Zhang; Pan Huo (Geotechnical and Geological Engineering, 2024)

Formation and growth of nanophase iron particles on the surface of Mercury revealed by experimental study - Ronghua Pang; Yang Li; Chen Li; Pengfei Zhang; Zhuang Guo; Sizhe Zhao; Han Yu; Li Wang; Chenxi Zhu; Shuangyu Wang; Kairui Tai; Qinwei Zhang; et al. (Acta Geochimica, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Riemann–Hilbert approach for the inhomogeneous discrete nonlinear Schrödinger equation with nonzero boundary conditions - Ya-Hui Liu; Rui Guo; Jian-Wen Zhang (Wave Motion, 2024)

Quercetin regulates dendritic cell activation by targeting STAT4 in the treatment of experimental autoimmune encephalomyelitis - Fang Zhou; Yu-Xin Guo; Rui Gao; Xiao-Yu Ji; Yu-Xuan Tang; Li-Bin Wang; Yuan Zhang; Xing Li (Toxicology and Applied Pharmacology, 2024)

Body size: A hidden trait of the organisms that influences the distribution of antibiotic resistance genes in soil - Rui Guo; Yanlai Yao; Zhe Zhang; Chunlai Hong; Fengxiang Zhu; Leidong Hong; Weijing Zhu (Journal of Hazardous Materials, 2024)

Hydrogen-donating behavior and hydrogen-shuttling mechanism of liquefaction solvents under Fe- and Ni-based catalysts - Haiyun Liu; Rui Zhang; Xin Zheng; Jing Xie; Bowen Tang; Zhi Li; Erguang Guo; Haoquan Hu; Lijun Jin (Fuel, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Untargeted LC–MS metabolomics reveals the metabolic responses in the Eriocheir sinensis gills exposed to salinity and alkalinity stress - Shihui Wang; Yingying Song; Liang Luo; Rui Zhang; Kun Guo; Zhigang Zhao (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Genome-wide identification of the MED25 BINDING RING-H2 PROTEIN gene family in foxtail millet (Setaria italica L.) and the role of SiMBR2 in resistance to abiotic stress in Arabidopsis - Yimin Fan; Yue Guo; Haiying Zhang; Rui Han; Pu Yang; Zhen Liang; Lizhen Zhang; Ben Zhang (Planta, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

The complete chloroplast genome sequence and phylogenetic relationship analysis of Eomecon chionantha, one species unique to China - Zhi Zhang; Guoshuai Zhang; Xinke Zhang; Huihui Zhang; Junbo Xie; Rui Zeng; Baolin Guo; Linfang Huang (Journal of Plant Research, 2024)

Research on the effect of shallow draft on the performance of azimuth thruster under bollard conditions - Heng Li; Jian-Qiang Wang; Xue-Qin Liu; Guo-Rui Ji; Yan Zhang; Zhi-Yuan Wei (Ocean Engineering, 2024)

Inactivation of microorganisms on fabrics using plasma-activated nebulized mist driven by different plasma gases - Pengyu Zhao; Sihong Ma; Li Guo; Yikang Jia; Rui Zhang; Min Chen; Zifeng Wang; Dingxin Liu; Yuan Zhao; Xiaohua Wang; Mingzhe Rong (Journal of Hazardous Materials, 2024)

Multifunctional BiOBr/BiOI 3D microspheres for improving visible-light-driven photocatalytic degradation and disinfection efficiency - Saifeng Zhang; Jian Guo; Saisai Deng; Rui Zhang; Qiuyu Zhu; Yuanxu Liu; Xiangang Lin; Yangyang Li (Journal of Environmental Chemical Engineering, 2024)

Regulating the defects of MIL-101(Cr) for the efficient and simultaneous determination of eleven plant growth regulators in fresh fruit juice - Rui Cheng; Yiqun Wan; Xuejin Mao; Hao Wan; Fan Liu; Lan Guo; Bingzhen Zhang (Food Chemistry, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Electrochemically assisted preparation of graphitic carbon nitride nanosheet membranes for efficient water purification - Yisa Zhou; Ya Zhang; Jian Xue; Rui Wang; Jiale Dong; Zongjie Yin; Chen Guo; Haihui Wang (Chemical Engineering Journal, 2024)

Simultaneous biogas upgrading and single cell protein production using hydrogen oxidizing bacteria - Rui Li; YuFeng Jiang; JieHua Huang; Kai Luo; XiaoLei Fan; RongBo Guo; Tao Liu; YiFeng Zhang; ShanFei Fu (Chemical Engineering Journal, 2024)

Preparation of crab-shell-based N, O co-doped graded porous carbon for supercapacitors using the confined nanospace deposition method - Yiming Li; Zhihao Yu; Mengyan Guo; Ming Zhang; Jian Xiong; Yina Qiao; Rui Zhang; Xuebin Lu (Waste Disposal & Sustainable Energy, 2024)

Impacts of permafrost degradation on streamflow in the northern Himalayas - Linfeng Fan; Fang Ji; Xingxing Kuang; Zhilin Guo; Rui Zhang; Chunmiao Zheng (Science China Earth Sciences, 2024)

Soil moisture drives the shift from selection to complementarity effect in the rainfed maize/faba bean intercropping system - Wei Wang; Meng-Ying Li; Wei Zhang; Aziz Khan; Rui Zhou; Shuang-Guo Zhu; Bao-Zhong Wang; Yu-Miao Yang; Hong-Yan Tao; Wen-Bo Li; You-Cai Xiong (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Curcumol: a review of its pharmacology, pharmacokinetics, drug delivery systems, structure–activity relationships, and potential applications - Sicheng Zhai; Rui Wang; Jingyuan Wang; Xiangdong Xu; Le Niu; Min Guo; Yongling Zhang; Yajun Shi; Xuexue Tang (Inflammopharmacology, 2024)

Intestinal carcinogenicity screening of environmental pollutants using organoid-based cell transformation assay - Ziwei Wang; Shen Chen; Yuzhi Guo; Rui Zhang; Qi Zhang; Xinhang Jiang; Miao Li; Yue Jiang; Lizhu Ye; Xiaoyu Guo; Chuang Li; Guangtong Zhang; et al. (Archives of Toxicology, 2024)

Precambrian tectono-magmatic evolution of the western margin of the Yangtze block, South China: evidence from zircon U-Pb-Lu-Hf isotopes, REE and trace elements of Yuanmou-Miyi complexes - Youliang Chen; Guoxin Zhan; Lipeng Qu; Guiqin Yin; Yanhong Guo; Yuwen Zheng; Rui Guo; Guan Yin; Chengjiang Zhang (International Geology Review, 2024)

Unveiling of dietary and gut-microbiota derived B vitamins: Metabolism patterns and their synergistic functions in gut-brain homeostasis - Qi Zhan; Rui Wang; Kiran Thakur; Jing-Yu Feng; Yun-Yang Zhu; Jian-Guo Zhang; Zhao-Jun Wei (Critical Reviews in Food Science and Nutrition, 2024)

Establishment, characterization and application of Largemouth bronze gudgeon (Coreius guichenoti) fin and skin cell lines in disease resistance - Qi Zhang; Zhihong Gong; Rui Shi; Yuhong Shi; Chenfei Guo; Xiaolin Liao; Hua Tian; Na Wang (Aquaculture, 2024)

A novel aldo-keto reductase gene, OsAKR1, from rice confers higher tolerance to cadmium stress in rice by an in vivo reactive aldehyde detoxification - Rui Guo; Qiang Zhang; Chang Zhao Chen; Jie Ya Sun; Chun Yan Tu; Meng Xing He; Ren Fang Shen; Jiu Huang; Xiao Fang Zhu (Journal of Hazardous Materials, 2024)

Association between air pollution and male sexual function: A nationwide observational study in China - Ziyuan Shen; Feng Zhang; Zihan Guo; Rui Qu; Yiqiu Wei; Jingxuan Wang; Weiqian Zhang; Xing Xing; Yan Zhang; Jue Liu; Dongdong Tang (Journal of Hazardous Materials, 2024)

Experimental study and model optimization of thermodynamic performance of a single screw water vapor compressor - Huafu Zhang; Zhentao Zhang; Lige Tong; Junling Yang; Yanan Li; Li Wang; Xia Guo; Rui Tian; Mingxin He; Chongguang Gao (International Journal of Refrigeration, 2024)

Insights into “wheat aroma”: Analysis of volatile components in wheat grains cultivated in saline–alkali soil - Qianqian Sun; Rui Zhang; Yu Liu; Liya Niu; Hongyan Liu; Peifang Ren; Bianna Xu; Boli Guo; Bo Zhang (Food Research International, 2024)

Highly thermally conductive composites with boron nitride nanoribbon array - Peng Wei; Lei Feng; Qiang Chen; Zhijie Dong; Qiang Song; Rui Tian; Ruoxi Zhang; Liyuan Guo; Dongfang Xu; Mengdan Hou; Haojie Song (Chemical Engineering Journal, 2024)

Exploiting genomic tools for genetic dissection and improving the resistance to Fusarium stalk rot in tropical maize - Junqiao Song; Yubo Liu; Rui Guo; Angela Pacheco; Carlos Muñoz-Zavala; Wei Song; Hui Wang; Shiliang Cao; Guanghui Hu; Hongjian Zheng; Thanda Dhliwayo; Felix San Vicente; et al. (Theoretical and Applied Genetics, 2024)

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

Preparation and application of biocontrol formulation of nematode-trapping fungus-Duddingtonia flagrans - Luyao Hao; Yuan Guo; Xiaomin Wang; Mingjuan Gao; Tonghai Liu; Yuan Ma; Yanni Zhang; Qiannan Li; Rui Wang; Xihuo You (Veterinary Parasitology, 2024)

Carbazomycins I and J, two novel carbazole alkaloids isolated from Saccharopolyspora phattalungensis - Wen Wang; Er Juan Zhao; Ting Peng; Zhang Yuan Yan; Zhi Kai Guo; Rui Hua Jiao (Phytochemistry Letters, 2024)

Arbuscular mycorrhizal fungi reduce ammonia emissions under different land-use types in agro-pastoral areas - Huaisong WANG; Rui GUO; Yibo TIAN; Nan CUI; Xinxin WANG; Lei WANG; Zhongbao YANG; Shuying LI; Jixun GUO; Lianxuan SHI; Tao ZHANG (Pedosphere, 2024)

Screening androgen receptor agonists of fish species using machine learning and molecular model in NORMAN water-relevant list - Xiao-Bing Long; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Chang-Er Chen; Guang-Guo Ying; Wen-Jun Shi (Journal of Hazardous Materials, 2024)

Association between ambient PM1 and the prevalence of chronic kidney disease in China: A nationwide study - Rui Chen; Chao Yang; Yuming Guo; Gongbo Chen; Shanshan Li; Pengfei Li; Jinwei Wang; Ruogu Meng; Huai-yu Wang; Suyuan Peng; Xiaoyu Sun; Fulin Wang; et al. (Journal of Hazardous Materials, 2024)

Retarding ice recrystallization by tamarind seed polysaccharide: Investigation in ice cream mixes and insights from molecular dynamics simulation - Xianbao Sun; Rui Guo; Taijie Zhan; Yuxing Kou; Xuan Ma; Hong Song; Wei Zhou; Lihua Song; Hui Zhang; Fan Xie; Chunmei Yuan; Zibo Song; et al. (Food Hydrocolloids, 2024)

Molten salt etching synthesis of Ti3C2Tx/Ni composites for highly efficient capacitive deionization - Wen Xi; Tianzhuo Guo; Zeren Xie; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Desalination, 2024)

Ternary Zn3V3O8 superstructure and synergistic modification of separator promote high performance and stable zinc ion battery - Rui Sun; Peng Xia; Xincheng Guo; Siyang Dong; Feng Xu; Yufei Zhang; Shengjun Lu; Qiang Zheng; Haosen Fan (Chemical Engineering Journal, 2024)

A polypyrrole-dopamine/poly(vinyl alcohol) anisotropic hydrogel for strain sensor and bioelectrodes - Shuang Chen; Bingyan Guo; Jiajun Yu; Zhuojun Yan; Rui Liu; Chaojie Yu; Zhongming Zhao; Hong Zhang; Fanglian Yao; Junjie Li (Chemical Engineering Journal, 2024)

The toxicity of polystyrene micro- and nano-plastics on rare minnow (Gobiocypris rarus) varies with the particle size and concentration - Tingting Chu; Rui Zhang; Fuyu Guo; Meng Zhu; Shuting Zan; Ruyi Yang (Aquatic Toxicology, 2024)

Intercropping efficiently utilizes phosphorus resource in soil via different strategies mediated by crop traits and species combination - Ran An; Rui-Peng Yu; Yi Xing; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Plant and Soil, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Eco-driving strategy for connected electric buses at the signalized intersection with a station - Yali Zhang; Rui Fu; Yingshi Guo; Wei Yuan (Transportation Research Part D: Transport and Environment, 2024)

Cypermethrin induces Sertoli cell apoptosis through endoplasmic reticulum-mitochondrial coupling involving IP3R1-GRP75-VDAC1 - Rui Zhang; Xu-Xu Wang; Jia-fei Xie; Ting-ting Yao; Qian-wen Guo; Qi Wang; Zhen Ding; Jin-Peng Zhang; Mei-Rong Zhang; Li-Chun Xu (Reproductive Toxicology, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Arbuscular mycorrhizal fungi offset NH3 emissions in temperate meadow soil under simulated warming and nitrogen deposition - Nan Cui; Stavros Veresoglou; Yibo Tian; Rui Guo; Lei Zhang; Li Jiang; Furong Kang; Weizhe Yuan; Dan Hou; Lianxuan Shi; Jixun Guo; Mingzhou Sun; et al. (Journal of Environmental Management, 2024)

3D reconstruction and characterization of cotton bolls in situ based on UAV technology - Shunfu Xiao; Shuaipeng Fei; Yulu Ye; Demin Xu; Ziwen Xie; Kaiyi Bi; Yan Guo; Baoguo Li; Rui Zhang; Yuntao Ma (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effect of konjac glucomannan with different degrees of deacetylation on the gel behavior of transglutaminase induced soybean protein isolate emulsion gels - Yuntao Wang; Hui Zhang; Qing Liang; Xiuqin Guo; Zijian Niu; Si Qiu; Wei Xu; Rui Li (Food Hydrocolloids, 2024)

Integrated straw-derived biochar utilization to increase net ecosystem carbon budget and economic benefit and reduce the environmental footprint - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2024)

Spatial distribution and risk assessment of pyrethroid insecticides in surface waters of East China Sea estuaries - Rui Wang; Feng Wang; Yintao Lu; Shengwei Zhang; Minghong Cai; Dongdong Guo; Hongyuan Zheng (Environmental Pollution, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Ecological flow considering hydrological season and habitat suitability for a variety of fish - Xinyu Li; Qirui Zhang; Yanfang Diao; Yuzhi Shi; Shuxian Li; Chuanhui Yao; Rui Su; Shichao Guo (Ecological Modelling, 2024)

Differentiation of prokaryotic community composition in suspended sediment size-fractionation in a small loess watershed - Tongtong Li; Wei Zhang; Lin Yang; Shengli Guo; Rui Wang (CATENA, 2024)

Serum Uric Acid Levels and Outcome of Acute Ischemic Stroke: a Dose–Response Meta-analysis - Peng Zhang; Rui Wang; Yang Qu; Zhen-Ni Guo; Qing Zhen; Yi Yang (Molecular Neurobiology, 2024)

Warming Tends to Promote Nitrogen Conservation but Stimulate N2O Emissions in Mangrove Sediments - Ning Zhang; Rui Guo; Feifei Wang; Zetao Dai; Yasong Li; Wenzhi Cao (Ecosystems, 2024)

The Effect of Artificial Substrate and Carbon Source Addition on Bacterial Diversity and Community Composition in Water in a Pond Polyculture System - Kun Guo; Mumin Shi; Xiaoli Huang; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Guoliang Ruan; Zhigang Zhao (Fishes, 2024)
The use of artificial substrates and biofloc technology can favor fish culture and improve water quality. The aim of this study was to evaluate whether artificial substrates and carbon source additions modify the microbial activity of water bodies. The diversity and structure of microflora in the water after adding artificial substrates and carbon sources to the ponds were analyzed using high-throughput sequencing based on the V3-V4 region of 16S rRNA genes. The results showed that there was no difference in the richness and diversity of intestinal microflora between the control and experimental groups. Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) showed that artificial substrate and carbon source addition changed the structure of the microflora. The results of a linear discriminant analysis (LDA) effect size (LefSe) indicated 11 biomarkers in the EGˍst group. Spearman correlation heatmap analysis showed that environmental factors affected the bacterial communities, and the results of a redundancy analysis indicated that chemical oxygen demand was a critical factor in controlling the bacterial communities in the water. These results provide an understanding of the effect of artificial substrate and carbon source addition on bacterial diversity and community composition in water.

Dynamic spillover effects between EU economic sanctions against Russia, oil prices, and share prices of energy companies in third countries: evidence from China and the USA - Ming Li; Zaixu Zhang; Xiaoyu Wang; Rui Guo (Environmental Science and Pollution Research, 2024)

Hybrid organic frameworks: Synthesis strategies and applications in photocatalytic wastewater treatment - A review - Zhaobo Wang; Hongxin Wang; Peng Shi; Jiangyuan Qiu; Rui Guo; Junhua You; Hangzhou Zhang (Chemosphere, 2024)

In silico prediction and a systematic toxicology-based in vivo investigation uncovering the mechanism of aquatic toxicity caused by beta-lactam antibiotics - Ruixian Guo; Xinyan Ma; Huibo Xu; Yuanyuan Ma; Rui Zhang; Xinyan Liu; Binan Lu; Jingpu Zhang; Ying Han (Chemosphere, 2024)

Thallium content in vegetables and derivation of threshold for safe food production in soil: A meta-analysis - Xiyuan Xiao; Wenqiang Zhou; Zhaohui Guo; Chi Peng; Rui Xu; Yunxia Zhang; Yunyun Yang (Science of The Total Environment, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

A tale of two vein types: Bed-parallel fibrous versus blocky filled fractures in organic-rich shales and their overpressured hydrocarbon fluids - Miao Wang; Feng Liang; Tong Lin; Yelei Wang; Hui Zhang; Qian Huang; Yifan Song; Tingting Liu; Yanwei Feng; Rui Ni; Xiaoying Guo; Tengfei Zhou; et al. (Marine and Petroleum Geology, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Efficient benzo(a)pyrene degradation by coal gangue-based catalytic material for peroxymonosulfate activation - Chunquan Li; Shuaijun Yin; Yutong Yan; Chao Liang; Qingshui Ma; Rui Guo; Yubo Zhang; Jiushuai Deng; Zhiming Sun (Journal of Environmental Management, 2024)

Enhanced O/W emulsion stability and betanin protection using yeast protein and chitooligosaccharide: Comparative insights from complex coacervation and layer-by-layer methods - Jiangnan Hu; Rui Yang; Runxuan Chen; Chang Liu; Xinmei Sha; Ku Li; Hui Guo; Yuyu Zhang (Food Hydrocolloids, 2024)

GC-IMS determination of volatile organic compounds as potential indicators of wheat germination rate - Yu Liu; Shuwei Ren; Qianqian Sun; Boli Guo; Yingquan Zhang; Ming Li; Rui Zhang (Food Bioscience, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Characteristics, sources, and health risk assessment of atmospheric particulate mercury in Guanzhong Basin - Xiaofei Li; Rui Zhang; Lekhendra Tripathee; Feng Yu; Jingning Guo; Wen Yang; Junming Guo; Shichang Kang; Junji Cao (Environmental Pollution, 2024)

Biogas upgrading by biotrickling filter: Effects of temperature and packing materials - Jie-Hua Huang; Xiao-Lei Fan; Rui Li; Meng-Ting Sun; Hua Zou; Yi-Feng Zhang; Rong-Bo Guo; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Heavy Metal Scavenger Metallothionein Rescues Against Cold Stress-Evoked Myocardial Contractile Anomalies Through Regulation of Mitophagy - Zhaohui Pei; Yayuan Xiong; Shasha Jiang; Rui Guo; Wei Jin; Jun Tao; Zhenzhong Zhang; Yingmei Zhang; Yunzeng Zou; Yan Gong; Jun Ren (Cardiovascular Toxicology, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A global meta‐analysis of yield‐scaled N 2 O emissions and its mitigation efforts for maize, wheat, and rice - Zhisheng Yao; Haojie Guo; Yan Wang; Yang Zhan; Tianli Zhang; Rui Wang; Xunhua Zheng; Klaus Butterbach‐Bahl (Global Change Biology, 2024)
Maintaining or even increasing crop yields while reducing nitrous oxide (N 2 O) emissions is necessary to reconcile food security and climate change, while the metric of yield‐scaled N 2 O emission (i.e., N 2 O emissions per unit of crop yield) is at present poorly understood. Here we conducted a global meta‐analysis with more than 6000 observations to explore the variation patterns and controlling factors of yield‐scaled N 2 O emissions for maize, wheat and rice and associated potential mitigation options. Our results showed that the average yield‐scaled N 2 O emissions across all available data followed the order wheat (322 g N Mg −1 , with the 95% confidence interval [CI]: 301–346) > maize (211 g N Mg −1 , CI: 198–225) > rice (153 g N Mg −1 , CI: 144–163). Yield‐scaled N 2 O emissions for individual crops were generally higher in tropical or subtropical zones than in temperate zones, and also showed a trend towards lower intensities from low to high latitudes. This global variation was better explained by climatic and edaphic factors than by N fertilizer management, while their combined effect predicted more than 70% of the variance. Furthermore, our analysis showed a significant decrease in yield‐scaled N 2 O emissions with increasing N use efficiency or in N 2 O emissions for production systems with cereal yields >10 Mg ha −1 (maize), 6.6 Mg ha −1 (wheat) or 6.8 Mg ha −1 (rice), respectively. This highlights that N use efficiency indicators can be used as valuable proxies for reconciling trade‐offs between crop production and N 2 O mitigation. For all three major staple crops, reducing N fertilization by up to 30%, optimizing the timing and placement of fertilizer application or using enhanced‐efficiency N fertilizers significantly reduced yield‐scaled N 2 O emissions at similar or even higher cereal yields. Our data‐driven assessment provides some key guidance for developing effective and targeted mitigation and adaptation strategies for the sustainable intensification of cereal production.

Super Resolution Mapping of Scatterometer Ocean Surface Wind Speed Using Generative Adversarial Network: Experiments in the Southern China Sea - Xianci Wan; Baojian Liu; Zhizhou Guo; Zhenghuan Xia; Tao Zhang; Rui Ji; Wei Wan (Journal of Marine Science and Engineering, 2024)
This paper designed a Generative Adversarial Network (GAN)-based super-resolution framework for scatterometer ocean surface wind speed (OSWS) mapping. An improved GAN, WSGAN, was well-trained to generate high-resolution OSWS (~1/64 km) from low-resolution OSWS (~12.5 km) retrieved from scatterometer observations. The generator of GAN incorporated Synthetic Aperture Radar (SAR) information in the training phase. Therefore, the pre-trained model could reconstruct high-resolution OSWS with historical local spatial and texture information. The training experiments were executed in the South China Sea using the OSWS generated from the Advanced SCATterometer (ASCAT) scatterometer and Sentinel-1 SAR OSWS set. Several GAN-based methods were compared, and WSGAN performed the best in most sea states, enabling more detail mining with fewer checkerboard artifacts at a scale factor of eight. The model reaches an overall root mean square error (RMSE) of 0.81 m/s and an overall mean absolute error (MAE) of 0.68 m/s in the collocation region of ASCAT and Sentinel-1. The model also exhibits excellent generalization capability in another scatterometer with an overall RMSE of 1.11 m/s. This study benefits high-resolution OSWS users when no SAR observation is available.

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Emission characteristics of intermediate volatility organic compounds from a Chinese gasoline engine under varied operating conditions: Influence of fuel, velocity, torque, rotational speed, and after-treatment device - Rongzhi Tang; Song Guo; Kai Song; Ying Yu; Rui Tan; Hui Wang; Kefan Liu; Ruizhe Shen; Shiyi Chen; Limin Zeng; Zhou Zhang; Wenbin Zhang; et al. (Science of The Total Environment, 2024)

Forager-farmer transition at the crossroads of East and Southeast Asia 4900 years ago - Minmin Ma; Minxia Lu; Rui Sun; Zhonghua Zhu; Dorian Q. Fuller; Jianxin Guo; Guanglin He; Xiaomin Yang; Lingling Tan; Yongxiu Lu; Jiajia Dong; Ruiliang Liu; et al. (Science Bulletin, 2024)

Landscape differentiation of soil bacteria and bacteria-soil-vegetation interactions in desert-oasis ecosystems - Lijuan Chen; Changsheng Li; Zhishan Zhang; Qi Feng; Haiyang Xi; Rui Guo; Chengqi Zhang; Yuxi Wei (Global and Planetary Change, 2024)

Electrospinning is a potential way for preparing edible plant protein-based nanofibers with porous surface using safflower seed meal - Yanling Yang; Chuang Peng; Dong Zeng; Zhengjie Yang; Xiaohu Wang; Shuang Zhang; Yucheng Bai; Lujing Kuang; Lizhi Guo; Yonghua Qin; Hairong Xiong; Jiawei Wan; et al. (Food Hydrocolloids, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Mechanical analysis of toppling failure using FDEM: A case study for soft-hard interbedded anti-dip rock slope - Hui Guo; Chengzeng Yan; Guohua Zhang; Rui Xu; Tie Wang; Yu-Yong Jiao (Computers and Geotechnics, 2024)

Effects of salinity in food waste on the growth of black soldier fly larvae and global warming potential analysis - Rui Li; TianHui Lin; XiaoLei Fan; XiaoFeng Dai; JieHua Huang; YiFeng Zhang; RongBo Guo; ShanFei Fu (Chemical Engineering Journal, 2024)

Exosome as non-invasive prognostic and diagnostic biomarker and nanovesicle for targeted therapy of non-small cell lung carcinoma - Zhao Yang; Shi Fu; Yongchao Li; Youfeng Liang; Mingxuan Hao; Rui Guo; Changyuan Yu; Zahid Hussain; Jinku Zhang; Haifeng Wang (Chemical Engineering Journal, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Plasma membrane-localized hexose transporter OsSWEET1b, affects sugar metabolism and leaf senescence - Qiang Zhang; Changzhao Chen; Rui Guo; Xiaofang Zhu; Xinyu Tao; Mengxing He; Zhiwen Li; Lan Shen; Qing Li; Deyong Ren; Jiang Hu; Li Zhu; et al. (Plant Cell Reports, 2024)

Dietary supplementation with polysaccharides from Rhizoma dioscoreae resulting in the enhanced immunity and the structural modulation of the intestinal microbiota in Luciobarbus capito - Yuan Sun; Xiaowei Hu; Xianwei Meng; Rui Liu; Zhigang Zhao; Shihui Wang; Rui Zhang; Kun Guo; Liang Luo (Aquaculture, 2023)

Solutions on the periodic background and transition state mechanisms for the higher-order Chen–Lee–Liu equation - Jia-Xue Niu; Rui Guo; Jian-Wen Zhang (Wave Motion, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Efficient wastewater disinfection through FeOOH-mediated photo-Fenton reaction: A review - Chen Wang; Peng Shi; Zhaobo Wang; Rui Guo; Junhua You; Hangzhou Zhang (Journal of Environmental Chemical Engineering, 2023)

Shared and Distinct Topographic Alterations of Alpha-Range Resting EEG Activity in Schizophrenia, Bipolar Disorder, and Depression - Rui Xue; Xiaojing Li; Jianning Chen; Sugai Liang; Hua Yu; Yamin Zhang; Wei Wei; Yan Xu; Wei Deng; Wanjun Guo; Tao Li (Neuroscience Bulletin, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Single-cell transcriptome analysis revealing the intratumoral heterogeneity of ccRCC and validation of MT2A in pathogenesis - Jie Wang; Zili Zuo; Zongze Yu; Zhigui Chen; Xiangdi Meng; Zhaosen Ma; Jiqiang Niu; Rui Guo; Lisa Jia Tran; Jing Zhang; Tianxiao Jiang; Fangdie Ye; et al. (Functional & Integrative Genomics, 2023)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Heavy metal pollution alters reproductive performance and mate choice in an anuran, Strauchbufo raddei - Rui Su; Rui Guo; Zhenyu Liu; Yongna Yuan; Wenya Zhang (Marine Pollution Bulletin, 2023)

A new method for pre-enrichment of gallium and lithium based on mode of occurrence in coal gangue from Antaibao surface mine, Shanxi Province, China - Shiqi Dai; Fengshuai Sun; Lei Wang; Lanhao Wang; Rui Zhang; Han Guo; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2023)

Hydrophobic aggregation via partial Gal removal affects solution characteristics and fine structure of tamarind kernel polysaccharides - Rui Guo; Xianbao Sun; Yuxing Kou; Hong Song; Xujiao Li; Lihua Song; Taolei Zhao; Hui Zhang; Deshun Li; Yanfang Liu; Zibo Song; Jieli Wu; et al. (Food Hydrocolloids, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

What is affecting the improvement of green innovation efficiency in the old industrial base: evidence from Northeast China - Fuyou Guo; Mingxi Zhou; Ligeer De; Rui Li; Yu Zhang (Environmental Science and Pollution Research, 2023)

Optimizing the performance of Fe-based metal-organic frameworks in photo-Fenton processes: Mechanisms, strategies and prospects - Zhaobo Wang; Ying Cheng; Chen Wang; Rui Guo; Junhua You; Hangzhou Zhang (Chemosphere, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Boosting PFOA photocatalytic removal from water using highly adsorptive and sunlight-responsive ZIF67/MIL-100(Fe) modified C3N4 - Peidong Su; Chunhui Zhang; Yu Liu; Junke Zhang; Ridha Djellabi; Rui Wang; Junqiang Guo; Rui Zhang; Hongwei Guo; Xiang Ding; Xinyue Liu (Journal of Environmental Chemical Engineering, 2023)

Controllable solvent treatment of fluorinated graphite for high power density and low cathode swelling lithium primary batteries - Sen Ma; Wen Liu; Daoming Zhang; Cheng Yang; Ying Luo; Xiaobing Lou; Rui Guo; Yong Wang; Jingying Xie (Chemical Engineering Journal, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Effects of hypoxia on the gill morphological structure, apoptosis and hypoxia-related gene expression in blunt snout bream (Megalobrama amblycephala) - Xin-xin Yu; Yan-rui Zhang; Shan-shan Li; Guo-dong Zheng; Shu-ming Zou (Fish Physiology and Biochemistry, 2023)

Risk factors for thrombocytopenia in patients receiving linezolid therapy: a systematic review and meta-analysis - Dan Zhang; Yasi Xu; Xiang Wang; Leping Hou; Mengyu Xing; Shuang Xu; Rui Guo; Ying Luo (European Journal of Clinical Pharmacology, 2023)

Polarity-extended liquid chromatography-triple quadrupole mass spectrometry for simultaneous hydrophilic and hydrophobic metabolite analysis - Rui Guo; Qisheng Zhong; Jiaqi Liu; Peiming Bai; Zongpeng Wang; Jieling Kou; Peijie Chen; Jie Zhang; Bo Zhang (Analytica Chimica Acta, 2023)

Genome-wide analysis of long noncoding RNA profiles in pseudorabies-virus-infected PK15 cells - Jian-guo Dong; Ming-rui Chen; Dan Rao; Ning Zhang; Shuhai He; Lei Na (Archives of Virology, 2023)

From anaerobic digestion to single cell protein synthesis: A promising route beyond biogas utilization - Rui Li; XiaoLei Fan; YuFeng Jiang; RuoNan Wang; RongBo Guo; Yifeng Zhang; ShanFei Fu (Water Research, 2023)

Analyzing “economy-society-environment” sustainability from the perspective of urban spatial structure: A case study of the Yangtze River delta urban agglomeration - Hanyu Yin; Rui Xiao; Xufeng Fei; Zhonghao Zhang; Zhi Gao; Yi Wan; Wenfang Tan; Xucheng Jiang; Wei Cao; Yuxiang Guo (Sustainable Cities and Society, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Anaerobic selenite-reducing bacteria and their metabolic potentials in Se-rich sediment revealed by the combination of DNA-stable isotope probing, metagenomic binning, and metatranscriptomics - Rui Xu; Max Kolton; Wan Tao; Xiaoxu Sun; Pingzhou Su; Duanyi Huang; Miaomiao Zhang; Zhaohui Yang; Zhaohui Guo; Hanbing Gao; Qi Wang; Baoqin Li; et al. (Journal of Hazardous Materials, 2023)

Trehalose metabolism targeting as a novel strategy to modulate acid tolerance of yeasts and its application in food industry - Zhongpeng Guo; Moying Li; Zitao Guo; Rui Zhu; Yu Xin; Zhenghua Gu; Liang Zhang (Food Microbiology, 2023)

A reliable Bayesian neural network for the prediction of reservoir thickness with quantified uncertainty - Li-Li Bao; Jiang-She Zhang; Chun-Xia Zhang; Rui Guo; Xiao-Li Wei; Zi-Lu Jiang (Computers & Geosciences, 2023)

Controllable micro cross-linking towards multifunctional flame-retardant aliphatic polyamide - Qin Zhang; Guo-Rui Zhu; Xiang-Xin Xiao; Qing-Song Liu; Min Jiang; De-Ming Guo; Hai-Bo Zhao; Wen-Da Li; Li Chen; Bo-Wen Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Estimation of in-season nitrogen requirement for drip-irrigated spring maize without or with straw incorporation using critical nitrogen dilution curve - Ru Guo; Rui Qian; Muhammad Asad Naseer; Fei Han; Peng Zhang; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Plant and Soil, 2023)

Hepatoprotective effects of chlorogenic acid on mice exposed to aflatoxin B1: Modulation of oxidative stress and inflammation - Kang Cheng; Jingyi Niu; Jinyan Zhang; Yining Qiao; Guorun Dong; Rui Guo; Xiaotong Zheng; Zhihua Song; Jin Huang; Jinrong Wang; Yong Zhang (Toxicon, 2023)

Ferulic acid enhanced resistance against blue mold of Malus domestica by regulating reactive oxygen species and phenylpropanoid metabolism - Mi Guo; Canying Li; Rui Huang; Linhong Qu; Jiaxin Liu; Chenyang Zhang; Yonghong Ge (Postharvest Biology and Technology, 2023)

Sustainable network analysis and coordinated development simulation of urban agglomerations from multiple perspectives - Hanyu Yin; Zhonghao Zhang; Yi Wan; Zhi Gao; Yuxiang Guo; Rui Xiao (Journal of Cleaner Production, 2023)

Spatiotemporal clustering analysis of shared electric vehicles based on trajectory data for sustainable urban governance - Lewen Bao; Zonglin Liu; Rui Miao; Zhihua Chen; Bo Zhang; Peng Guo; Yuze Ma (Journal of Cleaner Production, 2023)

Effects of different water-cooled heat sinks on the cooling system performance in a data center - Wei He; Jifang Zhang; Hailong Li; Rui Guo; Shengchun Liu; Xiaohui Wu; Jie Wei; Yulin Wang (Energy and Buildings, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Prenatal bisphenol S exposure induces hepatic lipid deposition in male mice offspring through downregulation of adipose-derived exosomal miR-29a-3p - Rui Zhang; Jingyao Guo; Yupeng Wang; Rundong Sun; Guangzhu Dong; Xinru Wang; Guizhen Du (Journal of Hazardous Materials, 2023)

High-throughput calculation of organ-scale traits with reconstructed accurate 3D canopy structures using a UAV RGB camera with an advanced cross-circling oblique route - Shunfu Xiao; Yulu Ye; Shuaipeng Fei; Haochong Chen; Bingyu zhang; Qing li; Zhibo Cai; Yingpu Che; Qing Wang; AbuZar Ghafoor; Kaiyi Bi; Ke Shao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Intraspecific variations of adaptive strategies of native and invasive plant species along an elevational gradient - Hasigerili; Kun Guo; Miao-Miao Zheng; Rui-Ling Liu; Yan-Yan Wang; Yuan Gao; Li Shu; Xiao-Ran Wang; Jian Zhang; Wen-Yong Guo (Flora, 2023)

Insights into dissolved organics in non-urban areas - Optical properties and sources - Feng Yu; Xiaofei Li; Rui Zhang; Jingning Guo; Wen Yang; Lekhendra Tripathee; Lang Liu; Yuqin Wang; Shichang Kang; Junji Cao (Environmental Pollution, 2023)

ROS and DRP1 interactions accelerate the mitochondrial injury induced by polystyrene nanoplastics in human liver HepG2 cells - Yunjing Li; Menghao Guo; Shuyan Niu; Mengting Shang; Xiaoru Chang; Zuoyi Sun; Rui Zhang; Xin Shen; Yuying Xue (Chemico-Biological Interactions, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Scale optimization of urban agglomerations based on the connection strength between cities under the framework of sustainable development - Qingxiang Meng; Zhonghao Zhang; Xufeng Fei; Yuxiang Guo; Rui Xiao (Environment, Development and Sustainability, 2023)

Characteristics of drought, low temperature, and concurrent events of maize in Songliao Plain - Yunmeng Zhao; Ying Guo; Rui Wang; Kaiwei Li; Guangzhi Rong; Jiquan Zhang; Chunli Zhao (International Journal of Climatology, 2023)
Maize is susceptible to drought and low temperatures. In recent years, drought, low temperatures, and their composite events have often occurred during the growth period of maize, causing a huge impact. In this study, maize in the Songliao Plain was used as the research object. Based on the crop water surplus deficit index (CWSDI) and heat index (F(T)), combined with the Theil–Sen median and Mann–Kendall tests (Sen–MK) and empirical orthogonal function (EOF), the temporal trends and spatial patterns of drought and low temperatures in different growth periods of maize were obtained. Copula modelling was used to analyse the joint probability distribution and return period of drought and low temperatures. The results showed that the temporal variation trend of the CWSDI was significantly different at different growth periods of maize, and there were different trends and spatial modal distributions. However, the temporal variation trend of F(T) was similar, showing a downward trend over the entire region. There was no obvious asymmetry or skew‐dependent structure in the distribution of concurrent events of drought and low temperature; however, the joint probability contours of different growth periods were biased to the upper left. The recurrence period of drought and low‐temperature concurrent events was within 2 years, and the recurrence period was basically between 2 and 5 years, with a reduction in drought or low temperatures.

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

Simultaneously mapping loci related to two plant architecture traits by phenotypic recombination BSA/BSR in peanut (Arachis hypogaea L.) - Xiaona Yu; Yaoyao Li; Xinyuan Cui; Xianheng Wang; Jihua Li; Rui Guo; Fanzhuang Yan; Shaojing Zhang; Ruihua Zhao; Danlei Song; Tong Si; Xiaoxia Zou; et al. (Theoretical and Applied Genetics, 2023)

Enhanced biological stabilization of metal-chelant complexes in the chelator-washed soils by sulfate-reducing bacteria - Guixiang Zhang; Yu Gao; Rui Ren; Xiaofang Guo; Baoshan Xing; Yang Li; Zheyun Zhang; Hao Wu (Journal of Soils and Sediments, 2023)

Causal associations of circulating Helicobacter pylori antibodies with stroke and the mediating role of inflammation - Xingzhi Guo; Peng Tang; Xin Zhang; Rui Li (Inflammation Research, 2023)

Genome-Wide Identification and Expression Analysis of the CAD Gene Family in Walnut (Juglans regia L.) - Pengyu Wu; Rui Zhang; Shangqi Yu; Jiazhi Fu; Zhongzhong Guo; Dong Li; Zhiyong Pan; Haifang Hu (Biochemical Genetics, 2023)

Geographic variation of litter chemistry and palatability in an invasive plant versus its native competitor - Yaolin Guo; Youzheng Zhang; Jihua Wu; Christina L. Richards; Oliver Bossdorf; Bo Li; Rui‐Ting Ju (Journal of Biogeography, 2023)
Aim Latitudinal variation in biotic interactions is recognized as a driver underlying variation in plant invasion success and therefore an important issue in conservation biogeography. However, previous studies have mainly focused on interactions between living plants and herbivores, whereas litter traits and detritivory have been hardly studied along latitude or compared between native and invasive plants. Our aim was to compare latitudinal variation in leaf litter chemistry and palatability to detritivores between invasive and native plants, and investigate which chemical traits determine detritivory and whether they are climate‐driven. Location China. Taxa Spartina alterniflora , Phragmites australis , Porcellio laevis , Chiromantes dehaani . Methods We combined field surveys with laboratory experiments to compare latitudinal variation in litter chemistry between the widespread invasive Spartina alterniflora and its native competitor Phragmites australis across their co‐occurring range (20.9–40.7° N, ~2200 km). For both species, we examined litter palatability to two common detritivores ( Porcellio laevis and Chiromantes dehaani ) along the same latitude. We also analysed relationships among climate, litter traits and detritivory. Results In five of nine litter traits, we found latitudinal clines, with little difference between the two plant species in how they responded across the gradient. Litter palatability decreased with increasing latitude, but was generally higher in Spartina than Phragmites . Two key litter traits (C:P ratio and flavonoid content) were significantly associated with temperature of origin and with detritivory. Main Conclusions There were geographic clines in litter traits and palatability, with strong links between climate, litter chemistry and detritivory, in both Spartina and Phragmites . Spartina litter, however, was more rapidly decomposed by detritivores, which could create positive feedbacks, and contributes to the successful Spartina invasion along China's coast. Future ecological restoration projects should therefore dispose Spartina plant tissue or litter off‐site, to reduce the competitiveness of Spartina and support the conservation of native Phragmites .

Effects of saline-alkali stress on the tissue structure, antioxidation, immunocompetence and metabolomics of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Science of The Total Environment, 2023)

Theoretical study the electrocatalytic performance and mechanism of novel designed electrocatalyst Ru@2DMs for CO2RR - Linxia Cui; Ke Shi; Mingyuan Zhang; Jiuwen Guo; Zhe Yan; Haigang Hao; Rui Gao (Fuel, 2023)

Anti-hardening effect and mechanism of silkworm sericin peptide in high protein nutrition bars during early storage - Hongtao Zhu; Xiu-Xiu Zhang; Rui Zhang; Jing-Yu Feng; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Long-term straw incorporation regulates greenhouse gas emissions from biodegradable film farmland, improves ecosystem carbon budget and sustainable maize productivity - Rui Qian; Ru Guo; Muhammad Asad Naseer; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Field Crops Research, 2023)

Te-doped NiFe2O4 stabilized by amorphous carbon layers derived from one-step topological transitions of NiFe LDHs with significantly enhanced oxygen evolution reaction - Yanyan Li; Haoran Guo; Jiayang Zhao; Yao Zhang; Liyun Zhao; Rui Song (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

A corrected p-y curve model for large-diameter pile foundation of offshore wind turbine - Xiao-ling Zhang; Rui Zhou; Guo-liang Zhang; Yan Han (Ocean Engineering, 2023)

Efficient removal of Cr(VI) by the modified biochar with chitosan schiff base and MnFe2O4 nanoparticles: Adsorption and mechanism analysis - Ling Yan; Weijuan Guo; Binbin Huang; Yujun Chen; Xinyu Ren; Yiyang Shen; Yefeng Zhou; Rui Cheng; Jie Zhang; Muqing Qiu; Baowei Hu (Journal of Environmental Chemical Engineering, 2023)

Highly reactive coke made from Low-rank Coal: Relationship between thermal properties and multilevel structure - Xin Zhang; Jun Zhang; Rui Guo; Qiang Xiao; Yawei Feng; Huan Cheng (Fuel, 2023)

The interaction mechanism and the functionality of yeast protein with hydrophilic and hydrophobic bioactive molecules - Haili Sun; Yifei Sun; Xin Tang; Yuanmeng Cui; Demei Meng; Yuyu Zhang; Ku Li; Hui Guo; Hai Chen; Rui Yang (Food Bioscience, 2023)

Managing iodine and tin based defects for efficient and stable mixed Sn-Pb perovskite solar cells - Yanjun Xing; Zhiqiang Deng; Tonghui Guo; Zequn Zhang; Qidong Tai; Rui Zhao; Jiaxing Xiong; Qiuxiang Wang; Like Huang; Xiaohui Liu; Ziyang Hu; Yuejin Zhu; et al. (Chemical Engineering Journal, 2023)

Boosting photocatalytic ammonia synthesis performance over OVs-Rich Ru/W18O49: Insights into the roles of oxygen vacancies in enhanced hydrogen spillover effect - Lulu Zhang; Rui Li; Luyao Cui; Zijun Sun; Lijun Guo; Xiaochao Zhang; Yunfang Wang; Yawen Wang; Zhuobin Yu; Tao Lei; Xuan Jian; Xiaoming Gao; et al. (Chemical Engineering Journal, 2023)

A novel solvent system of polyamides achieves new application in ZIBs by aggregation induced Lewis acid-base centers - Murong Xi; Zhenjie Liu; Rui Sheng; Jiafeng Zhu; Yong Guo; Juan Ding; Xingchao Wang; Yue Zhang; Lei Wang; Zhipeng Sun; Wenjun Zhang; Jiulin Wang; et al. (Chemical Engineering Journal, 2023)

Interaction Between the Glymphatic System and α-Synuclein in Parkinson’s Disease - Yu Zhang; Cui Zhang; Xu-Zhong He; Zhen-Hua Li; Jing-Cai Meng; Rui-Ting Mao; Xin Li; Rong Xue; Qian Gui; Guo-Xing Zhang; Lin-Hui Wang (Molecular Neurobiology, 2023)

A model description of beta oscillations in the external globus pallidus - Mingming Chen; Yajie Zhu; Rui Zhang; Renping Yu; Yuxia Hu; Hong Wan; Dezhong Yao; Daqing Guo (Cognitive Neurodynamics, 2023)

Fast and visual detection of nucleic acids using a one-step RPA-CRISPR detection (ORCD) system unrestricted by the PAM - Kangfeng Lin; Jianguang Guo; Xiangju Guo; Qinghan Li; Xiao Li; Zhen Sun; Zehang Zhao; Jiao Weng; Jinzhun Wu; Rui Zhang; Boan Li (Analytica Chimica Acta, 2023)

Quantify the effect of manure fertilizer addition and optimal nitrogen input on rainfed wheat yield and nitrogen requirement using nitrogen nutrition index - Pengzhao Liu; Xingyu Guo; Dong Zhou; Qi Zhang; Xiaolong Ren; Rui Wang; Xiaoli Wang; Xiaoli Chen; Jun Li (Agriculture, Ecosystems & Environment, 2023)

Morphological alterations in C57BL/6 mouse intestinal organoids as a tool for predicting chemical-induced toxicity - Ziwei Wang; Shen Chen; Yaqin Pang; Lizhu Ye; Qi Zhang; Xinhang Jiang; Rui Zhang; Miao Li; Zhanyu Guo; Yue Jiang; Daochuan Li; Xiumei Xing; et al. (Archives of Toxicology, 2023)

Transcriptomic analysis of juvenile cobia in response to hypoxic stress - Jian-Sheng Huang; Zhi-Xiong Guo; Jian-Dong Zhang; Wei-Zheng Wang; Zhong-Liang Wang; Rui-Tao Xie; Eric Amenyogbe; Gang Chen (Aquaculture International, 2023)

Particle sorting to improve the removal of fluoride and aluminum nitride from secondary aluminum dross by roasting - Huimin Xie; Zhaohui Guo; Rui Xu; Yanglin Zhang (Environmental Science and Pollution Research, 2023)

A novel method of imposing external water pressure to explore the failure behavior of railway tunnel linings - Ben-Guo He; Rui-Hua Xue; Zhi-Qiang Zhang; Xia-Ting Feng; Chuan Wu (Tunnelling and Underground Space Technology, 2023)

GSK2795039 prevents RIP1-RIP3-MLKL-mediated cardiomyocyte necroptosis in doxorubicin-induced heart failure through inhibition of NADPH oxidase-derived oxidative stress - Xiao-Juan Zhang; Lu Li; Ai-Ling Wang; Hong-Xia Guo; Hui-Ping Zhao; Rui-Fang Chi; Hui-Yu Xu; Li-Guo Yang; Bao Li; Fu-Zhong Qin; Jia-Pu Wang (Toxicology and Applied Pharmacology, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Genome-wide identification and expression analysis of the cotton patatin-related phospholipase A genes and response to stress tolerance - Yunxiao Wei; Zhili Chong; Chao Lu; Kaili Li; Chengzhen Liang; Zhigang Meng; Yuan Wang; Sandui Guo; Liangrong He; Rui Zhang (Planta, 2023)

A chitin synthase mutation confers widespread resistance to buprofezin, a chitin synthesis inhibitor, in the brown planthopper, Nilaparvata lugens - Bin Zeng; Fu-Rong Chen; Ya-Ting Liu; Di Guo; Yi-Jie Zhang; Ze-Rui Feng; Li-Xiang Wang; John Vontas; Shun-Fan Wu; Kun Yan Zhu; Cong-Fen Gao (Journal of Pest Science, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Chaofan Guo; Xin Liu; Xiaojing Liao; Haimei Wu; Zhaorui Zhang; Dehua Wu; Rui Ma; Yongshun Huang; Na Zhao; Yongmei Xiao; Qifei Deng (Environmental Pollution, 2023)

Redox of anionic and cationic radical intermediates in a bipolar polyimide COF for high-performance dual-ion organic batteries - Shuai Gu; Jingjing Chen; Rui Hao; Xi Chen; Zhiqiang Wang; Iftikhar Hussain; Guiyu Liu; Kun Liu; Qingmeng Gan; Zhiqiang Li; Hao Guo; Yingzhi Li; et al. (Chemical Engineering Journal, 2023)

Inhibition of ice recrystallization by tamarind (Tamarindus indica L.) seed polysaccharide and molecular weight effects - Xianbao Sun; Rui Guo; Yuxing Kou; Hong Song; Taijie Zhan; Jinhong Wu; Lihua Song; Hui Zhang; Fan Xie; Jiangmei Wang; Zibo Song; Yan Wu (Carbohydrate Polymers, 2023)

Territorial function differentiation and its comprehensive regionalization in China - Jie Fan; Kan Zhou; Kerong Sheng; Rui Guo; Dong Chen; Yafei Wang; Hanchu Liu; Zheng Wang; Yong Sun; Jie Zhang; Jianxiong Wu; Hao Zhao (Science China Earth Sciences, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Immune and intestinal microbiota responses to heat stress in Chinese mitten crab (Eriocheir sinensis) - Zhiqiang Li; Zhigang Zhao; Liang Luo; Shihui Wang; Rui Zhang; Kun Guo; Yuhong Yang (Aquaculture, 2023)

Secondary organic aerosol formation in China from urban-lifestyle sources: Vehicle exhaust and cooking emission - Zirui Zhang; Wenfei Zhu; Min Hu; Hui Wang; Lizi Tang; Shuya Hu; Ruizhe Shen; Ying Yu; Kai Song; Rui Tan; Zheng Chen; Shiyi Chen; et al. (Science of The Total Environment, 2023)

Contamination vertical distribution and key factors identification of metal(loid)s in site soil from an abandoned Pb/Zn smelter using machine learning - Zhaohui Guo; Yunxia Zhang; Rui Xu; Huimin Xie; Xiyuan Xiao; Chi Peng (Science of The Total Environment, 2023)

Competitive control of multiscale aquifer heterogeneity on solute transport in an alluvial aquifer - Maosheng Yin; Rui Ma; Yong Zhang; Jingjing Lin; Zhilin Guo; Chunmiao Zheng (Journal of Hydrology, 2023)

Selective detection of trace carbon monoxide at room temperature based on CuO nanosheets exposed to (111) crystal facets - Yuanyuan Wu; Ji Li; Mingsong Lv; Xianfa Zhang; Rui Gao; Chuanyu Guo; Xiaoli Cheng; Xin Zhou; Yingming Xu; Shan Gao; Zoltán Major; Lihua Huo (Journal of Hazardous Materials, 2023)

Lead-chlorine synergistic immobilization mechanism in municipal solid waste incineration fly ash (MSWIFA)-based magnesium potassium phosphate cement - Xing Cao; Qiushi Zhang; Weichen Yang; Lin Fang; Shiwei Liu; Rui Ma; Kai Guo; Ning Ma (Journal of Hazardous Materials, 2023)

Influence of size effect on the properties of slag and waste glass-based geopolymer paste - Xi Jiang; Yiyuan Zhang; Yao Zhang; Jianmin Ma; Rui Xiao; Fengdi Guo; Yun Bai; Baoshan Huang (Journal of Cleaner Production, 2023)

Studies on the interaction between homological proteins and anthocyanins from purple sweet potato (PSP): Structural characterization, binding mechanism and stability - Rui Zhang; Shuxin Ye; Ying Guo; Muci Wu; Sijia Jiang; Jingren He (Food Chemistry, 2023)

An experimental investigation on the effect of soluble sugar degradation on the of domestic-source-contaminated soil sites formation and evolution - Yuliang Guo; Liwen Cao; Shuxun Sang; Rui Zhang (Environmental Pollution, 2023)

Metabolomics analysis reveals the response mechanism to carbonate alkalinity toxicity in the gills of Eriocheir sinensis - Rui Zhang; Zhigang Zhao; Mingshuai Li; Liang Luo; Shihui Wang; Kun Guo; Wei Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Shape-controlled synthesis of Pd nanotetrahedrons with Pt-doped surfaces for highly efficient electrocatalytic oxygen reduction and formic acid oxidation - Liuxuan Luo; Zehao Tan; Cehuang Fu; Rui Xue; Xiaojing Cheng; Tianzi Bi; Lutian Zhao; Yangge Guo; Xiyang Cai; Jiewei Yin; Shuiyun Shen; Junliang Zhang (Chemical Engineering Journal, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

More intelligent and efficient thermal environment management: A hybrid model for occupant-centric thermal comfort monitoring in vehicle cabins - Xinglei He; Xiaohan Zhang; Rui Zhang; Jiaxin Liu; Xiaoyu Huang; Jinchen Pei; Jingyang Cai; Fen Guo; Yichun Wang (Building and Environment, 2023)

Water-soluble brown carbon in PM2.5 at two typical sites in Guanzhong Basin: Optical properties, sources, and implications - Xiaofei Li; Feng Yu; Yiying Song; Chao Zhang; Fangping Yan; Zhaofu Hu; Yali Lei; Lekhendra Tripathee; Rui Zhang; Jingning Guo; Yuqin Wang; Qingcai Chen; et al. (Atmospheric Research, 2023)

The draft genome sequence and characterization of Exserohilum rostratum, a new causal agent of maize leaf spot disease in Chinese Mainland - Qingzhou Ma; Chongyang Cheng; Yuehua Geng; Rui Zang; Yashuang Guo; Lixin Yan; Chao Xu; Meng Zhang; Haiyan Wu (European Journal of Plant Pathology, 2023)

Spatial distribution and quantitative source identification of nutrients and beneficial elements in the soil of a typical suburban area, Beijing - Qin-Rui Zhang; Sheng-Qiang Zhang; Yong Huang; Huan Li; Yan-Hui Jia; Jun Li; Guo-Li Yuan (Environmental Monitoring and Assessment, 2023)

Development, characterisation, and in vitro anti-tumor effect of self-microemulsifying drug delivery system containing polyphyllin I - Xin Wang; Rui Zhang; Shu Wang; Minju Gu; Yuan Li; Xiuping Zhuang; Chao Chen; Peimin Yang; Gongling Guo; Ping Sun (Drug Delivery and Translational Research, 2023)

Selenite Ameliorates Cadmium-induced Cytotoxicity Through Downregulation of ROS Levels and Upregulation of Selenoprotein Thioredoxin Reductase 1 in SH-SY5Y Cells - Hecheng Wang; Shibo Sun; Yan Ren; Rui Yang; Jianli Guo; Yu Zong; Qiuxian Zhang; Jing Zhao; Wei Zhang; Weiping Xu; Shui Guan; Jianqiang Xu (Biological Trace Element Research, 2023)

Evaluating the effects of contact time and leaching solution on measured solubilities of aerosol trace metals - Rui Li; Shuwei Dong; Chengpeng Huang; Feng Yu; Fu Wang; Xiaofei Li; Huanhuan Zhang; Yan Ren; Mingxian Guo; Qingcai Chen; Baozhu Ge; Mingjin Tang (Applied Geochemistry, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Xanthophyll cycle-related non-photochemical quenching protects Sargassum thunbergii from high light-induced photoinhibition - Guo-Ning Nan; Xiao-Qun Zhou; Xiu-Mei Zhang; Quan-Sheng Zhang; Zi-Min Hu; Rui-Ping Huang; Di Zhang (Frontiers in Marine Science, 2022)
As a common macroalga living in the intertidal zone, Sargassum thunbergii (Sargassaceae, Phaeophyta) is often exposed to drastic changes in solar photosynthetically active radiation during a diurnal cycle; thus, the potential photosynthetic adaptation processes deserve attention. In this work, we examined the photosynthetic performance and xanthophyll cycle activity of this alga in response to high light (1,200 μmol photons m –2 s –1 , the average in-situ light intensity at noon) by using chlorophyll fluorescence and high-performance liquid chromatography (HPLC). On exposure to high light, a rapid decrease in the effective quantum yield of photosystem II (PSII) (Y(II)) occurred, indicating down-regulation of PSII activity; a corresponding increase in non-photochemical quenching (NPQ) indicated the existence of energy-dissipating cycles. After turning off the light, Y(II) gradually increased to 0.7, accompanied by a decrease in NPQ. However, no complete recovery of NPQ was observed, and its value remained at ≈4, even after an 80-min dark treatment. The size of the xanthophyll cycle pigments pool was quantified using HPLC and was found to be ≈16 mol mol −1 Chl a × 100. The activity of the xanthophyll cycle, characterized by a de-epoxidation state (DPS), could reach up to ≈0.5. Such a large pigments pool and rapid accumulation of zeaxanthin may allow S. thunbergii to induce high values of NPQ (≈10). These results were further complemented by inhibitor (dithiothreitol, DTT) and pre-illumination experiments showing that (1) both NPQ and the xanthophyll cycle could be inhibited by DTT, and there was always a strong positive correlation between NPQ and DPS; (2) the previously formed antheraxanthin exhibited a long retention time and a slow epoxidation; and (3) the long retention of antheraxanthin contributed to a rapid accumulation of zeaxanthin. In conclusion, our present study demonstrated that xanthophyll cycle-induced NPQ can significantly protect S. thunbergii from light fluctuations in the intertidal zone.

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

Numerical simulation of rock breaking by TBM disc cutter in soil-rock composite formations - Qing Yu; Xiaohong He; Haoyu Miao; Minghua Lin; Kaixiang Zhang; Rui Guo (Bulletin of Engineering Geology and the Environment, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Wave Motion and Seabed Response around a Vertical Structure Sheltered by Submerged Breakwaters with Fabry–Pérot Resonance - Lai Jiang; Jisheng Zhang; Linlong Tong; Yakun Guo; Rui He; Ke Sun (Journal of Marine Science and Engineering, 2022)
This paper presents the results from a numerical simulation study to investigate wave trapping by a series of trapezoidal porous submerged breakwaters near a vertical breakwater, as well as the seabed response around the vertical breakwater. An integrated model, based on the volume-averaged Reynolds-averaged Navier–Stokes (VARANS) equations is developed to simulate the flow field, while the dynamic Biot’s equations are used for simulating the wave-induced seabed response. The reflection of the wave energy over the submerged breakwaters, caused by the vertical breakwater, can be reserved, indicating that the existence of the submerged breakwaters in the front of the vertical breakwater can either provide shelter or worsen the hazards to the vertical breakwater. Numerical examples show two different modes under the Fabry–Pérot (F–P) resonance condition of the wave transformation, namely the wave reflection (Mode 1) and the wave trapping (Mode 2). The distance between the submerged breakwaters and the vertical breakwater, is a key parameter dominating the local hydrodynamic process and the resultant dynamic stresses around the vertical breakwater. The numerical results indicated that more submerged breakwaters and a higher porosity of submerged breakwaters will obviously dissipate more wave energy, and hence induce a smaller wave force on the rear vertical breakwater and liquefaction area around the vertical breakwater.

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

The structure and subduction relicts of the Changchun–Yanji suture, NE China: new evidence from deep seismic reflection profiling - Jiaduo Zhang; Hesheng Hou; Jianbo Zhou; Wei Fu; Rui Guo; Zongdong Pan; Hengcheng Ying (International Journal of Earth Sciences, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Human Urine-Derived Stem Cells Improve Partial Bladder Outlet Obstruction in Rats: Preliminary Data and microRNA-mRNA Expression Profile - Menjiang Tu; Rui Wang; Pei Zhu; Qingqing Wang; Bishao Sun; Keshi Lu; Jiawei Zhang; Weijie Xie; Huan Guo; Shulin Li; Yuqi Wu; Xiangwei Wang (Stem Cell Reviews and Reports, 2022)
Partial bladder outlet obstruction (pBOO) often results in bladder tissue inflammation and remodeling. As human urine-derived stem cells (USCs) have demonstrated therapeutic benefits, we used a rat model to investigate the effect of USCs on bladder function and explore the miRNA and gene expression profiles in bladder tissue using RNA sequencing. Eighteen rats were assigned to a sham surgery group, pBOO group, and pBOO+USC group (six biweekly treatments). Routine urodynamic monitoring, analysis of detrusor muscle strips, and pathophysiology assessments were conducted. Finally, altered miRNA and mRNA expression profiles of bladder tissue were examined using RNA sequencing and bioinformatics analysis. After USC treatment, elevated bladder compliance and maximal voiding pressure, declined end filling pressure and voided volume, and improved detrusor muscle contractility and carbachol sensitivity were found. Histology and TUNEL assay revealed reduced collagen deposition and muscle cell apoptosis in bladder tissue. The differential expression of eight miRNAs was reversed by USC treatment. Two large nodes (miR-142 and miR-9a) were identified in the miRNA-gene interaction network in the USC-treated group. The Kyoto Encyclopedia of Genes and Genomes analysis revealed enrichment of multiple significant pathways, including those involved in necroptosis and cytokine-cytokine receptor interactions. This is the first study to demonstrate the protective effect of USCs on bladder function and remodeling in pBOO rats. The miRNA and mRNA expression levels differed in the bladder of pBOO rats with and without USC treatment. Although the mechanism underlying these effects has not been fully elucidated, necroptosis and cytokine-cytokine receptor interaction-related pathways may be involved. Graphical abstract

Nutrient Reabsorption Mechanism Adapted to Low Phosphorus in Wild and Cultivated Soybean Varieties - Wenyue Shen; Rui Guo; Yaxuan Zhao; Danping Liu; Jing Chen; Ningning Miao; Shujuan Gao; Tao Zhang; Lianxuan Shi (Journal of Plant Growth Regulation, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Combined Effects of Eco-Substrate and Carbon Addition on Water Quality, Fish Performance and Nutrient Budgets in the Pond Polyculture System - Kun Guo; Zhigang Zhao; Jun Xie; Liang Luo; Shihui Wang; Rui Zhang; Wei Xu; Xiaoli Huang (Fishes, 2022)
Traditional aquaculture can cause serious environmental pollution. Biofilm and biofloc technology have the potential to limit aquaculture pollution. An outdoor experiment was conducted to evaluate the combined effects of eco-substrates and carbon addition on water quality, fish performance and nutrient budgets in the pond polyculture system. In the treatment group, the total ammonia nitrogen, nitrate nitrogen, nitrite nitrogen, and total nitrogen of the water were significantly lower compared to the control group (p 92%) and P (>95%) input during the experiment. Comprehensive accumulation was the main N (>58%) and P (>69%) output. The N and P feed input and comprehensive accumulation output declined in the treatment group. The N utilization efficiency in the experimental group increased slightly (p > 0.05), while the P utilization efficiency in the experimental group was significantly higher compared to the control (p

Effects of Alkalinity on the Antioxidant Capacity, Nonspecific Immune Response and Tissue Structure of Chinese Mitten Crab Eriocheir sinensis - Mingshuai Li; Shihui Wang; Zhigang Zhao; Liang Luo; Rui Zhang; Kun Guo; Lanlan Zhang; Yuhong Yang (Fishes, 2022)
The effects of various levels of alkalinity stress (0, 18.25, 35.41, 52.53 and 69.74 mmol/L) in Chinese mitten crab (Eriocheir sinensis) were investigated by means of measuring hepatopancreas antioxidant system and serum nonspecific immune system-related indices at 0, 12, 24, 48 and 96 h, hepatopancreas tissue structure at 96 h. The activities of superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and aspartate aminotransferase (AST) in each concentration group generally showed a trend of a first increasing and then decreasing during the 96-h stress process (p 0.05). The activities of CAT, GSH and AST in all treatment reached peak values at 24–48 h. At 96 h of alkalinity stress, the activities of GSH, alanine aminotransferase (ALT), acid phosphatise (ACP) and alkaline phosphatise (AKP) in the 18.25 mmol/L group were not significantly different with the control group (p > 0.05). The activities of SOD and CAT in the 52.53 and 69.74 mmol/L treatment were significantly lower than those in the control group (p

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

LncRNA SNHG14 is beneficial to oxygen glucose deprivation/reoxygenation-induced neuro-2a cell injury via mir-98-5p sequestration-caused BCL2L13 upregulation - Gaolian Zhang; Jianhui Guo; Jing Zeng; Xiaoning Zhang; Rui Chen; Gang Wang; Weibin Liang (Metabolic Brain Disease, 2022)

RNAi-Based Transcriptome Suggests Candidate Genes Regulated by ZxNHX1 to Affect The Salt Tolerance of Zygophyllum xanthoxylum - Hai-Shuang Liu; Xiao-Nong Guo; Wei-Wei Chai; Rui-Xin Zhang; Pei-Qin Li; Cui-Min Ma; Qing Ma; Suo-Min Wang (Journal of Plant Growth Regulation, 2022)

A novel therapeutic strategy for atherosclerosis: autophagy-dependent cholesterol efflux - Haipeng Guo; Dongmei Wei; Rui Liu; Chao Zhang; Song Jiang; Weijia Wang; Hongzhe Hu; Lijuan Shen; Xiaofei Liang (Journal of Physiology and Biochemistry, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Population Genetic Diversity and Differentiation of Mitten Crab, Genus Eriocheir, Based on Microsatellite Markers - Shihui Wang; Liang Luo; Rui Zhang; Kun Guo; Wei Xu; Zhigang Zhao (Fishes, 2022)
Mitten crab, Eriocheir sensu stricto, is an important indigenous aquatic species and food source in Eastern Asia. Genetic diversity is an important prerequisite for the conservation and utilization of germplasm resources. However, the genetic diversity and differentiation of Eriocheir s. s. remains unclear. This study evaluated population genetic diversity and genetic differentiation of three Eriocheir s. s. populations from Suifenhe (SFH), Liaohe (LH), and Nanliujiang (NLJ), China, based on 19 microsatellite markers. The mean observed number of alleles (Na) was 22.84 alleles, and the mean polymorphism information content (PIC) was 0.86, which demonstrated high genetic diversity. The allele frequency distribution showed an “L” shape, ranging from 0.01 to 0.74. The genetic diversity parameter values of the LH population were higher than those of the other two populations. All pairwise FST values showed significant differences among the three Eriocheir s. s. populations (p

RIG-I acts as a tumor suppressor in melanoma via regulating the activation of the MKK/p38MAPK signaling pathway - Rui Guo; Shun-Yuan Lu; Jin-Xia Ma; Qian-Lan Wang; Lu Zhang; Ling-Yun Tang; Yan Shen; Chun-Ling Shen; Jin-Jin Wang; Li-Ming Lu; Zhu-Gang Wang; Hong-Xin Zhang (Human Cell, 2022)
Studies have indicated that RIG-I may act as a tumor suppressor and participate in the tumorigenesis of some malignant diseases. However, RIG-I induces distinct cellular responses via different downstream signaling pathways depending on the cell type. To investigate the biological function and underlying molecular mechanism of RIG-I in the tumorigenesis of melanoma, we constructed RIG-I knockout, RIG-I -overexpressing B16-F10 and RIG-I knockdown A375 melanoma cell lines, and analyzed the RIG-I-mediated change in the biological behavior of tumor cells in spontaneous and poly (I:C)-induced RIG-I activation. Cell proliferation, cell cycling, apoptosis and migration were detected by CCK-8 assay, BrdU incorporation assay, Annexin V–PI staining assay and Transwell assay, respectively. In vivo tumorigenicity was evaluated by tumor xenograft growth in nude mice and subsequently by Ki67 staining and TUNEL assays. Furthermore, Western blotting was utilized to explore the underlying mechanism of RIG-I in melanoma cells. Our data showed that RIG-I promotes apoptosis and inhibits proliferation by G1 phase cell cycle arrest in the melanoma cell lines. Mechanistically, RIG-I induced the phosphorylation of p38 MAPK and MAPK kinases MKK3 and MKK4. In conclusion, the current study demonstrated that RIG-I suppressed the development of melanoma by regulating the activity of the MKK/p38 MAPK signaling pathway, which is relevant to research on novel therapeutic targets for this malignant disease.

Assessing residual motor function in patients with disorders of consciousness by brain network properties of task-state EEG - Lipeng Zhang; Rui Zhang; Yongkun Guo; Dexiao Zhao; Shizheng Li; Mingming Chen; Li Shi; Dezhong Yao; Jinfeng Gao; Xinjun Wang; Yuxia Hu (Cognitive Neurodynamics, 2022)

Effects of dietary protein concentration on growth and anti-oxidant capacity of coho salmon Oncorhynchus kisutch (Walbaum, 1792) alevins - Cong-mei Xu; Hai-rui Yu; Qin Zhang; Ling-yao Li; Jing-jing Fan; Meng-jie Guo; Fang-hui Li; Xiang-yi Qiu; Ling-ling Shan (Aquaculture International, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Laboratory and centrifugal model tests on failure mechanism of canal slopes under cyclic action of wetting–drying - Rui Zhu; Ying-hao Huang; Chen Zhang; Wan-li Guo; Hao Chen (European Journal of Environmental and Civil Engineering, 2022)

Antibiotic resistomes in water supply reservoirs sediments of central China: main biotic drivers and distribution pattern - Kai Zhang; Kuangjia Li; Rui Xin; Ya Han; Ziwei Guo; Wei Zou; Wei Wei; Xiangchao Cui; Zhongshuai Zhang; Ying Zhang (Environmental Science and Pollution Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Glyphosate-induced GhAG2 is involved in resistance to salt stress in cotton - Wancong Yu; Zhaohui Xue; Xianzheng Zhao; Rui Zhang; Jiping Liu; Sandui Guo (Plant Cell Reports, 2022)

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Study on excavation stability of shallow rectangular shield pipe jacking tunnel - Wantao Ding; Zhongrong Wang; Xinghang Huang; Rui Chen; Lewen Zhang; Yingjie Zheng; Xiaowei Guo (Arabian Journal of Geosciences, 2022)

Development of sustainable self-compacting concrete using recycled concrete aggregate and fly ash, slag, silica fume - Zhanggen Guo; Jing Zhang; Tao Jiang; Tianxun Jiang; Chen Chen; Rui Bo; Yan Sun (European Journal of Environmental and Civil Engineering, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

A two-phase comprehensive NSCLC prognostic study identifies lncRNAs with significant main effect and interaction - Jing Zhu; Jinxing Guan; Xinyu Ji; Yunjie Song; Xiaoshuang Xu; Qianqian Wang; Quanan Zhang; Renhua Guo; Rui Wang; Ruyang Zhang (Molecular Genetics and Genomics, 2022)
Long noncoding RNA (lncRNA) are involved in regulating physiological behaviors for various malignant tumors, including non-small-cell lung cancer (NSCLC). However, few studies comprehensively evaluated both lncRNA–lncRNA interaction effects and main effects of lncRNA on overall survival of NSCLC. Hence, we performed a two-phase designed study of lncRNA expression in tumor tissues using 604 NSCLC patients from The Cancer Genome Atlas as the discovery phase and 839 patients from Gene Expression Omnibus as the validation phase. In the discovery phase, we adopted a two-step strategy, Screening before Testing , for dimension reduction and signal detection. These candidate lncRNAs first screened out by the weighted random forest (Ranger), were then tested through the Cox proportional hazards model adjusted for covariates. Significant lncRNAs with either type of effects aforementioned were carried forward into the validation phase to confirm their significances again. As a result, in the discovery phase, 19 lncRNAs were identified by Ranger, among which five lncRNAs and one pair of lncRNA–lncRNA interaction exhibited significant effects (FDR- q ≤ 0.05) main and interaction effects on NSCLC survival, respectively, through Cox model. After the independent validation, we finally observed that one lncRNA (ENSG00000227403.1) with main effect was robustly associated with NSCLC prognosis ( HR discovery = 0.90, P = 1.20 × 10 –3 ; HR validation = 0.94, P = 4.11 × 10 –3 ) and one pair of lncRNAs (ENSG00000267121.4 and ENSG00000272369.1) had significant interaction effect on NSCLC survival ( HR discovery = 1.12, P = 3.07 × 10 –4 ; HR validation = 1.11, P = 0.0397). Our comprehensive NSCLC prognostic study of lncRNA provided population-level evidence for further functional study.

Correction to: Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Heavy metal pollution from copper smelting during the Shang Dynasty at the Laoniupo site in the Bahe River valley, Guanzhong Basin, China - Menglei Wu; Yana Jia; Yuzhu Zhang; Rui Wen; Jiahua Guo; Ninglian Wang; Wanqing Liu; Haijun Qiu; Haoyu Wang; Yiheng Xian; Chun Yu; Ting Yang (Journal of Geographical Sciences, 2021)

Gastrodin Regulates the Notch Signaling Pathway and Sirt3 in Activated Microglia in Cerebral Hypoxic-Ischemia Neonatal Rats and in Activated BV-2 Microglia - Jing Guo; Xiao-Li-Na Zhang; Zhang-Rui Bao; Xue-Ke Yang; Ling-Shuang Li; Yu Zi; Fan Li; Chun-Yun Wu; Juan-Juan Li; Yun Yuan (NeuroMolecular Medicine, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

Contaminant transport in heterogeneous aquifers: A critical review of mechanisms and numerical methods of non-Fickian dispersion - Zhilin Guo; Rui Ma; Yong Zhang; Chunmiao Zheng (Science China Earth Sciences, 2021)

Dynamic vertical and rocking impedances of a strip foundation in offshore engineering - Rui He; Jisheng Zhang; Zhen Guo; Weiyun Chen (Marine Georesources & Geotechnology, 2021)

Lateral Hypothalamic Area Glutamatergic Neurons and Their Projections to the Lateral Habenula Modulate the Anesthetic Potency of Isoflurane in Mice - Shiyi Zhao; Rui Li; Huiming Li; Sa Wang; Xinxin Zhang; Dan Wang; Juan Guo; Huihui Li; Ao Li; Tingting Tong; Haixing Zhong; Qianzi Yang; et al. (Neuroscience Bulletin, 2021)
The lateral hypothalamic area (LHA) plays a pivotal role in regulating consciousness transition, in which orexinergic neurons, GABAergic neurons, and melanin-concentrating hormone neurons are involved. Glutamatergic neurons have a large population in the LHA, but their anesthesia-related effect has not been explored. Here, we found that genetic ablation of LHA glutamatergic neurons shortened the induction time and prolonged the recovery time of isoflurane anesthesia in mice. In contrast, chemogenetic activation of LHA glutamatergic neurons increased the time to anesthesia and decreased the time to recovery. Optogenetic activation of LHA glutamatergic neurons during the maintenance of anesthesia reduced the burst suppression pattern of the electroencephalogram (EEG) and shifted EEG features to an arousal pattern. Photostimulation of LHA glutamatergic projections to the lateral habenula (LHb) also facilitated the emergence from anesthesia and the transition of anesthesia depth to a lighter level. Collectively, LHA glutamatergic neurons and their projections to the LHb regulate anesthetic potency and EEG features.

A new dineolignan with anti- β -amyloid aggregation activity from the fruits of crataegus pinnatifida bge - Peng Zhao; Li-Li Lou; Hao Zhang; Rui Guo; Xiao-Bo Wang; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Systematic analysis of differentially expressed ZmMYB genes related to drought stress in maize - Peng-Yu Zhang; Xiao Qiu; Jia-Xu Fu; Guo-Rui Wang; Li Wei; Tong-Chao Wang (Physiology and Molecular Biology of Plants, 2021)

How the variations of terrain factors affect the optimal interpolation methods for multiple types of climatic elements? - Bing Guo; Fei Yang; Hongwei Wu; Rui Zhang; Wenqian Zang; Cuixia Wei; Guangmao Jiang; Chao Meng; Huihui Zhao; Xiaoyan Zhen; Dafu Zhang; Hailing Zhang (Earth Science Informatics, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Different physiological responses of C3 and C4 plants to nanomaterials - Tonghao Bai; Peng Zhang; Zhiling Guo; Andrew J. Chetwynd; Mei Zhang; Muhammad Adeel; Mingshu Li; Kerui Guo; Ruize Gao; Jianwei Li; Yi Hao; Yukui Rui (Environmental Science and Pollution Research, 2021)

Temporal and spatial evolution patterns of drought in China over the past 500 years - Cuixia Wei; Bing Guo; Wenqian Zang; Fei Yang; Yuefeng Lu; Dafu Zhang; Hongwei Wu; Xiaoyan Zhen; Haorun Xue; Chao Meng; Shuting Chen; Xiao Yang; et al. (Arabian Journal of Geosciences, 2021)

Divergent Projection Patterns Revealed by Reconstruction of Individual Neurons in Orbitofrontal Cortex - Junjun Wang; Pei Sun; Xiaohua Lv; Sen Jin; Anan Li; Jianxia Kuang; Ning Li; Yadong Gang; Rui Guo; Shaoqun Zeng; Fuqiang Xu; Yu-Hui Zhang (Neuroscience Bulletin, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Diversity-oriented synthesis and antifungal activities of novel pimprinine derivative bearing a 1,3,4-oxadiazole-5-thioether moiety - Zi-Long Song; Yun Zhu; Jing-Rui Liu; Shu-Ke Guo; Yu-Cheng Gu; Xinya Han; Hong-Qiang Dong; Qi Sun; Wei-Hua Zhang; Ming-Zhi Zhang (Molecular Diversity, 2021)

Gentianella acuta prevents acute myocardial infarction induced by isoproterenol in rats via inhibition of galectin-3/TLR4/MyD88/NF-кB inflammatory signalling - Jia-Huan Sun; Hong-Xia Yang; Ting-Ting Yao; Yuan Li; Lin Ruan; Geng-Rui Xu; Chuang Zhang; Guo-Xin Guo; Ai-Ying Li (Inflammopharmacology, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Geochemistry and zircon U-Pb ages of the Oligocene sediments in the Baiyun Sag, Zhujiang River Mouth Basin - Rui Sun; Ming Ma; Kai Zhong; Xiayang Wang; Zhao Zhao; Shuai Guo; Xingzong Yao; Gongcheng Zhang (Acta Oceanologica Sinica, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Light grazing facilitates carbon accumulation in subsoil in Chinese grasslands: A meta‐analysis - Zhi‐Yun Jiang; Zhong‐Min Hu; Derrick Y. F. Lai; Dao‐Rui Han; Mei Wang; Min Liu; Meng Zhang; Ming‐Yan Guo (Global Change Biology, 2020)
Grazing by livestock greatly affects the soil carbon (C) cycle in grassland ecosystems. However, the effects of grazing at different intensities and durations on the dynamics of soil C in its subsoil layers are not clearly understood. Here, we compiled data from 78 sites (in total 122 published studies) to examine the effects of varying grazing intensities and durations on soil C content at different depths for grasslands in China. Our meta‐analysis revealed that grazing led to an overall decrease in soil C content and productivity of above‐ground vegetation (e.g., above‐ground biomass and litter) but an increase in below‐ground biomass. Specifically, the effects of grazing on soil C content became less negative or even positive with increasing soil depths. An increase of soil C content was consequently found under light grazing (LG), although soil C content still decreased under moderate and heavy grazing. The increase in soil C content under LG could be largely attributed to the increase of soil C content in subsoil layers (>20 cm), despite that soil C content in surface soil layer (0–20 cm) decreased. Moreover, the magnitude of increase in soil C content under LG in subsoil layers increased with grazing duration. A possible reason of the increase in soil C content in the subsoil layers was due to the increases in below‐ground biomass. Our study highlights that LG may modify the allocation of C input and promote its accumulation in subsoil layers, thus offsetting the negative impact of grazing on surface soil C content, a finding that has significant implications for C sequestration in grasslands.

Prevalence of Clonorchis sinensis infection in fish in South‐East Asia: A systematic review and meta‐analysis - Ying Zhang; Qing‐Long Gong; Qing‐Bo Lv; Yang‐Yuan Qiu; Yan‐Chun Wang; Hong‐Yu Qiu; Xin‐Rui Guo; Jun‐Feng Gao; Qiao‐Cheng Chang; Chun‐Ren Wang (Journal of Fish Diseases, 2020)
Clonorchis sinensis , an important fish‐borne zoonotic trematode, is widely distributed in South‐East Asia, especially in China. Infections from human and animal reservoir hosts occur due to the consumption of raw or undercooked fish with C. sinensis metacercariae. This study aimed to evaluate the prevalence of C. sinensis metacercariae in fish in South‐East Asia via systematic review and meta‐analysis. We searched PubMed, ScienceDirect, China National Knowledge Infrastructure, Wanfang and Chongqing VIP databases for studies published between 1976 and 2020 that are related to the prevalence of C. sinensis metacercariae in fish. Studies were screened with keywords based on inclusion and exclusion criteria. Seventy‐one eligible articles were identified, covering three countries: China, Korea and Vietnam. The pooled prevalence of C. sinensis metacercariae in fish from South‐East Asia was 30.5%, with 35.1% in China, 29.7% in Korea and 8.4% in Vietnam. In subgroup analyses of climate, season, water source and publication date, the highest prevalence was identified in the Dwb climate type (43.3%), summer (70.2%), river (34.5%) and pre‐2001 publications (38.9%), respectively. In comparison, the lowest prevalence was found in the Dfa climate type (14.5%), winter (19.5%), lake (8.0%) and post‐2001 publications (23.8%). Meta‐regression results indicated that country ( p = .009), the published time ( p = .035) and water source subgroups ( p = .003) may be the source of heterogeneity. Overall, our study indicates that a high prevalence of C. sinensis infections occurs in fish in China, Korea and Vietnam, illuminating a significant public health concern in these countries.

Hydrogeochemical and isotopic characteristics of groundwater in Xinchang preselected site and their implications - Zhichao Zhou; Ju Wang; Rui Su; Yonghai Guo; Jingbo Zhao; Ming Zhang; Ruili Ji; Yanan Li; Jiebiao Li (Environmental Science and Pollution Research, 2020)

Fluoride Inhibits Longitudinal Bone Growth by Acting Directly at the Growth Plate in Cultured Neonatal Rat Metatarsal Bones - Rui Ma; Shuang Liu; Tingting Qiao; Demin Li; Ruixue Zhang; Xiaoying Guo (Biological Trace Element Research, 2020)

Complete genome sequence of a novel mycovirus isolated from the phytopathogenic fungus Corynespora cassiicola in China - Yanfen Wang; Hang Zhao; Caiying Xue; Chao Xu; Yuehua Geng; Rui Zang; Yuxia Guo; Haiyan Wu; Meng Zhang (Archives of Virology, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Cloning and expression of Allophycocyanin gene from Gracilariopsis lemaneiformis and studying the binding sites of phycocyanobilin on its α and β subunits - Yalin Guo; Xiaonan Zang; Xuexue Cao; Feng Zhang; Deguang Sun; Menghui Shang; Rui Li; Zhaxi Yangzong; Xuehong Wei; Xuecheng Zhang (Journal of Applied Phycology, 2020)

Transcriptome Profile Analysis of Resistance Inoculated by Dryopteris crassirhizoma Dryocrassin ABBA in Potato Tubers - Wenzhong Wang; Rui Gao; Tong Zhang; Lingling Chen; Peng Feng; Zongbao Zhao; Changxu Zhang; Fanxiang Min; Shuai Yang; Qi Wei; Mei Guo; Ying Chang (American Journal of Potato Research, 2020)

α -Tetralone glycosides from the green walnut husks of Juglans mandshurica Maxim. and their cytotoxic activities - Yuan-Yuan Zhou; Shuang Guo; Ying Wang; Hong-Juan Song; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Dissecting the Potential of Selenoproteins Extracted from Selenium-Enriched Rice on Physiological, Biochemical and Anti-Ageing Effects In Vivo - Rui Zeng; Muhammad Umer Farooq; Guo Zhang; Zhichen Tang; Tengda Zheng; Yang Su; Sajad Hussain; Yuanke Liang; Xiaoying Ye; Xiaomei Jia; Jianqing Zhu (Biological Trace Element Research, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Synthesis, pharmacological evaluation and molecular docking of novel R-/S-2-(2-hydroxypropanamido)-5-trifluoromethyl benzoic acid as dual anti-inflammatory anti-platelet aggregation agents - Rong Rong; Rui-zhen Zhang; Xin Wang; Yu-han Dan; Yun-li Zhao; Zhi-guo Yu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Release of tartrate as a major carboxylate by alfalfa (Medicago sativa L.) under phosphorus deficiency and the effect of soil nitrogen supply - Honghua He; Miaomiao Wu; Lei Guo; Chenbin Fan; Zekun Zhang; Rui Su; Qi Peng; Jiayin Pang; Hans Lambers (Plant and Soil, 2020)

Plasma Endostatin Levels at Acute Phase of Ischemic Stroke Are Associated with Post-Stroke Cognitive Impairment - Sifan Qian; Ruyi Li; Chenhuan Zhang; Rui Zhang; Daoxia Guo; Xiaoqing Bu; Aili Wang; Hao Peng; Jing Chen; Yonghong Zhang; Jiang He; Tan Xu; et al. (Neurotoxicity Research, 2020)

The enhancement of NH3-SCR performance for CeO2 catalyst by CO pretreatment - Ping Zhang; Rui-tang Guo; Li-jun Wu; Wei-guo Pan (Environmental Science and Pollution Research, 2020)

Cenozoic tectonics and landform evolution in the Qilian Mountains and adjacent areas - Kai Du; Lirong Yang; Rui Zhang; Leping Yue; Huaijun Guo; Yunxiang Zhang; Jianxing Li; Hujun Gong (International Geology Review, 2020)

Effects of florfenicol exposure on growth, development and antioxidant capacity of flounder Paralichthys olivaceus larvae at different developmental stages - Rui Guo; Yingqi Zhang; Xianyu Zhang; Qian Zhang; Rui Cheng; Rahman Md Mostafizur; Ying Liu (Journal of Oceanology and Limnology, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Molecular mapping of the gene(s) conferring resistance to Soybean mosaic virus and Bean common mosaic virus in the soybean cultivar Raiden - Mian Wu; Ying-Na Liu; Cong Zhang; Xue-Ting Liu; Cheng-Chen Liu; Rui Guo; Ke-Xin Niu; An-Qi Zhu; Jia-Yin Yang; Jian-Qun Chen; Bin Wang (Theoretical and Applied Genetics, 2019)

Urbanization and CO2 emissions in resource-exhausted cities: evidence from Xuzhou city, China - Shanshan Guo; Yanfang Zhang; Xiangyan Qian; Zhang Ming; Rui Nie (Natural Hazards, 2019)

Design and Experiment of a Plateau Data-Gathering AUV - Hao Xu; Guo-Cheng Zhang; Yu-Shan Sun; Shuo Pang; Xiang-Rui Ran; Xiang-Bin Wang (Journal of Marine Science and Engineering, 2019)
The design, control, and implementation of an autonomous underwater vehicle (AUV) for collecting hydrological information from plateau rivers and lakes are presented in this paper. The hardware and software structures of the control system were previously described. A novel sliding mode controller (SMC) with combinational reaching law of vertical hovering motion is proposed to improve the robustness and stability. The S-plane control, a nonlinear controller with little parameters, is used in the horizontal motion. Besides, the navigation strategy based on the dead-reckoning algorithm, a path tracking based on the light-of-sight (LOS) algorithm, and a control allocation strategy considering saturation are present. Finally, experiments were performed in a tank and in a river in the Qinghai–Tibet Plateau to prove the feasibility and reliability of the AUV system.

Integrated analysis of miRNAs and their targets reveals that miR319c/TCP2 regulates apical bud burst in tea plant (Camellia sinensis) - Shengrui Liu; Xiaozeng Mi; Ran Zhang; Yanlin An; Qiying Zhou; Tianyuan Yang; Xiaobo Xia; Rui Guo; Xuewen Wang; Chaoling Wei (Planta, 2019)

The faster-onset antidepressant effects of hypidone hydrochloride (YL-0919) - Li-jun Sun; Li-ming Zhang; Dan Liu; Rui Xue; Yan-qin Liu; Lei Li; Ying Guo; Chao Shang; Jun-qi Yao; You-zhi Zhang; Yun-feng Li (Metabolic Brain Disease, 2019)

Bivariate copula function-based spatial–temporal characteristics analysis of drought in Anhui Province, China - Rui Wang; Chunli Zhao; Jiquan Zhang; Enliang Guo; Danjun Li; Si Alu; Si Ha; Zhenhua Dong (Meteorology and Atmospheric Physics, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Nitrogen use-inefficient oilseed rape genotypes exhibit stronger growth potency during the vegetative growth stage - Xiao Guo; Huiying He; Rong An; Yuying Zhang; Rui Yang; Lanqin Cao; Xiaoming Wu; Biyun Chen; Hui Tian; Yajun Gao (Acta Physiologiae Plantarum, 2019)

Transcriptional regulation contributes more to Monascus pigments diversity in different strains than to DNA sequence variation - Xiaoyu Guo; Yao Li; Rui Zhang; Jiyuan Yu; Xinbao Ma; Mianhua Chen; Yurong Wang (World Journal of Microbiology and Biotechnology, 2019)

A new triterpene from the green walnut husks of Juglans mandshurica Maxim - Yuan-Yuan Zhou; Hong-Juan Song; Shuang Guo; Ying Wang; Hui-Rui Gao; Xiao-Juan Zhang; Yan-Ping Sun; Yan Liu; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2019)

Lithological identification with probabilistic distribution by the modified compositional Kriging - Feilong Han; Hongbing Zhang; Qiang Guo; Jianwen Rui; Qiuyan Ji (Arabian Journal of Geosciences, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Dynamic Impedances of Offshore Rock-Socketed Monopiles - Rui He; Ji Ji; Jisheng Zhang; Wei Peng; Zufeng Sun; Zhen Guo (Journal of Marine Science and Engineering, 2019)
With the development of offshore wind energy in China, more and more offshore wind turbines are being constructed in rock-based sea areas. However, the large diameter and thin-walled steel rock-socketed monopiles are very scarce at present, and both the construction and design are very difficult. For the design, the dynamic safety during the whole lifetime of the wind turbine is difficult to guarantee. Dynamic safety of a turbine is mostly controlled by the dynamic impedances of the rock-socketed monopile, which are still not well understood. How to choose the appropriate impedances of the socketed monopiles so that the wind turbines will neither resonant nor be too conservative is the main problem. Based on a numerical model in this study, the accurate impedances are obtained for different frequencies of excitation, different soil and rock parameters, and different rock-socketed lengths. The dynamic stiffness of monopile increases, while the radiative damping decreases as rock-socketed depth increases. When the weathering degree of rock increases, the dynamic stiffness of the monopile decreases, while the radiative damping increases.

Spatial distribution, source identification, and potential risk assessment of toxic contaminants in surface waters from Yulin, China - Jing Liu; Yongjun Liu; Aining Zhang; Yu Liu; Ying Zhu; Ming Guo; Rui Zhang (Environmental Monitoring and Assessment, 2019)

Calpain-2 promotes MKP-1 expression protecting cardiomyocytes in both in vitro and in vivo mouse models of doxorubicin-induced cardiotoxicity - Dong Zheng; Zhaoliang Su; Yi Zhang; Rui Ni; Guo-Chang Fan; Jeffrey Robbins; Long-Sheng Song; Jianmin Li; Tianqing Peng (Archives of Toxicology, 2019)

Comparative detection of Karenia mikimotoi by exponential rolling circle amplification (E-RCA) and double-ligation E-RCA - Chunyun Zhang; Rui Sun; Yuanyuan Wang; Guofu Chen; Changlu Guo; Jin Zhou (Journal of Applied Phycology, 2019)

Luminescence chronology of the Palaeolithic–Neolithic transition in the Yujiagou site at the Nihewan Basin, northern China - Xue Rui; Yu‐Jie Guo; Jia‐Fu Zhang; Yue Hu; Hui‐Jie Mei; You‐Ping Wang; Fei Xie; Bo Li (Journal of Quaternary Science, 2019)
The relationship between the Palaeolithic–Neolithic cultural transition and environmental changes is important for understanding human history. However, the timing and nature of human behaviour at the transition, and their relationship to local environmental conditions, remain poorly understood. The Yujiagou archaeological site in the Nihewan Basin, northern China, provides valuable chronological and archaeological information about cultural changes in northern China due to its continuous archaeological sequence of cultural layers from the Palaeolithic to Neolithic. In this study, we apply post‐infrared infrared stimulated luminescence (pIRIR) dating on individual feldspar grains to date the Yujiagou deposits. We provide a revised chronology for the archaeological sequence at the site. We combine these results with multi‐proxy climatic indicators to gain insights into palaeoenvironmental changes in the region. The results show that the age of the artefact‐bearing deposits ranges from 13.5 to 9.7 ka. Polished stones and pottery begin to occur in the archaeological layer around 13 ka, corresponding to a transitional period when the local climate changed from cold to warm. This site provides evidence for understanding the process that led to the regional transition from hunter‐gathering to farming.

Integrated drought risk assessment of multi-hazard-affected bodies based on copulas in the Taoerhe Basin, China - Rui Wang; Jiquan Zhang; Enliang Guo; Si Alu; Danjun Li; Si Ha; Zhenhua Dong (Theoretical and Applied Climatology, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Relative Telomere Length and Stroke Risk in a Chinese Han Population - Dan Gao; Rui Zhang; Guofa Ji; Chunqi Li; Dangshe Guo; Tianbo Jin; Mingwei Chen (Journal of Molecular Neuroscience, 2018)

Transgenic Rice Overexperessing a Tomato Mitochondrial Phosphate Transporter, SlMPT3;1, Promotes Phosphate Uptake and Increases Grain Yield - Guo-hong Yu; Sheng-cai Huang; Rui He; Ying-zhang Li; Xian-guo Cheng (Journal of Plant Biology, 2018)

Neuregulin-1β Plays a Neuroprotective Role by Inhibiting the Cdk5 Signaling Pathway after Cerebral Ischemia-Reperfusion Injury in Rats - Rui Zhang; Cui Liu; Yaqing Ji; Lei Teng; Yunliang Guo (Journal of Molecular Neuroscience, 2018)

Biglycan, a Nitric Oxide-Downregulated Proteoglycan, Prevents Nitric Oxide-Induced Neuronal Cell Apoptosis via Targeting Erk1/2 and p38 Signaling Pathways - Sujuan Chen; Dandan Guo; Wei Zhang; Yunfei Xie; Haijie Yang; Binfeng Cheng; Lei Wang; Rui Yang; Jiajia Bi; Zhiwei Feng (Journal of Molecular Neuroscience, 2018)

Sperm Morphology and Motility of Bufo raddei Under Long-Term Environmental Heavy Metal Stress - Rui Guo; Wenya Zhang; Ying Yang; Jian Ding; Shiwei Ai; Wenzhi Yang; Xiaojuan Bai; Yingmei Zhang (Bulletin of Environmental Contamination and Toxicology, 2018)

Cascades of Ionic and Molecular Networks Involved in Expression of Genes Underpin Salinity Tolerance in Cotton - Muhammad Ali Abid; Chengzhen Liang; Waqas Malik; Zhigang Meng; Zhu Tao; Zhaoghong Meng; Javaria Ashraf; Sandui Guo; Rui Zhang (Journal of Plant Growth Regulation, 2018)

Assessing non-linear variation of temperature and precipitation for different growth periods of maize and their impacts on phenology in the Midwest of Jilin Province, China - Enliang Guo; Jiquan Zhang; Yongfang Wang; Si Alu; Rui Wang; Danjun Li; Si Ha (Theoretical and Applied Climatology, 2018)

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Potentiation effects by usnic acid in combination with antibiotics on clinical multi-drug resistant isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Guo-Ying Zuo; Rui-Chun Fu; Wei Yu; Yun-Ling Zhang; Gen-Chun Wang (Medicinal Chemistry Research, 2018)

A novel bispecific antibody fusion protein co-targeting EGFR and CD47 with enhanced therapeutic index - Yun Yang; Rui Guo; Qi Chen; Youxun Liu; Pengfei Zhang; Ziheng Zhang; Xi Chen; Tianyun Wang (Biotechnology Letters, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

The Arc Gene Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Rui Bi; Li-Li Kong; Min Xu; Guo-Dong Li; Deng-Feng Zhang; Tao Li; Yiru Fang; Chen Zhang; Buchang Zhang; Yong-Gang Yao (Molecular Neurobiology, 2018)

Genomic analysis of a recombinant NADC30-like porcine reproductive and respiratory syndrome virus in china - Lin-jian Wang; Bo Wan; Zhenhua Guo; Songlin Qiao; Rui Li; Sha Xie; Xin-xin Chen; Gaiping Zhang (Virus Genes, 2018)

Association between coal consumption and urbanization in a coal-based region: a multivariate path analysis - Xiaojia Guo; Zilong Zhang; Rui Zhao; Guokui Wang; Jing Xi (Environmental Science and Pollution Research, 2018)

Residents’ environmental conservation behaviour in the mountain tourism destinations in China: Case studies of Jiuzhaigou and Mount Qingcheng - Yu-ling Zhang; Jie Zhang; Hong-ou Zhang; Ruo-yang Zhang; Yang Wang; Yong-rui Guo; Zong-cai Wei (Journal of Mountain Science, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

White Matter Connectivity Pattern Associate with Characteristics of Scalp EEG Signals - Jinnan Gong; Cheng Luo; Xuebin Chang; Rui Zhang; Benjamin Klugah-Brown; Lanjin Guo; Peng Xu; Dezhong Yao (Brain Topography, 2017)

Voronoi Cell Finite Element Method for Fluid-Filled Materials - Rui Zhang; Ran Guo (Transport in Porous Media, 2017)

Association of ACYP2 and TSPYL6 Genetic Polymorphisms with Risk of Ischemic Stroke in Han Chinese Population - Yiqian Liang; Rui Zhang; Shuo Zhang; Guofa Ji; Puyu Shi; Tian Yang; Feng Liu; Jing Feng; Chunqi Li; Dangshe Guo; Mingwei Chen (Molecular Neurobiology, 2017)

Behavioral responses of the egg parasitoid Trissolcus japonicus to volatiles from adults of its stink bug host, Halyomorpha halys - Yong-Zhi Zhong; Jin-Ping Zhang; Li-Li Ren; Rui Tang; Hai-Xia Zhan; Guo-Hua Chen; Feng Zhang (Journal of Pest Science, 2017)

A simple method for removing low-density granulocytes to purify T lymphocytes from peripheral blood mononuclear cells - Si-gong Zhang; Yu-xin Song; Xiao-ming Shu; Hai-li Shen; Han-bo Yang; Rui-xue Duo; Guo-chun Wang (Journal of Zhejiang University-SCIENCE B, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Fluctuating asymmetry rather than oxidative stress in Bufo raddei can be an accurate indicator of environmental pollution induced by heavy metals - Rui Guo; Wenya Zhang; Shiwei Ai; Liang Ren; Yingmei Zhang (Environmental Monitoring and Assessment, 2017)

Increased lateral root formation by CRISPR/Cas9-mediated editing of arginase genes in cotton - Yanling Wang; Zhigang Meng; Chengzhen Liang; Zhaohong Meng; Yuan Wang; Guoqing Sun; Tao Zhu; Yongping Cai; Sandui Guo; Rui Zhang; Yi Lin (Science China Life Sciences, 2017)

Paleogene-Neogene stratigraphic realm and tectonic-sedimentary evolution of the Qilian Mountains and their surrounding areas - LiRong Yang; JianXing Li; LePing Yue; HongLiang Wang; HuaiJun Guo; XiaoHui Zhu; Tao Zhu; Kai Du; Rui Zhang; YunXiang Zhang; HuJun Gong (Science China Earth Sciences, 2017)

Carboxyamidotriazole alleviates muscle atrophy in tumor-bearing mice by inhibiting NF-κB and activating SIRT1 - Chen Chen; Rui Ju; Lei Zhu; Juan Li; Wei Chen; De-chang Zhang; Cai-ying Ye; Lei Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Physiological characteristics and metabolomics of transgenic wheat containing the maize C4 phosphoenolpyruvate carboxylase (PEPC) gene under high temperature stress - Xueli Qi; Weigang Xu; Jianzhou Zhang; Rui Guo; Mingzhong Zhao; Lin Hu; Huiwei Wang; Haibin Dong; Yan Li (Protoplasma, 2017)

Two new compounds from Trollius chinensis Bunge - Ya Jie-Shi; Lin Wei-Sang; Rui Yan; Qiang Zhao; Yang Zhang; Gui Yun-Zhao; Yun Cong-Li; Xue Chen; Chong Yu-Zhang; Hua Qiao; Guo Gang-Zhang (Journal of Natural Medicines, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

MicroRNA-9 Mediates the Cell Apoptosis by Targeting Bcl2l11 in Ischemic Stroke - Na Wei; Lin Xiao; Rui Xue; Dandan Zhang; Jun Zhou; Huayan Ren; Si Guo; Jingjing Xu (Molecular Neurobiology, 2016)

Thermal state of soils in the active layer and underlain permafrost at the kilometer post 304 site along the China-Russia Crude Oil Pipeline - Yong-ping Wang; Guo-yu Li; Hui-jun Jin; Lan-zhi Lu; Rui-xia He; Peng Zhang (Journal of Mountain Science, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Erythropoietin Attenuates the Memory Deficits in Aging Rats by Rescuing the Oxidative Stress and Inflammation and Promoting BDNF Releasing - Zhankui Jia; Rui Xue; Shengli Ma; Jingjing Xu; Si Guo; Songchao Li; Erwei Zhang; Jun Wang; Jinjian Yang (Molecular Neurobiology, 2016)

A field study on the dynamic uptake and transfer of heavy metals in Chinese cabbage and radish in weak alkaline soils - Shiwei Ai; Rui Guo; Bailin Liu; Liang Ren; Sajid Naeem; Wenya Zhang; Yingmei Zhang (Environmental Science and Pollution Research, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Mitochondrial DNA Haplogroup A Decreases the Risk of Drug Addiction but Conversely Increases the Risk of HIV-1 Infection in Chinese Addicts - A-Mei Zhang; Qiu-Xiang Hu; Feng-Liang Liu; Rui Bi; Bi-Qing Yang; Wen Zhang; Hao Guo; Ian Logan; Yong-Tang Zheng; Yong-Gang Yao (Molecular Neurobiology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Functional divergence of GhCFE5 homoeologs revealed in cotton fiber and Arabidopsis root cell development - Fenni Lv; Peng Li; Rui Zhang; Nina Li; Wangzhen Guo (Plant Cell Reports, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

ZmDBF3, a Novel Transcription Factor from Maize (Zea mays L.), Is Involved in Multiple Abiotic Stress Tolerance - Wei Zhou; Cheng-Guo Jia; Xian Wu; Rui-Xue Hu; Gang Yu; Xiang-Hui Zhang; Jin-Liang Liu; Hong-Yu Pan (Plant Molecular Biology Reporter, 2016)

Association between the MTHFR A1298C polymorphism and risk of cancer: evidence from 265 case–control studies - Xin-Li Zhu; Zhi-Zhong Liu; Sen-Xiang Yan; Wei Wang; Rui-Xia Chang; Chun-Yan Zhang; Yan Guo (Molecular Genetics and Genomics, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Two new eunicellin diterpenoids from the South China Sea gorgonian Muricella sibogae and their bioactivities - Xing-Wang Zhang; Xu-Li Tang; Hong-Rui Yuan; Dan-Qing Feng; Pei Su; Ping-Lin Li; Guo-Qiang Li (Natural Product Research, 2015)

Distribution of the Vrn-D1b allele associated with facultative growth habit in Chinese wheat accessions - Xian-rui Guo; Yuan-yuan Wang; Ling-zhi Meng; Hong-wei Liu; Li Yang; Yang Zhou; Hong-jun Zhang (Euphytica, 2015)

A Hybrid Positive-and-Negative Curvature Approach for Detection of the Edges of Magnetic Anomalies, and Its Application in the South China Sea - Lianghui Guo; Rui Gao; Xiaohong Meng; Guoli Zhang (Pure and Applied Geophysics, 2015)

p55γ functional mimetic peptide N24 blocks vascular proliferative disorders - Jiaojiao Guo; Ning Xie; Geng Li; Yan Zhang; Fengxiang Lv; Sile Guo; Yuanqing Feng; Chun-Mei Cao; Rui-Ping Xiao (Journal of Molecular Medicine, 2015)

Metaproteomic analysis of bacterial communities in marine mudflat aquaculture sediment - Rui Lin; Xiangmin Lin; Tingting Guo; Linkun Wu; Wenjing Zhang; Wenxiong Lin (World Journal of Microbiology and Biotechnology, 2015)

Atrokylindriopsis, a new genus of hyphomycetes from Hainan, China, with relationship to Chaetothyriales - Ying-Rui Ma; Ji-Wen Xia; Jian-Mei Gao; Xiang-Yu Li; Rafael F. Castañeda Ruíz; Xiu-Guo Zhang; Zhuang Li (Mycological Progress, 2015)

Predicting Inter-session Performance of SMR-Based Brain–Computer Interface Using the Spectral Entropy of Resting-State EEG - Rui Zhang; Peng Xu; Rui Chen; Fali Li; Lanjin Guo; Peiyang Li; Tao Zhang; Dezhong Yao (Brain Topography, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Effects of alfalfa saponin extract on mRNA expression of Ldlr, LXRα, and FXR in BRL cells - Xin-ping Liang; Dong-qiang Zhang; Yan-yan Chen; Rui Guo; Jie Wang; Cheng-zhang Wang; Ying-hua Shi (Journal of Zhejiang University-SCIENCE B, 2015)

Characterization of genomic sequence of a drought-resistant gene TaSnRK2.7 in wheat species - HONG YING ZHANG; WEI LI; XIN GUO MAO; RUI LIAN JING (Journal of Genetics, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Heterologous expression and characterization of a novel halotolerant, thermostable, and alkali-stable GH6 endoglucanase from Thermobifida halotolerans - Yi-Rui Yin; Feng Zhang; Qing-Wen Hu; Wen-Dong Xian; Wael N. Hozzein; En-Min Zhou; Hong Ming; Guo-Xing Nie; Wen-Jun Li (Biotechnology Letters, 2015)

Solubilization of 4,4′-dibromodiphenyl ether under combined TX-100 and cosolvents - Xingjian Yang; Guining Lu; Rui Wang; Chuling Guo; Hongliang Zhang; Zhi Dang (Environmental Science and Pollution Research, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

An 18-element GEO broadcast ephemeris based on non-singular elements - Lan Du; Zhongkai Zhang; Jin Zhang; Li Liu; Rui Guo; Feng He (GPS Solutions, 2015)

Spatial characteristics of development efficiency for urban tourism in eastern China: A case study of six coastal urban agglomerations - Rui Li; Qian Guo; Dianting Wu; Hongmei Yin; Hua Zhang; Taoxing Zhu (Journal of Geographical Sciences, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Chemical constituents from Melastoma dodecandrum and their inhibitory activity on interleukin-8 production in HT-29 cells - Guo-Xun Yang; Rui-Ze Zhang; Bin Lou; Ke-Jun Cheng; Juan Xiong; Jin-Feng Hu (Natural Product Research, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Two new species of Spadicoides and Gangliostilbe from southern China - Li-Guo Ma; Ji-Wen Xia; Ying-Rui Ma; Rafael F. Castañeda-Ruíz; Xiu-Guo Zhang (Mycological Progress, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Streptomyces calidiresistens sp. nov., isolated from a hot spring sediment - Yan-Yan Duan; Hong Ming; Lei Dong; Yi-Rui Yin; Yi Zhang; En-Min Zhou; Lan Liu; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Zircon geochronology constraints on the age and nature of ‘Precambrian metamorphic rocks’ in the Xing’an block of Northeast China - Wei Sun; Xiao-Guo Chi; Zhi Zhao; Shi-Yu Pan; Jian-Feng Liu; Rui Zhang; Jing-Yu Quan (International Geology Review, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

The role of Somatic embryogenesis receptor-like kinase 1 in controlling pollen production of the Gossypium anther - Ya-li Shi; San-dui Guo; Rui Zhang; Zhi-gang Meng; Mao-zhi Ren (Molecular Biology Reports, 2014)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Evaluation of salinity tolerance in seedlings of sugar beet (Beta vulgaris L.) cultivars using proline, soluble sugars and cation accumulation criteria - Guo-Qiang Wu; Na Liang; Rui-Jun Feng; Jing-Jing Zhang (Acta Physiologiae Plantarum, 2013)

Molecular Cloning and Characterization of the PsbP Domain Protein 1 Gene (GhPPD1) in Cotton (Gossypium hirsutum L.) - Tao Zhou; Rui Zhang; Maozhi Ren; Shasha Zhang; Qin Lin; Sandui Guo (Plant Molecular Biology Reporter, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Optimization of biotransformation from phytosterol to androstenedione by a mutant Mycobacterium neoaurum ZJUVN-08 - Xiao-yan Zhang; Yong Peng; Zhong-rui Su; Qi-he Chen; Hui Ruan; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)

Metal-Binding Activity of the Soluble Recombinant Pig Metallothionein 1A Expressed in Escherichia coli - Dongbo Sun; Hong Zhang; Guojun Wu; Qinghe Zhu; Siwen Lv; Donghua Guo; Rui Wu; Jun Bao (Biological Trace Element Research, 2012)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

Involvement of p38MAPK/NF-κB Signaling Pathways in Osteoblasts Differentiation in Response to Mechanical Stretch - Liang Wang; Jian-yu Li; Xi-zheng Zhang; Lu Liu; Zong-ming Wan; Rui-xin Li; Yong Guo (Annals of Biomedical Engineering, 2012)

Increased expression of calcium-sensing receptors in atherosclerosis confers hypersensitivity to acute myocardial infarction in rats - Jin Guo; Hong-zhu Li; Lu-chuan Wang; Wei-hua Zhang; Guang-wei Li; Wen-jing Xing; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2012)

Highly Selective and Sensitive Chemosensor for Hg2+ Based on the Naphthalimide Fluorophore - Rui Yang; Xiangfeng Guo; Wei Wang; Yu Zhang; Lihua Jia (Journal of Fluorescence, 2012)

Molecular Cloning and Characterization of GhGolS1, a Novel Gene Encoding Galactinol Synthase from Cotton (Gossypium hirsutum) - Tao Zhou; Rui Zhang; Sandui Guo (Plant Molecular Biology Reporter, 2012)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

Purification and partial characterization of glutathione S-transferases from three field populations of Panonychus citri (Acari: Tetranychidae) - Jin-Zhi Niu; Wei Dou; Bao-Jun Wang; Guo-Na Zhang; Rui Zhang; Yi Yin; Jin-Jun Wang (Experimental and Applied Acarology, 2012)

Variation in the internalization of differently sized nanoparticles induces different DNA-damaging effects on a macrophage cell line - Mingyi Zhang; Juan Li; Gengmei Xing; Rui He; Wei Li; Yan Song; Haili Guo (Archives of Toxicology, 2011)

Quantitative analysis of expression of six BmGST genes in silkworm, Bombyx mori - Guo-dong Zhao; Yi-ling Zhang; Rui-na Gao; Rui-xian Wang; Ting Zhang; Bing Li; Yi Zhang; Chang-de Lu; Wei-de Shen; Zheng-guo Wei (Molecular Biology Reports, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Molecular cloning and characterization of GhAPm, a gene encoding the μ subunit of the clathrin-associated adaptor protein complex that is associated with cotton (Gossypium hirsutum) fiber development - Tao Zhou; Rui Zhang; Dawei Yang; Sandui Guo (Molecular Biology Reports, 2011)

The cardioprotective effect of fluvastatin on ischemic injury via down-regulation of toll-like receptor 4 - Jun Yang; Xiao-Dong Zhang; Jian Yang; Jia-Wang Ding; Zhao-Qi Liu; Shu-Guo Li; Rui Yang (Molecular Biology Reports, 2011)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

The functional expression of calcium-sensing receptors in BRL cells and related signal transduction pathway responsible for intracellular calcium elevation - Wenjing Xing; Guangwei Li; Yuhui Xi; Jin Guo; Hongzhu Li; Hongxia Li; Weihua Zhang; Li Zhang; Lingyun Wu; Rui Wang; Changqing Xu (Molecular and Cellular Biochemistry, 2010)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

The influence of ADAR1’s regulation on lymphocyte cell function during rejection - Lei Cai; Yan Li; Feng Liu; Wei Zhang; Binliang Huo; Wei Zheng; Rui Ding; Jiyuan Guo; Qingchuan Zhao; Kefeng Dou (Molecular Biology Reports, 2010)

Salicylic Acid Reduces Napropamide Toxicity by Preventing Its Accumulation in Rapeseed (Brassica napus L.) - Jing Cui; Rui Zhang; Guo Lin Wu; Hong Mei Zhu; Hong Yang (Archives of Environmental Contamination and Toxicology, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

A PKC-β inhibitor protects against cardiac microvascular ischemia reperfusion injury in diabetic rats - Liping Wei; Dongdong Sun; Zhiyong Yin; Yuan Yuan; Andrew Hwang; Yingmei Zhang; Rui Si; Rongqing Zhang; Wenyi Guo; Feng Cao; Haichang Wang (Apoptosis, 2010)

Genetic transformation of the bast fiber plant ramie (Boehmeria nivea Gaud.) via Agrobacterium tumefaciens - Xiongfeng Ma; Chunming Yu; Shouwei Tang; Sandui Guo; Rui Zhang; Yanzhou Wang; Aiguo Zhu; Siyuan Zhu; Heping Xiong (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A missense mutation in the transmembrane domain of CESA4 affects protein abundance in the plasma membrane and results in abnormal cell wall biosynthesis in rice - Baocai Zhang; Lingwei Deng; Qian Qian; Guangyan Xiong; Dali Zeng; Rui Li; Longbiao Guo; Jiayang Li; Yihua Zhou (Plant Molecular Biology, 2009)

Inhibitory effect of reinioside C on monocyte–endothelial cell adhesion induced by oxidized low-density lipoprotein via inhibiting NADPH oxidase/ROS/NF-κB pathway - Yong-Ping Bai; Chang-ping Hu; Mei-Fang Chen; Kang-Ping Xu; Gui-Shan Tan; Rui-Zhen Shi; Yuan-Jian Li; Guo-Gang Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A novel triple-regulated oncolytic adenovirus carrying PDCD5 gene exerts potent antitumor efficacy on common human leukemic cell lines - Min Xie; Ji-Hong Niu; Yan Chang; Qi-Jun Qian; Hong-Ping Wu; Lin-Fang Li; Yao Zhang; Jin-Lan Li; Xiao-Jun Huang; Guo-Rui Ruan (Apoptosis, 2009)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Molecular characterization of grapevine yellow speckle viroid-2 (GYSVd-2) - Dongmei Jiang; Zhixiang Zhang; Zujian Wu; Rui Guo; Hongqing Wang; Peige Fan; Shifang Li (Virus Genes, 2009)

Effect of Neuregulin on Apoptosis and Expressions of STAT3 and GFAP in Rats Following Cerebral Ischemic Reperfusion - Qin Li; Rui Zhang; Yun-liang Guo; Yuan-wu Mei (Journal of Molecular Neuroscience, 2009)

Molecular cloning and characterization of two novel cellulase genes from the mollusc Ampullaria crossean - Rui Guo; Ming Ding; Si-Liang Zhang; Gen-jun Xu; Fu-kun Zhao (Journal of Comparative Physiology B, 2008)

Insulin inhibits β-adrenergic action in ischemic/reperfused heart: a novel mechanism of insulin in cardioprotection - Qiu-Jun Yu; Rui Si; Ning Zhou; Hai-Feng Zhang; Wen-Yi Guo; Hai-Chang Wang; Feng Gao (Apoptosis, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Loop-mediated isothermal amplification for rapid detection of Bacillus anthracis spores - Yan-Mei Qiao; Yong-Chao Guo; Xian-En Zhang; Ya-Feng Zhou; Zhi-Ping Zhang; Hong-Ping Wei; Rui-Fu Yang; Dian-Bing Wang (Biotechnology Letters, 2007)

An experimental study of the mechanisms of freeze/thaw and wind erosion of ancient adobe buildings in northwest China - Jian-Jun Qu; Guo-Dong Cheng; Ke-Cun Zhang; Jia-Cheng Wang; Rui-Ping Zu; Hai-Yan Fang (Bulletin of Engineering Geology and the Environment, 2007)

pEGFP-T, a novel T-vector for the direct, unidirectional cloning and analysis of PCR-amplified promoters - Baoli Wang; Xiaoxia Li; Fang Zheng; Rui Liu; Jinxing Quan; Hui Liang; Shanyi Guo; Gang Guo; Jingyu Zhang (Biotechnology Letters, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Research progress of socio-economic water cycle in China - Jia Shao-feng; Wang Guo; Zhang Shi-feng; Yu Gui-rui; Wang Jin-xia; Xia Jun (Journal of Geographical Sciences, 2002)

New progress of research on water cycle in atmosphere in China - Wang Guo; Jia Shao-feng; Yu Gui-rui; Xu Juan; Wang Jin-xia; Wang Qiu-feng; Ge Quan-sheng; Huang Ji-kun; Xia Jun; Li Li-fnjuan; Jin De-sheng; Dong Suo-cheng; et al. (Journal of Geographical Sciences, 2001)